Geometric-topologically constrained modeling of stochastic fracture networks and uncertainty quantification of dominant factors controlling flow behavior - Peizhuang Han; Qingquan Liu; Lin Ma; Chaofan Chen; Kun Sang Lee; Heinz Konietzky; Dariusz Knez; Yuanping Cheng (Computers and Geotechnics, 2027)

Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Agmatine protects against MAFLD via decreasing RBM15/IGF2BP2-mediated m6A modification of SREBP1 - Guangkui Bu; Yu Li; Guangfu Lin; Lichun Han; Deyi Chen; Xiaoping Lv (Molecular Biology Reports, 2026)

Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

The application of RPA-PfAgo technology combined with multidimensional data analysis in the rapid detection of the MTHFR A1298C polymorphism - Yaqun Liu; Lianghui Chen; Xuanyi Zheng; Peikui Yang; Jinkun Han; Jiayi Huang; Yanling Shen; Xiaotong Cai; Miaofen Fang; Yicun Chen; Chengsong Xie; Min Lin; et al. (Functional & Integrative Genomics, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Astaxanthin activates PI3K/AKT and AMPK signaling to alleviate oxidative stress and improve mouse oocyte In vitro maturation - Mei Zhou; Mengzhen Luo; Yueming Yuan; Liqin Han; Lin Chen; Shangquan Gan (Theriogenology, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Aligning green spaces with human activity: uncovering opportunity-realization mismatches in urban green exposure - Yicheng Zheng; Tao Lin; Nicholas A.S. Hamm; Yuan Chen; Tongyu Zhou; Xiangzhong Guo; Hongkai Geng; Matthew Ng; Hoon Han; Christopher Pettit; Yong-Guan Zhu (Landscape and Urban Planning, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Fire severity shapes uneven early recovery of soil properties, understory vegetation and microbial communities after wildfire in a subtropical Pinus massoniana plantation - Jisi Han; Weixing Xue; Zeyao Zhao; Lin Chen; Zhaogui Yan (Forest Ecology and Management, 2026)

Rhamnogalacturonan I in commercial samples of polygalacturonic acid is a functional driver: A study of isolation, structural elucidation, role in immunostimulation and hydrogel mechanics - Xueting Zhang; Chuying Huo; Pengfei Shan; Niping Chen; Quanwei Zhang; Hauyee Fung; Wenting Zhao; Jing Li; Peili Zhu; Shanlong Tang; Ye Yuan; Lin Sun; et al. (Food Hydrocolloids, 2026)

Effect of boiling and in vitro digestion on nutritional quality and metabolomic profiles of bambara groundnut and soybean protein isolates - Mingmin Chen; Shir Reen Chia; Zhen Zheng; Wei Han Foo; Lin Chen (Food Hydrocolloids, 2026)

Effects of sustained eccentric loading on concrete-encased concrete-filled steel tubular (CFST) columns - Zhi-Cheng Yang; Di Fan; Guan-Yuan Zhao; Li Zhu; Lin-Hai Han; Chen-Yu Zhang (Engineering Structures, 2026)

Structural assessment of post-impact concrete-filled steel tubular (CFST) members based on vibration tests and Bayesian model updating - Shang-Jun Chen; Chuan-Chuan Hou; Lin-Hai Han; Hua Yang (Engineering Structures, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Defect-engineered Cu-TCPP/ZIF-L nanosheet-modified PVDF membrane with enhanced water purification and dye removal performance - Yiming Zhao; Jingyuan Zhang; Junmei Liu; Jiatong Han; Dan Xu; Jing Wang; Fengzhi Lyu; Lin Qin; Donghui Xu; Ge Chen; Guangyang Liu (Chemical Engineering Journal, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Salinity shapes biofilm community to promote partial nitrification and sulfamethoxazole removal in membrane-aerated biofilm reactors - Zhi-Cheng Wu; Yu-Lin Han; Chen-Wei Zheng; He-Ping Zhao (Journal of Water Process Engineering, 2026)

Chalcopyrite as an indicator of uranium mineralization in the Qigequan deposit, western Qaidam Basin: Constraints from mineralogy, geochemistry, and sulfur isotopes - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Wen-Yi Wu; Chen Zhang; Zhe Chi; Zhi-Lin Cheng; Bin Guo; Yi-Fan Gao (Journal of Geochemical Exploration, 2026)

Synergistic modulation of nickel–manganese glycerate via sequential sulfurization and oxidation for high-performance battery–supercapacitor hybrids - Tsung-Rong Kuo; Lu-Yin Lin; Tzu-Han Chou; You-Zher Yu; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen (Journal of Environmental Chemical Engineering, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Preparation of plant-based meat analogues by soft matter method: Effects of NaCl concentrations and addition order - Jing-Wen Zhang; Qin Yang; Hui-Lin Li; Qing-Xuan Liu; Han-Qing Chen (Food Hydrocolloids, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Immune response as a modifier linking phthalate exposure to lung function decline: Results from a longitudinal study - Wei-Chi Wang; Yuan-Ting C. Lo; Hsiu-Ying Ku; Hsu-Kai Huang; You-Zhen Chen; Wei-Yu Lin; Han-Bin Huang (Environmental Pollution, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

A tetrahedral framework DNA-metformin nano-firefighter for quenching adipose chronic inflammation: Reprogramming macrophages to restore metabolic homeostasis in obesity - Zhuo Chen; Jiaqi Li; Alimire Alifu; Fenglin Jiang; Wenjing Tang; Zaowei Yang; Yuhao Liu; Bo Tian; Xi Chen; Yu Chen; Qi Han; Yunfeng Lin (Chemical Engineering Journal, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Regulating cation disorder to stabilize oxygen redox in Li-rich DRX cathodes via Fe substitution - Chia-Ching Lin; Péter Udvarhelyi; Hao-Hsiang Chang; Tsung-Yi Chen; Zhenfei Cai; Yu Zhao; Han-Yi Chen; Denis Y.W. Yu (Chemical Engineering Journal, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Enhanced phenanthrene degradation in microalgae-bacteria systems: Mechanistic roles of exogenous and indigenous degraders - Mengying Wang; Han Wang; Xuetao Liang; Jingran Li; Chen Wang; Longyan Cui; Shuo Yang; Jiaxuan Lin; Qi Yang; Zhilin Yang (Bioresource Technology, 2026)

Integrative study of acute ammonia exposure on the skin of the Striped catfish (Pangasianodon hypophthalmus) - Wei-Hsuan Hsiao; Shun-Yi Lin; Ying-Hsien Wu; Han-Chen Ho; Tsunglin Liu; Liang-Chun Wang (Aquatic Toxicology, 2026)

Exposure to a porcine appeasing pheromone in periparturient sows: Effects on behavior, health status, and reproductive performance - Shuang Liu; Liang Wang; Xu-Kai Nie; Chun-Yu Song; Ying-Han Chen; Lin Wang; Cai-Yu Lian (Applied Animal Behaviour Science, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Waste mop cloth recycling enables rapid, high-throughput removal of viscous winter oil spills - Min Zhang; Ching-Wen Lou; Kaifang Xie; Hengshu Zhou; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Journal of Hazardous Materials, 2026)

The plum rain season enhances indoor airborne resistome and potential pathogen exposure - Changyi Lu; Yifang Zhang; Chenshuo Lin; Hu Li; Ruixia Han; Qing-Lin Chen (Journal of Hazardous Materials, 2026)

Optimized design of ozone microbubble aeration reactor to enhance the removal of dissolved organic matter: A pilot-scale study on drinking water treatment - Jinmin Su; Tao Lin; Han Chen; Wei Liu; Yuchen Wang; Yimu Qiao (Journal of Environmental Management, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Integrative transcriptomic and functional analysis reveals fatty acyl elongases involved in sex pheromone biosynthesis in rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyraloidea) - Ling-Yue Chen; Xiao-Yang Lin; Ke-Xin Wang; Xiao Feng; Hong-Ting Tang; Shuang-Lin Dong; Ling-Ling Zheng; Yi-Han Xia (Insect Biochemistry and Molecular Biology, 2026)

Selective partitioning of plant proteins during emulsification impairs foam stability: conformational changes of aqueous-phase residues relative to animal proteins - Yiqiu Deng; Wanjun Han; Yiting Lin; Xiuhang Chai; Fengxiang Chen; Yuanfa Liu (Food Hydrocolloids, 2026)

Prenatal exposure to residential greenness and artificial light at night and neurodevelopmental outcomes in children aged 4–12 years: A retrospective cohort study in China - Jian Chen; Daosen Wang; Jiaxuan Fu; Ranran Gong; Qifei Chen; Jie Tang; Ziyu Feng; Han Li; Xinyun Lin; Xiuhong Li (Environmental Research, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Behaviour of concrete-encased CFST hybrid member subjected to long-term bending moments - Chen-Yu Zhang; Guan-Yuan Zhao; Lin-Hai Han; Zhi-Cheng Yang (Engineering Structures, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

An intelligent nanosystem for disrupting the neuro-immune-oncology axis to unleash anti-tumor “immune storm” - Yuanhang Han; Yunxiang Ding; Yuyang Wang; Zhiqiang Yang; Xiaoxiao Liang; Xin Wang; Yushen Lu; Ruimin Wang; Zhenyi Chen; Yifan Hu; Lin Cai; Jianbin Xu; et al. (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Multi-omics Analysis Reveals the Protection of a Quadruple Probiotic Mixture in Experimental Autoimmune Hepatitis - Yu Chen; Shuhui Wang; Anzhuo Chen; Zhuoying Lin; Han Wang; Wanneng Li; Jun Liu; Jia Yao; Dean Tian; Yu Lei; Mei Liu (Probiotics and Antimicrobial Proteins, 2026)

Folding integrated all-paper photoelectrochemical immunoassay using annealed ZnO for point-of-care detection of ferritin - Yibin Cai; Haining Li; Yanping Chen; Shuyi Lu; Huanhuan Zhu; Dianping Tang; Xiao Han; Shaofeng Lin (Analytica Chimica Acta, 2026)

Characterization of a novel Era-homolog (AtERG1) in Arabidopsis that is essential for chloroplast development - Yi Lin; Shuangyuan Jia; Chenchen Zhang; Shanshan Chen; Han Xiang; Jiaqi Chen; Ying Yang; Jiawei Chen; Ming Li; Jinwen Liu (Journal of Plant Biochemistry and Biotechnology, 2026)

Mobilized-clay-driven toppling: A new mechanism resolving the “energy paradox” of under-dip slope failure in flysch terrains - Thanh-Tùng Nguyễn; Ivo Baroň; Filip Hartvich; Jiří Havlík; Lenka Kociánová; Jan Klimeš; Jan Černý; Martin Šutjak; Václav Dušek; Cheng-Han Lin; Chia-Han Tseng; Yi-Chin Chen; et al. (Landslides, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Warming Rate Shapes Metabolic Depression in the Mudflat Gastropod Batillaria attramentaria: Transcriptional and Alternative Splicing Regulations - Guodong Han; Shan Lin; Yaru Chen; Lina Du (Journal of Ocean University of China, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Taixinan contourite and mixed systems on the Gaoping Slope: Influence of intermediate water masses on the Taixinan canyon group - Zhi Lin Ng; Shan Liu; Kunwen Luo; Xinyu Xue; Zhixuan Lin; Tzu-Ting Chen; Ho-Han Hsu; Ming Su (Quaternary Science Reviews, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Numerical investigation with viscosity of nonlinear wave forces on a dual-tube submerged floating tunnel - Hong-fei Mao; Kai-lin Chen; Long Han; Zhong-bing Zhou; Yan-li He; Li-min Wang; Jing Xie (Ocean Engineering, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Low-moisture extrusion exerts distinct effects on the dynamic digestion kinetics of proteins in plant-based meat analogues - Zi Chen; Aiqian Ye; Tiantian Sun; Yiming Zhao; Weilin Liu; Jianzhong Han; Quanquan Lin (Food Research International, 2026)

Exploring the endogenous and exogenous key aroma-active components in three aroma types of black teas from different cultivars - Weixuan Li; Zhouling Zhong; Han Yan; Longyu Guo; Ge Chen; Zhi Lin; Haipeng Lv; Yue Zhang; Yin Zhu (Food Research International, 2026)

Postharvest properties and metabolomic profiling of cucumbers treated with hydrogen sulfide under low-temperature storage - Wei Han Foo; Mingmin Chen; Xue Zhao; Yu Xuan Lim; Lin Chen (Food Chemistry, 2026)

Discovery, molecular docking, and umami-enhancing synergy of five novel umami peptides from Dictyophora rubrovolvata: Insights into T1R1/T1R3 interaction - Jialin Li; Jiaqi Chen; Zhenan Rao; Han Xie; Jichun Zhao; Lin Lei; Kaifang Zeng; Jian Ming (Food Chemistry, 2026)

MRI-guided nano-prodrug with self-detoxifying bioclearance for precision detection and therapy of cancer metastases - Wenyi Zhang; Dengyi Duan; Jing Peng; Lin Chen; Kangkang Liu; Yiming Li; Jianmin Li; Gang Han; Yang Zhao (Chemical Engineering Journal, 2026)

Denitrogenation of aqueous organic nitrogen by vacuum ultraviolet in tandem with chlorine - Baiyang Chen; Hao-Lin Yang; Longjie Cheng; Yuheng Chen; Xiao Li; Qiaoxia Han (Chemical Engineering Journal, 2026)

A subcellular spatial profiling platform for expanding the drug toxicity window - Liu Yang; Qingjie Bai; Shuyuan Guo; Luyao Hu; Chenghao Bi; Litao Shao; Zihao Lin; Kairui Cui; Shenshen Yang; Jinxia Wei; Liwei Shao; Liwen Han; et al. (Chemical Engineering Journal, 2026)

Differences between human and rat 5α-Reductase 1 inhibition by phenolic disinfectants: Comparative kinetics and binding modes for neurosteroid synthesis - Xinyu Han; Wanyu Li; Yinghao Huang; Lisha Wang; Tianchi Zhao; Xishi Chen; Hao Lin; Yiyan Wang; Ren-shan Ge; Jianfeng Ma (Chemico-Biological Interactions, 2026)

Alnustone ameliorates obesity and polycystic ovary syndrome by remodeling adipose metabolism via AMPK signaling - Yiming Qin; Shourui Hu; Yanqi Xu; Zongxuan Lin; Xiaofan Liang; Yue Liu; Yuxuan Li; Chunxuan Geng; Xiangyan Chen; Xizi Feng; Zi-Jiang Chen; Han Zhao; et al. (Science China Life Sciences, 2026)

Sexually dimorphic expression and hormonal responsiveness of steroidogenic Cyp genes during gonadal differentiation in mandarin fish - Jieming Zhang; Shengyue Lin; Ziyan Deng; Weijian Chen; Guojun Cai; Min Zhang; Lilin Zhan; Chong Han; Jian Gong; Qiang Li (Fish Physiology and Biochemistry, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Permafrost slope failure and mitigation techniques in cold regions - Guo Ming; Yu Wenbing; Li Guo; Chen Lin; Han Fenglei (Bulletin of Engineering Geology and the Environment, 2026)

FAL1 facilitates cisplatin resistance of lung adenocarcinoma via BMI1/BIM-mediated apoptosis–autophagy interaction - Teng Ma; Yang Xia; Yijiang Chen; Han Lin; Chunfeng Pan (Molecular and Cellular Biochemistry, 2026)

Effects of volcanic altitudes on the rhizosphere microbial community composition and structure of Euphorbia maculata - Yaozhou Zhang; Han Lin; Qixiu Cheng; Haining Wang; Yiming Zhang; Yueming Bao; Rui Qin; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2026)

Numerical examination of hydrodynamic forces on a submerged forced rotating circular cylinder under wave action - Hong-Fei Mao; Long Han; Kai-Lin Chen; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Hui Yang; Dong-Bin He; Li-Min Wang (Ocean Engineering, 2026)

Field validation of a multi-functional dry habitat for subsea pipeline maintenance - Jin Guo; Jiawang Chen; Bo Han; Haiyang You; Yuan Lin; Deqing Mei (Ocean Engineering, 2026)

Is BPA only the tip of the iceberg? Occurrence and risk assessment of 32 bisphenol analogues in landfill leachate - Zhi-Zhong Zhang; Lin-Hui Zhang; Hang Li; Fei Chen; Sakhayana Nikolaevna Danilova; Ming-Han Li; Bing-Feng Liu; Yi-Fan Li; Zi-Feng Zhang (Journal of Hazardous Materials, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Impacts of continuous ultra-low temperature freezing on the evolution of pore throat characteristics and coalbed methane production in bituminous coal - Lei Qin; Siheng Lin; Niandong Chen; Feilong Zhang; Zengning Huang; Han Wang; Shiyin Lv; Miao Mu (Journal of Applied Geophysics, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Graphitization-driven interfacial polarization and conductivity in core–shell Fe3O4@hydrochar composites achieving high-performance electromagnetic wave absorption - Lin Wang; Yingshan Deng; Zurong Zhu; Dan Michelle Wang; Dafu Chen; Guanghui Bai; Zhongyi Feng; Yao Han; Yueyao Liu; Jinxia Zhai; Chengyun Ning; Zhengao Wang (Chemical Engineering Journal, 2026)

A low-power and visualized varicose vein ablation surgery based on interventional optical fiber therapeutic probe - Fangzhou Jin; Yinsheng Lin; Yading Luo; Jian Han; Xu Yue; Wenwei Chen; Yongkang Zhang; Shanshan Guo; Xiaobing Niu; Jun Guo; Bai-Ou Guan; Chengzhi Li; et al. (Chemical Engineering Journal, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

In-situ heterojunction on high-aspect-ratio cellulose nanocrystals for long-range charge transport in e-skin - Chenchen Shen; Weiwei Chen; Lin Guo; Yanrui Zou; Shuan Han; Ning Yu; Lin Gan; Jin Huang (Carbohydrate Polymers, 2026)

Identification of WRKY transcription factors (TFs) in the recretohalophyte Tamarix chinensis and functional analysis of TcWRKY13 under salt stress - Xingxing Xu; Nan Yin; Chunhao Jiang; Lin Guan; Yutong Chen; Shuai Han; Qianqian Jin; Yanhong Shen; Qingzhang Du; Guojun Zhang (Plant Cell Reports, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

High-resolution temporal biogeochemical variations in a seagrass-coral cohabitate ecosystem: day-night, rain, and coral spawning - Huei-Ting Lin; Yu-Chen Yen; Chih-Chiang Hsieh; Hirofumi Watanabe; Yiing-Jang Yang; Hui-Yu Wang; Han Song Ong; Shi-Ming Chen; Pei-Ling Wang (Science of The Total Environment, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Building tailorable Kagome lattices with quantum-confined orbitals in periodic mirror twin boundaries - Ruo-Han Zhang; Jiang-Hui Pan; Ya-Xin Zhao; Chen-Yue Hao; Ke Lv; Mo-Han Zhang; Xiao-Ya Wang; Ya-Ning Ren; Ji Feng; Lin He (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Use of AI-mediated image analysis to investigate the influence of environmental factors and recreational scuba diving on fish activity patterns in a marine protected area - Ching-Han Chang; Dong-Lin Li; Li-Shu Chen; Yi-Ta Shao (Regional Studies in Marine Science, 2026)

Experimental investigation of nonlinear hydrodynamic properties of the T-foil on a high-speed trimaran - Shijie Liu; Lincen Han; Hongyu Lin; Shaoqing Liu; Xi Chen; Yichen Jiang (Ocean Engineering, 2026)

Differential deformation characteristics and evolution of ultra-deep strike-slip faults in the Tarim craton, China - Yingtao Yao; Jun Han; Lianbo Zeng; Cheng Huang; Bo Lin; Zhangxing Chen; Zhe Mao; Dongsheng Cao (Journal of Structural Geology, 2026)

Effects of inoculum sources from different depths and oxygen concentration on bioleaching and microbial community assembly in mine waste dump - Zi Han Lin; Bing Zhou; Chen Sheng Zhang; Xuan Qi Zhang; Yan Bo Chen; Min Liang Fei; Xiao Fei Wei; Zhang Zheng Cai; Tian Shou Hu; Jie Hu; Han Ke (Journal of Hazardous Materials, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Overlooked spectral matching-Enabled sulfoxide wastewater valorization and in situ pollutant elimination - Lingzhi Shen; Yue Yang; Yixun Zheng; Mengyang Niu; Zhiqing Lin; Zihong Xu; Yongpeng Zhang; Shan Yao; Yanli Wang; Kun Zhao; Zhenjun Xiao; Zili Lin; et al. (Journal of Cleaner Production, 2026)

Machine-learning-guided extraction optimization and physicochemical characteristic of GRAS microalgae proteins for sustainable food applications - Wei Han Foo; Mingmin Chen; Yu Xuan Lim; Lin Chen (Food Hydrocolloids, 2026)

PFAS and adipokines: Decoding their roles in the risk of breast nodules and breast cancer - Mengya Xu; Xinyu Zhu; Yangyang Liu; Xuezhen Liu; Wanlu Liu; Baihao Lin; Yuyu Zheng; Kang Liu; Yue Feng; Nada Alhazmi; Shengtao Ma; Hao Chen; et al. (Environmental Research, 2026)

Biodegradable mulch film-enriched with biochar, chicken feather, and oyster shell powder for improved soil quality and crop productivity - Kesinee Iamsaard; Girma Sisay Wolde; Chih-Huang Weng; Ying-Chen Chen; Han-Yu Hsueh; Jenn-Wen Huang; Yao-Tung Lin (Environmental Research, 2026)

Formation and evolution of sandy deserts in China: A review - Xin Wang; Ziying Yu; Han Hu; Chongwen Luo; Wenjing Yang; Jiayi Lin; Yu Cao; Zaijun Li; Fei Wang; Baofeng Li; Shengqian Chen; Huayu Lu; et al. (Earth-Science Reviews, 2026)

Nb5+ pre-intercalation synergistically regulates layered vanadates for high-performance aqueous Zn-ion batteries - Shenglin Zhong; Denglian Chen; Xiang Hu; Han Lin; Menghui Mu; Zhenhai Wen; Jiangcong Zhou (Chemical Engineering Journal, 2026)

Dual effects of montmorillonite on CO2 hydrate formation kinetics in saline sand–clay systems: Experimental study and growth modeling - Xiran Lin; Ying Teng; Ying Liu; Mingkun Bai; Yiqi Chen; Pengfei Wang; Liangbin Xu; Jinlong Zhu; Songbai Han; Huiru Sun; Senyou An; Jianbo Zhu (Chemical Engineering Journal, 2026)

Octopus-inspired photonic-electronic synergistic hydrogel tactile sensor for accurate and reliable health monitoring - Boqing Jia; Changxu Zhang; Yihe Zhao; Lan Yu; Yibo Lv; Gengyu Han; Xinyu Shi; Zhuorui Chen; Xuanting Lu; Jiaxiang Wang; Min Li; Guoxi Luo; et al. (Chemical Engineering Journal, 2026)

Diversity of arbuscular mycorrhizal fungi of Taiwan cypress along altitude in tropical forests - Wan-Rou Lin; Hsuan-Min Cheng; Ren-Cheng Liu; Tzu-Chao Lin; Lei-Chen Lin; Pi-Han Wang (Tropical Ecology, 2026)

Two Novel Peniphenone Derivatives with Distinct Stereoconfigurations from Ascidian-Derived Fungus Diaporthe sp. SYSU-MS4722 and Their Anti-Fibrotic Activities - Shuya Ren; Yanhong Han; Yan Yan; Yuran Zhou; Siwen Yuan; Junjie Chen; Heng Guo; Zhenjian Lin; Qifeng Lin; Senhua Chen; Lan Liu; Yongkang Qiao; et al. (Journal of Ocean University of China, 2026)

The aging eye: navigating molecular mechanisms and innovative interventions - Yumeng Lin; Zhongyu Han; Yunfeng Zhang; Ruimin Yuan; Mingyu Huang; Yating Liu; Jun Wang; Chen Xu; Luze Liu; Ping Yu; Qingsong Yang; Liuzhi Zeng; et al. (Biogerontology, 2026)

Neutrophil extracellular traps in post-traumatic urethral microenvironment promote hypertrophic urethral stricture via the TLR9/NF-kB/Smad3/IL-8 axis - Ye-Hui Chen; Zhi-Bin Ke; Bo-Han Lin; Yi-Cheng Xu; Xue-Yi Xue; Qing-Shui Zheng; Xiong-Lin Sun; Yong Wei; Ying-Chun Liang; Ning Xu (Apoptosis, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Reinforced stepwise dissociation of water molecules via U 5f-O 2p-Ti 3d gradient orbital coupling for photoelectrochemical water splitting - Xiaochuan Deng; Tong Liu; Xudong Wu; Qijue Lin; Hanlin Liu; Han Yang; Xun Yang; Maoyin Wang; Kaiguo Chen; Jiayu Dai; Tao Chen; Wenkun Zhu (Science Bulletin, 2026)

Research on multi condition electric load forecasting of tugboat based on graph structure temporal parallel fusion framework - Wenjie Liu; Zhen Su; Kunhuang Han; Lin Chen; Xiaoyan Li (Ocean Engineering, 2026)

Corrigendum to “Early Cretaceous radiolarians and siliceous rock geochemistry from Kangmar, Southern Xizang: Biostratigraphic, paleoenvironmental, and paleogeographic implications for the Neo-Tethys Ocean” [Marine Micropaleontology 201 (2025) 102523] - Han Yan; Hanting Zhong; Chenyu Wang; Zongqi Lin; Cai Wang; Xiachao Huang; Chao Chen; Mingcai Hou (Marine Micropaleontology, 2026)

Efficient medium-chain alkane degradation by two isolated bacterial strains: performance and synergistic mechanisms - Yaxue He; Rui Han; Hui Wang; Aohan Zhang; Piet N.L.Lens; Christian Kennes; Xiaoyan Li; Qian Li; Lichao Lu; Lei Wang; Jianmeng Chen; Rongsheng Lin; et al. (Environmental Research, 2026)

Exploration of salivary biomarkers for accurate diagnosis of anxiety, depression, and somatic symptom disorder by the integration of microfluidic chip and machine learning - Rongjie Wang; Fei Xu; Lin Wang; Xue Zhang; Miao Huang; Zhun Wei; Yan Jiang; Yunhong Zhang; Xiaoshuang Chen; Yanbo Liang; Yu Zhang; Xueqin Mao; et al. (Chemical Engineering Journal, 2026)

Effects of biochar and NPK fertilization on growth, root traits, and physiological performance of Casuarina equisetifolia seedlings - Bin Xie; Lin Zhao; Qiping Qiu; Han Lin; Can Chen; Anqiang Xie; Chuanyang Jiang; Zichuan Chen (Journal of Soils and Sediments, 2026)

Pencil-drawn paper-based portable photoelectrochemical immunoassay of carbohydrate antigen 19-9 based on TiO2 hollow cube homogeneous junctions - Qinyan Chen; Qiong Lin; Yibin Zeng; Haining Li; Xiao Han; Dianping Tang; Gaoda Ju (Analytica Chimica Acta, 2026)

Characterization, expression and evolution analysis of NLRC3 , NLRC5 and NLRX1 in Mastacembelus armatus under Aeromonas veronii infection - Shengyue Lin; Kaifeng Wang; Weijian Chen; Ziyan Deng; Guojun Cai; Min Zhang; Zihang Xie; Weibin Li; Chong Han; Qiang Li (Journal of Fish Biology, 2026)
NOD‐like receptors (NLRs) serve as crucial innate immune sensors in multicellular organisms, recognizing diverse pathogen‐associated components and regulating immune responses such as nuclear factor kappa B (NF‐κB) signalling and inflammatory pathways. To elucidate the roles of NLRC3 , NLRC5 and NLRX1 in the innate immunity of the Mastacembelus armatus , this study first characterized these genes and examined their response to Aeromonas veronii infection. We identified the three NLR genes from the M. armatus transcriptome and analysed their evolutionary relationships through domain architecture and maximum likelihood (ML) phylogenetic reconstruction. All three NLR proteins contained conserved NACHT and leucine‐rich repeat (LRR) domains, and ML phylogenetic analysis grouped M. armatus with other Synbranchiformes and Perciformes, consistent with established taxonomy. Tissue expression profiling in healthy fish revealed constitutive expression of all three genes across nine examined tissues, with significantly higher levels in gills, suggesting their involvement in frontline mucosal immunity. Temporal expression analysis in spleen, liver and kidney following A. veronii challenge showed distinct organ‐specific patterns: although all three genes were downregulated in the liver, they were significantly upregulated in spleen and kidney, indicating these as primary sites for NLR‐mediated immune responses in M. armatus . Selection pressure analysis using CodeML identified widespread purifying selection across teleost NLRs, alongside multiple positively selected sites in NLRC5 (7 sites in site model, 5 in branch‐site model) and NLRX1 (2 sites in site model, 22 in branch‐site model). These findings provide fundamental insights into NLR‐mediated immunity in M. armatus and contribute to understanding the evolution and function of NLR genes in teleosts.

Machine Learning Approaches for Probabilistic Prediction of Coastal Freak Waves - Dong-Jiing Doong; Wei-Cheng Chen; Fan-Ju Lin; Chi Pan; Cheng-Han Tsai (Journal of Marine Science and Engineering, 2026)
Coastal freak waves (CFWs) are sudden and hazardous wave events that occur near shorelines and can pose serious threats to coastal visitors and infrastructure. Due to the complex interactions among coastal bathymetry, wave dynamics, and environmental conditions, the mechanisms governing CFW formation remain poorly understood, making reliable prediction difficult. This study investigates the feasibility of applying machine learning techniques to predict CFW occurrences using observational environmental data. Three machine learning algorithms, the Random Forest (RF), Support Vector Machine (SVM), and Artificial Neural Network (ANN), were developed to generate probability-based predictions of CFW events. Environmental variables derived from buoy observations, including wave characteristics, wind conditions, swell parameters, wave grouping indicators, and nonlinear wave interaction indices, were used as model inputs. Hyperparameters were optimized using grid search combined with k-fold cross-validation. The results show that all three models achieved comparable predictive performance, with AUC values close to 0.80 and overall prediction accuracy around 74%. The ANN model achieved the highest recall, indicating strong capability in detecting CFW events, while the RF and SVM models showed more balanced precision and recall. Analysis of high-probability prediction events suggests that CFW occurrences are associated with swell-dominated conditions, strong wave grouping behavior, and enhanced nonlinear wave interactions. These results demonstrate that machine learning provides a promising framework for probabilistic prediction of coastal freak waves and has potential applications in coastal hazard assessment and early warning systems.

A Moon image point spread function deconvolution framework for satellite Earth observation image restoration - Han Lin; Ya Su; Binglong Chen; Qunyong Wu; Zhiqing Zhang (International Journal of Remote Sensing, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Chronology and geochemistry of radiolarian chert from Zhongba, southern Xizang (Tibet): Implications for the evolution of the Neo-Tethys Ocean - Han Yan; Han-Ting Zhong; Zong-Qi Lin; Chen-Yu Wang; Ling-Xue Gao; Cai Wang; Ming-Cai Hou (Palaeoworld, 2026)

Root traits determine the effects of organic amendments on soil aggregate organic carbon by regulating soil microbial multitrophic networks - Changdong HAN; Lin CHEN; Zhongjun JIA; Hongtao ZOU; Ling MA; Jingwang LI; Congzhi ZHANG; Guixiang ZHOU; Donghao MA; Jiabao ZHANG (Pedosphere, 2026)

A multiple-interdependency risk assessment model with time-varying reasoning capabilities for long-distance water diversion projects - Zihan Chen; Boran Zhu; Shilei Zhang; Ruihua Han; Jin Bai; Junqiang Lin; Youzhi Liu; Bo Wang (Journal of Hydrology, 2026)

A cellulosic waste-upcycled 1T/2H-MoS2/biochar heterostructure for efficient cationic dye adsorption via a multi-anchor chemisorption mechanism - Yifan Lu; Min He; Mingna Ge; Luning Chen; Lin Han; Cong Tu; Bang Yuan; Jie Huang (Journal of Environmental Chemical Engineering, 2026)

Statistical optimization of biochar production via high-temperature carbonization through Taguchi and principal component analysis approaches - Jamin Jamir Escalante; Wei-Hsin Chen; Chien-Yuan Su; Po-Han Li; Kun-Yi Andrew Lin; Kanit Manatura (Fuel, 2026)

Fermented red quinoa (FRQ) effectively mitigates chronic alcohol-induced cognitive impairment and hepatic steatosis through multi-mechanistic pathways - Zi-Han Lin; Zhaohui Wang; FenFen Wei; Xinyao Zhu; Junwei Ma; Yan Wu; Song-Mei Chen; Li-Hua Song (Food Research International, 2026)

From digestion to delivery: the gastrointestinal fate and functional duality of goat milk-derived extracellular vesicles - Chunping Chen; Cong Zheng; Fangcheng Hu; Yue Li; Xingyuan Liu; Wenxu Zhou; Baolong Liu; Lin Han; Caian He; Min Wang (Food Chemistry, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

Integrated Analysis of mRNA-seq and miRNA-seq Reveal the Dynamics of the Gonadal Differentiation of Procypris Mera - Zhenling Ke; Weijun Wu; Zhe Li; Yusen Li; Yaoquan Han; Jun Shi; Lilong Chen; Kangqi Zhou; Dapeng Wang; Yong Lin; Min Li; Hua Ye (Marine Biotechnology, 2026)

Global-to-regional variations in the effects of grassland management on soil carbon - Xi Lin; Shengwei Zhang; Alfredo Huete; Han Y.H. Chen; Hongbin Zhao; Qinsi He; Shengwei Lv; Qian Zhang; Xiaoduo Zhang; Xiaofeng Zhang (Agriculture, Ecosystems & Environment, 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Gene Regulatory Networks Controlling Fruit Anthocyanin Accumulation: A Review - Da Zhang; Bowei Zhu; Xin Liu; Han Wang; Guodong Zhao; Lin’guang Jia; Dongmei Chen; Tongsheng Zhao; Gang Niu; Chaohong Zhang; Xinsheng Zhang (Applied Fruit Science, 2026)

Operational Performance of Aquavoltaics Under Different Stakeholder Cooperation Schemes: Evidence from White Shrimp Aquaculture in Taiwan - Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou; Farok Afero; Szu-Han Liu; Cheng-Ting Huang (Fishes, 2026)
Aquaculture faces rising climate-change risks, while photovoltaic power generation requires substantial land resources, underscoring the need for multifunctional land use in the energy transition. Aquavoltaics—combining aquaculture with solar power—has emerged, and its success depends on stakeholder cooperation. Using white shrimp aquaculture in Taiwan as a case study, this study examines four cooperation schemes—a sole-investment scheme, a photovoltaic-led leasing scheme, a landowner lease-back scheme, and a separated aquaculture and photovoltaic operation scheme—across six aquavoltaic types. Cost–benefit and data envelopment analyses assess the economic returns and operational efficiency of aquaculture operators and photovoltaic companies under each scheme. The results show that all schemes offer profit potential but differ in efficiency and income distribution. The landowner lease-back scheme is most efficient for aquaculture operators, while photovoltaic companies operate near the efficiency frontier in all schemes. The findings highlight that cooperation design shapes the economic feasibility, efficiency, and livelihood impact of aquavoltaic systems, providing a useful reference for future policy and model design.

TLR5-mediated pathogenic bacteria defense and functional maintenance of Misgurnus anguillicaudatus ovary - Yali Wang; Mengzhen Wang; Yanxia Lin; Yunfan Han; Enping Chen; Xiaohua Xia (Aquaculture, 2026)

Highly effective masculinization of mandarin fish (Siniperca chuatsi) using Etonogestrel: A practical method for aquaculture and transcriptomic mechanism elucidation - Jiangwei Zhou; Simin Zhong; Shengyue Lin; Shuzheng Ye; Dingxian Chen; Chong Han; Qiang Li (Aquaculture, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

SiGSTU18 positively regulates saline-alkali tolerance in foxtail millet through glutathione metabolism and glutamic acid-mediated alleviation of oxidative stress and ion toxicity - Yun Li; Yuxue Zhao; Fuxing Xiang; Fangying Chen; Yanrui Xu; Xiaohu Lin; Jihan Cui; Yucui Han (Plant Science, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Biomimetic carboxymethyl β-glucan-ZIF-8 nanocarrier enhances structural stability, gastrointestinal release, and antioxidant efficacy of urolithin A via dectin-1-engaged mitophagy - Fangcheng Hu; Xingyuan Liu; Chunping Chen; Yushan Liu; Xiaotong Xu; Lin Han; Caian He; Min Wang (Food Research International, 2026)

Blue food proteins-derived immunomodulatory peptides: sources, preparation, identification techniques, mechanisms, and critical challenges of commercial application - Yu-Han Wu; Yan Chen; Ke-Lin Zhang; Fang-Miao Yu; Bin Wang; Qi Zeng (Food Research International, 2026)

Unraveling the aromatic essence of baked green tea using sensomics: insights from three representative cultivars - Yan Zhao; Chen-Yang Shao; Han Yan; Yue Zhang; Qun-Hua Peng; Zhi Lin; Xiao-Ting Zhai; Hai-Peng Lv; Yin Zhu (Food Chemistry, 2026)

Highland barley arabinoxylans with distinct molecular features modulate retrogradation and in vitro digestibility of highland barley starch - Yonghui Dong; Tingting Mu; Xue Wu; Chunping Chen; Haiyu Wu; Lin Han; Caian He; Min Wang (Food Hydrocolloids, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Hetero-folded hBN/graphene with ultrahigh thermal conduction and electrical insulation for reliable thermal management - Han Zhao; Pengyu Zhang; Jingran Guo; Dizhou Liu; Shixuan Dang; Duola Wang; Hongxuan Yu; Jiali Chen; Chuanyun Song; Yuanpeng Deng; Yingde Zhao; Cong Li; et al. (Chemical Engineering Journal, 2026)

Dual-halide solid electrolyte interphase engineering with MXene enables dense (110)-oriented Li deposition for high-performance Li metal anodes - Zongyu Mao; Shuaihe Zhang; Ye Han; Yujing Xu; Shuxin Xie; Bei Huang; Shuaihong Chen; Xintong Cai; Junyu Lin; Xiao Yu; Shaozhong Zeng; Dongju Fu; et al. (Chemical Engineering Journal, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Hydroxyl-functionalized electrolyte additives for stable low-temperature zinc-ion battery operation - Zhenzhen Kong; Xiyan Wei; Yongbiao Mu; Jinpeng Guan; Zetao Chen; Lin Yang; Liying Wang; Meisheng Han; Lin Zeng (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Biochar-NPK interactions improve soil nutrients and enzyme activity in Casuarina equisetifolia - Qiping Qiu; Bin Xie; Lin Zhao; Han Lin; Anqiang Xie; Dongyang Wu; Can Chen (Journal of Soils and Sediments, 2026)

Impacts of structurally distinct starches on growth, short-chain fatty acid production, hepatic lipid metabolic homeostasis, and inflammatory response in largemouth bass (Micropterus salmoides) - Han Huang; Xin Liu; Hao Sun; Yang Xiao; Yuanfa He; Yongjun Chen; Shimei Lin (Animal Feed Science and Technology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Cell size as a biomarker for proliferation in Noctiluca scintillans: Insights from controlled experiments - Nanjing Ji; Qiuping Li; Xiaotong Cheng; Yifan Chen; Honglin Chen; Yinghao Wang; Bin Han; Gewei Chen; Xin Shen; Senjie Lin (Marine Pollution Bulletin, 2026)

Mechanisms of cell death in Klebsiella pneumoniae-induced acute splenic injury in Aquarana catesbeiana - Han Lin; Hua Li; Kesong Chen; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Systematic assessment and improvement for the intelligent municipal solid waste sorter - Wei-Lung Mao; Shu-Han Huang; Hsu-Cheng Chen; Jun-Wei Zeng; Yu-Hao Lin (Journal of Cleaner Production, 2026)

A novel mainstream application of aerobic granular sludge for nitrite supply to Anammox: insights from granule size and microbial stratification - Zongshuo Han; Xiaoying Zheng; Wenfei Li; Haidong He; Yi Fan; Tao Lin; Wei Chen (Journal of Cleaner Production, 2026)

High performance CeO2/Mn2O3-Mn5O8 catalysts from Mn-MIL-100 for benzene catalytic oxidation - Hongxiang Chen; Biliang Lin; Guiping Jiao; Wenying Wei; Ning Zhao; Yanwei Han; Weiyan Zhu; Yifan Zhang; Yong Wang (Journal of Environmental Chemical Engineering, 2026)

Dose-dependent root phenotypic plasticity in Casuarina equisetifolia: Mechanistic insights into drought adaptation strategies for coastal sand-fixation afforestation - Chen Fang; Qinqin Lin; Can Chen; Yu Chen; Han Lin; Guoying Pan; Chuanyang Jiang; Anqiang Xie; Xia Li (Journal of Arid Environments, 2026)

An accelerated meshfree computational framework with machine learning classification for multi-phase modeling of landslide - Kuan-Chung Lin; Yih-Chin Tai; Po-Han Lee; Hock-Kiet Wong; Yanran Wang; Yu-Shu Lu; Jiun-Shyan Chen (Computers and Geotechnics, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Highly linear bionic strain decoupling sensor mediated by curved surface stress - Xueping Zhang; Junqiu Zhang; Jiachao Wu; Yu Chen; Xueyang Li; Wenjie Yu; Xiancun Meng; Guilin Li; Lina Ju; Bo Li; Tao Sun; Zhiwu Han; et al. (Chemical Engineering Journal, 2026)

Versatile fully polymeric conductive organohydrogel as an all-in-one wearable response platform for bioelectronics - Kelei Shi; Huiping Chen; Jianwei Li; Yupan Han; Hongling Sun; Hu Liu; Lin Dong; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2026)

Electric field superposition for efficient implantable ultrasound energy harvesting - Aokai Yang; Chaoran Tan; Yuyang Lin; Haoying Han; Renfei Wei; Yan Wang; Kang Chen; Shizhe Lin; Liang Huang; Jun Zhou (Chemical Engineering Journal, 2026)

A microenvironment-responsive chitosan based injectable hydrogel with synergistic anti-inflammatory effects of triptolide and copper ions for spinal cord injury repair - Han-Jian Hu; Zhenming Tian; Zeng-Lin Li; Chun Cheung Chan; Hongyan Zhang; Shipeng Tang; Yu Chen; Zhaoyin Chen; Tian Hu; Bin Liu; Gang-Biao Jiang (Carbohydrate Polymers, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Experimental investigation and characterization of the vibration fatigue S-N curve for small-diameter 316L stainless steel butt-welded pipes - Ning Li; Hongbo Gao; Lei Lin; Pin Li; Shuai Zhou; Han Liu; Changning Li; Decheng Xu; Yin Liu; Zhilin Chen (Annals of Nuclear Energy, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Implementation of a Deep Learning Ensemble Framework Based on Bidirectional Message Queues - Xin-Jian Wei; Wu-Yang Yang; Xin Xu; Hai-Shan Li; Nan Wang; Wei-Sheng Wang; Han-Wei Lin; Chen Wang (Applied Geophysics, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Two novel TRAF homologs are implicated in the immunological response and interact with IRAK in the Zhikong scallop (Chlamys farreri) - Jiwen Chen; Wei Chen; Yifan Qu; Xiaoxue Lin; Haikun Zhang; Jilv Ma; Jie Cui; Fengchen Liu; Zhongyi Chu; Yue Zhao; Yabin Wang; Yaqiong Liu; et al. (Aquaculture, 2026)

Mechanistic insights into the transformation and toxicity evolution of IPPD-Q during chlorination and chloramination in drinking water - Han Chen; Tao Lin; Junding Yin; Siqiao Chen; Zhongkai Wang; Yuchen Wang (Water Research, 2026)

Attached microalgae-simulated plants enhanced multiple-pollutant removal in a tidal flow constructed wetland: quantified efficiencies, pathways, and biological mechanisms - Shu-Han Ge; Mei-Zi Yang; Wei-Yi Qian; Lin-Lan Zhuang; Hai-Ming Wu; Zhuo Chen; Xiao-Xiong Wang; Jian Zhang (Water Research, 2026)

How do electric vehicles impact community resilience? A bi-Layer network perspective - Cancan Zhang; Han Lin; Haiyan Hao; Yudi Chen (Transportation Research Part D: Transport and Environment, 2026)

Arching patterns in compacted clay: insights from plane-strain trapdoor tests - Xiang-Shen Fu; Han-Lin Wang; Zi-Jian Zhai; Ren-Peng Chen; Daniel Dias (Transportation Geotechnics, 2026)

Evolutionary mechanism of passive soil arching effect in sand at various relative densities and heights of fill - Han-Lin Wang; Zi-Jian Zhai; Xiang-Shen Fu; Xiao-Hu Zhang; Daniel Dias; Ren-Peng Chen (Transportation Geotechnics, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Structural reconstruction-induced electronic Kagome lattices with low-energy flat bands in twisted double bilayer graphene - Mo-Han Zhang; Yalei Zhang; Chen-Yue Hao; Zi-Han Guo; Chao Yan; Ya-Xin Zhao; Ya-Ning Ren; Jin-Hua Gao; Shengjun Yuan; Lin He (Science Bulletin, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Aerosol-cloud layer detection algorithm of the DQ-1/ACDL - Feiyue Mao; Weiwei Xu; Zengxin Pan; Lin Zang; Ge Han; Linxin Dai; Xiuqing Hu; Weibiao Chen; Wei Gong (Remote Sensing of Environment, 2026)

Comparison of metabolomic and transcriptomic analyses of Ganping mandarin fruit following on tree storage and postharvest low temperature storage - Xinyu Huang; Luoao Lin; John B. Golding; Penta Pristijono; Su Guo; Youjian Yu; Gang Chen; Dongdao Han; Huqing Yang; Ruihua Bai; Yongxin Li (Postharvest Biology and Technology, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Efficient bridge pier scour profile prediction by an enhanced Bayesian DeepONet - Zhao Chen; Han Lin; Dingzhu Zhashi; Wen Xiong; C.S. Cai (Ocean Engineering, 2026)

RAD51 m6A and PARylation modification orchestrate benzene-induced haematological toxicity - Lin Chen; Fengzhen Cui; Han Li; YuTao Zeng; Zhongming Wu; Weitian Chen; Qiaosheng Wen; Chunnian You; Yunqiang Xu; Lei Sun; Mingwei Sun; Qian Sun; et al. (Journal of Hazardous Materials, 2026)

Nonagricultural emissions and N2O5 hydrolysis drive wintertime inorganic nitrogen aerosol formation in Sichuan Basin: Nitrate and ammonium isotopic evidence - Xiaojuan Huang; Yuhan Long; Yuepeng Pan; Lin Han; Xiaoling Zhang; Junke Zhang; Runqi Zhang; Yingjun Chen; Jianmin Chen (Journal of Hazardous Materials, 2026)

Predicting in-situ CO2 solubility in formation brines using Raman spectroscopy and machine learning: Implications for offshore geological carbon storage - Ying Teng; Yiqi Chen; Xiran Lin; Mingkun Bai; Senyou An; Shuyang Liu; Pengfei Wang; Tao Zhang; Songbai Han; Jinlong Zhu; Jianbo Zhu; Heping Xie (Gas Science and Engineering, 2026)

Cold exposure triggers distinct RNA editing, alternative splicing, and gene expression patterns in cold domestication pufferfish (Takifugu obscurus) - Shuang Han; Jie Wang; Yuhao Luo; Jingping Zhang; Youquan Wang; Taixing Lin; Boyan Xu; Qigen Liu; Liangbiao Chen (Fish & Shellfish Immunology, 2026)

Tuning Fe-P covalency via regenerative phosphorus vacancies for efficient aqueous cyclohexanone degradation - Han Feng; Zhengyi Lu; Ming Chen; Changming Zhong; Yongquan Wang; Rong Lin; Wenfeng Xu; Junming Hong (Environmental Research, 2026)

Characteristics of benthic microeukaryotic communities in different ecosystems of the Yellow River Estuary salt marshes - Jing Han; Lin Sun; Junrong Liang; Yahui Gao; Changping Chen (Estuarine, Coastal and Shelf Science, 2026)

A floatable and anisotropic composite aerogel for enhanced synergistic adsorption-catalysis of antibiotics in marine aquaculture wastewater - Xiaoxia Lin; Yongli Chen; Keying Li; Xiyue Han; Xuexia Zhang; Yuqi Li; Hui Zhang (Desalination, 2026)

Inhalable tetrahedral DNA nanoplatforms for dual-barrier penetration and sustained deep-lung delivery of small-molecule drugs - Fenglin Jiang; Qi Han; Hao Deng; Jiaqi Li; Alimire Alifu; Zhuo Chen; Linlin Deng; Xiaoxiao Cai; Yu Chen; Yunfeng Lin (Chemical Engineering Journal, 2026)

A pH/glucose dual-responsive Janus dressing with optimized gradient modulus/tissue adhesion promotes diabetic wound healing by dynamic drug-payload release - Huabiao Ye; Ting Dong; Ruoxuan Li; Lihua Fang; Kaifang Xie; Guangting Han; Que Chen; Shan Chi; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2026)

Sulfone site enables H2O2 practical fabrication over metal-free photocatalyst - Zhi-Peng Tao; Lin Liu; Ke-Chao Wang; Chen-Ning Li; Jia-Qi Chu; Zhen-Hui Kang; Zheng-Bo Han (Chemical Engineering Journal, 2026)

Photothermal-pancaking synergy in interfacial absorption enables rapid purification of viscous oil-in-water emulsions - Ruoxuan Li; Chaofan Zhu; Ching-Wen Lou; Kaifang Xie; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Chemical Engineering Journal, 2026)

Optimization of bacterial nanocellulose synthesis using surfactants for immobilization of Saccharomyces cerevisiae to enhance resistance to lignocellulose-derived inhibitor - Yetong Feng; Dingkang Wei; Shuai Han; Peihong Chen; Jie Liu; Tao Chen; Yiran Yan; Yang Bai; Linxu Chen; Jianqun Lin; Jianqiang Lin; Zixiang Xu; et al. (Bioresource Technology, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Identification of Axonal Regeneration-Related Genes and a Potential Analgesic Drug for Neuropathic Pain - Yang Liu; Yongxue Zhang; Shikang Hao; Yabin Shi; Xiaoyue Chen; Zhibin Ye; Guona Zheng; Lin Kang; Han Hao (Molecular Neurobiology, 2026)

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

An aptamer integrated electrochemistry and photoluminescence dual-mode microfluidic biosensor for sensitive and accurate ovarian cancer extracellular vesicles detection - Xiaoshuang Chen; Junxia Han; Mingyuan Sun; Zhenhua Wang; Shuai Wang; Lin Han; Yu Zhang (Analytica Chimica Acta, 2026)

Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Numerical modelling of the through-draught induced by traveling trains in subways and its impact on airborne droplet transmission in compartments - Tiantian Wang; Jiyu Yao; Wei Han; Yibin Lu; Zhe Chen; Fangcheng Shi; Zhang Lin (Process Safety and Environmental Protection, 2025)

Early Cretaceous radiolarians and siliceous rock geochemistry from Kangmar, Southern Xizang: Biostratigraphic, paleoenvironmental, and paleogeographic implications for the Neo-Tethys Ocean - Han Yan; Hanting Zhong; Chenyu Wang; Zongqi Lin; Cai Wang; Xiachao Huang; Chao Chen; Mingcai Hou (Marine Micropaleontology, 2025)

Relating small waterbody denitrification with ecosystem respiration in an intensive anthropogenic region - Xuemei Zhao; Yi Zhu; Xu Yang; Li Zhang; Xuan Huang; Chunwang Li; Kebing Chen; Han Lin; Dongli She; Yongqiu Xia (Journal of Hydrology, 2025)

Pollution characteristics and influencing factors of rural greywater: A field investigation across China - Hao Wang; Xuejiao Han; Xingzhou Lin; Yao Chen; Bin Hong; Qijia Cai; Wenli Zheng; Jianying Chao; Licai Hu; Jiping Xiao; Junneng Wang; Hongbing Zhao; et al. (Journal of Environmental Management, 2025)

Enhanced photothermal combustion efficiency of propane in the presence of SO2 over Mo-doped Pt/WO3 catalyst: Rational utilization of Ptδ+-(SO4)δ- - Lijing Han; Huimin Chai; Jinliang Lin; Kaiting Chen; Qingwei Li; Qiuhong Zhou; Jun Ye; Hai Liu; Xinyu Han; Zeshu Zhang; Yibo Zhang (Journal of Environmental Chemical Engineering, 2025)

Control properties of PAA/sulfite advanced oxidation process for DCAN, DCAcAm and TCNM - Yuchen Wang; Tao Lin; Han Chen; Feiyu Lu (Journal of Environmental Chemical Engineering, 2025)

Dry alkali-ball milling for high-solid conversion of biomass to sugar and ethanol: Comparison with conventional ball milling - Kaili Ding; Hao Lin; Xueli Chen; Xiwen Jia; Suan Shi; Xiaojun Guo; Ling Zhou; Lujia Han; Weihua Xiao (Fuel, 2025)

A multi-task deep attention network for simultaneous rapid quantification of sucrose, glucose, and fructose contents in pumpkin using FT-NIR spectroscopy - Yingchao Xu; Jiayu Luo; Shudan Xue; Huihui Han; Wenlong Luo; Wenjun Liu; Qingmin Jin; Huijing Lin; Baoling Chen; Yingyin Lin; Rong Zhang; Yujuan Zhong (Food Chemistry, 2025)

Exosome-like nanovesicles (EVNs): A comprehensive overview of their isolation, characterization and biological applications - Haiyu Wu; Pan Gao; Wenxu Zhou; Chunping Chen; Min Wang; Lin Han (Food Chemistry, 2025)

A systematic analysis of the sensory qualities of Asparagus cochinchinensis (lour.) Merr. From the four major production areas in China: Sensory characteristics, key flavor substances, and molecular mechanisms of flavor formation - Jingping Zhong; Shuyu Deng; Mengqi Li; Honglin Yin; Xinming Chen; Zhiyan Deng; Xiaoming Bao; Qingchu Tan; Junzhi Lin; Dingkun Zhang; Gang Shen; Li Han; et al. (Food Chemistry, 2025)

Acute skin responses to ammonia in striped catfish (Pangasianodon hypophthalmus) unveil a potential damage-buffering mechanism - Wei-Hsuan Hsiao; Shun-Yi Lin; Tsung-Lin Liu; Han-Chen Ho; Liang-Chun Wang (Fish & Shellfish Immunology, 2025)

White spot syndrome virus facilitates and relies on shrimp de novo nucleotide synthesis to support viral pathogenesis - Cong-Yan Chen; Der-Yen Lee; Shih-Shun Lin; Chun-Hung Liu; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

Mitochondrial pyruvate carrier proteins mediate host-pathogen interactions during WSSV infection in shrimp - Yu-Chen Lin; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Efficient preparation of large-area anisotropic graphite films with high thermal conductivity and excellent electromagnetic shielding performance - Zhihong Han; Mingyi Tan; Daming Chen; Wenzheng Zhang; Zhipeng Lin; Jiahui Zhou; Yuhao Fang; Shengze Zhang; Qihong Wei; Xinghong Zhang; Wenbo Han (Chemical Engineering Journal, 2025)

CO2-mediated SEI engineering via Li2C2O4 pre-lithiation: A dual-functional strategy for high-stability SiOx/Gr anodes - Lifan Wang; Peng Han; Lin Zhang; Cong Zhong; Min Chen; Ruixiang Li; Yiheng Wu; Zhengping Zuo; Xindong Wang; Xuefeng Wang; Chun Zhan; Guicheng Liu (Chemical Engineering Journal, 2025)

Theranostic nanoplatform for triple-negative breast cancer therapy: Autophagy suppression-coordinated siRNA delivery triggers apoptosis, ferroptosis, and pyroptosis via photothermal activation - Guobao Ning; Lishen Yang; Bilian Li; Jianghua Lin; Shufen Li; Fengqi Zhou; Han Chen; Xingye Zheng; Weijie Sun; Hui Zhao; Can-Peng Li (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Synergistic enhancement of CO2 hydrate growth by montmorillonite and tryptophan: Insights from piecewise kinetic modeling - Xiran Lin; Ying Teng; Mingkun Bai; Yiqi Chen; Pengfei Wang; Liangbin Xu; Senyou An; Jianbo Zhu; Jinlong Zhu; Songbai Han (Chemical Engineering Journal, 2025)

Morphological, histological and multi-omics analysis revealed the molecular response of female western mosquitofish (Gambusia affinis) to levonorgestrel exposure - Kaichun Chen; Tongfu Lu; Weijian Chen; Shengyue Lin; Dingxian Chen; Shuzheng Ye; Weiqian Liang; Sixun Li; Binhua Deng; Jian Gong; Chong Han; Qiang Li (Aquatic Toxicology, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Enhanced production of eicosapentaenoic acid and fucoxanthin in Phaeodactylum tricornutum via a two-stage strategy with multifactorial synergistic effects - Xin Dong; Meng-Han Zhao; Chen-Xi Li; Xiao Lin; Ning Ma; Hong-Jin Qiao; Dian-Feng Han; Ying-Jiang Xu (Journal of Applied Phycology, 2025)

Levonorgestrel-induced sex reversal in mandarin fish (Siniperca chuatsi): An effective protocol for all-female production and its aquaculture applications - Shiyan Liu; Jinmeng Teng; Suhan Peng; Shuang Liu; Jiaqi Lin; Long Chen; Ju Hu; Haoran Lin; Caiyun Sun; Shuisheng Li; Songlin Chen; Chong Han; et al. (Animal Reproduction Science, 2025)

Artificial Intelligence in Environment and Human Health: Progress, Opportunities and Challenges - Dongyang Han; Yanyi Xu; Luofei Lin; Xia Meng; Renjie Chen; Haidong Kan (Current Environmental Health Reports, 2025)

Influence of Human Activity on Wet Deposition and Nitrogen Species in Coastal and Marine Environments - Hung-Yu Chen; Jia-Han Lin; FuJung Tsai (Journal of Marine Science and Engineering, 2025)
In this study, 101 and 102 rainwater samples were collected from April 2020 to February 2024 in a coastal and marine area, respectively. The results show that the Cl/Na ratios in both study areas were lower than the seawater value (1.17), suggesting chloride depletion. The chloride depletion rates in both areas decreased after the COVID-19 lockdown period. The molar ratio of NH4+ to non-sea-salt sulfate (nss-SO42−) was 1.54, with a mixture of (NH4)2SO4 and NH4HSO4 in the coastal area, and 0.83, with NH4HSO4 as the main form, in the marine area. A decreasing trend attributed to high O3 and relative humidity (RH) levels occurred in 2022. Among the dissolved organic nitrogen (DON) species, DON accounted for 24% and 32% of the total dissolved nitrogen (TDN) in the coastal and marine areas, respectively, indicating a greater relative contribution under lower anthropogenic influence. On the basis of the correlation between the species and source analysis results, NO3− mainly originated from fossil fuel combustion, NH4+ originated from agricultural emissions and secondary aerosols, and DON originated from secondary aerosols via combustion processes and natural emissions. In terms of the flux, due to lockdown activities, the Dissolved Inorganic Nitrogen (DIN) flux decreased significantly from 40.6 to 19.3 mmol m−2 yr−1 in the coastal area and from 27.7 to 15.1 mmol m−2 yr−1 in the marine area. Additionally, a slight decrease occurred in the DON flux, from 21.6 to 19.3 mmol m−2 yr−1 and from 27.7 to 15.1 mmol m−2 yr−1, respectively. Regarding new production, based on nitrogen input, the level in the coastal area decreased from 5.83 to 2.10 g C m−2 yr−1, and that in the marine area decreased from 3.92 to 1.55 g C m−2 yr−1, indicating a significant reduction during the COVID-19 lockdown.

Removal of 6PPD-quinone by Fe(II)-GLDA complex-activated periodate under neutral conditions - Yiyang Lin; Tao Lin; Han Chen; Junding Yin (Journal of Water Process Engineering, 2025)

Microalgal-bacterial granular sludge enhances oxytetracycline removal: Microbial responses, degradation pathways, and adaptive mechanisms - Yunqing Li; Xiaoying Zheng; Haidong He; Ruijie Hu; Zongshuo Han; Jiaqing Tao; Tao Lin; Wei Chen (Journal of Hazardous Materials, 2025)

Elucidation of the molecular mechanism for the phenolic acid removing the fishy odor bound to proteins in sea bass - Huanqing Lei; Yaoxing Chen; Rui Wang; Qiaohui Zeng; Langhong Wang; Jian Li; Wenhao Lin; Xinan Zeng; Zhong Han; Ji Ma; Ruoyong Wang (Food Chemistry, 2025)

Unraveling ozone formation sensitivity to ambient VOCs and NOx at urban and mountain sites in a typical city of eastern China - Xiaorong Zhang; Deming Han; Jiandong Shen; Feng Chen; Liuyan Cao; Jinhan Chen; Xu Lin; Yang Yang; Lin Yang; Wenjing Li; Xiaowei Qiao; Shuangxu Zhou; et al. (Environmental Pollution, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

Natural-product-derived carbon dots to combat Candida albicans infections without drug resistance by multifaceted antifungal mechanisms - Babar Khan; Haiyan Wang; Yun Wang; Faisal Latif; Peiya Chen; Mengyuan Han; Kejia Feng; Yonghao Ye; Fu-Gen Wu; Fengming Lin (Chemical Engineering Journal, 2025)

Preparation of antibacterial CO2-based polycarbonate hydrogels with dual cross-linkages for co-loading of antibiotics and hypoglycemic agents and their applications on diabetic wound dressings - Zheng-Ian Lin; Tzu-Hsien Tsai; Guan-Lin Liu; Chih-Yuan Hsu; Siang-Ming Tsai; Yi-Ping Fang; Wing-Cheung Law; Han-Lin Tsai; Jia-Ying Tsai; Hsuan-Ying Chen; Bao-Tsan Ko; Pei-Wen Cheng; et al. (Chemical Engineering Journal, 2025)

Food-derived bioactive peptides: health benefits, structure–activity relationships, and translational prospects - Hongda Chen; Jiabei Sun; Haolie Fang; Yuanyuan Lin; Han Wu; Dongqiang Lin; Zhijian Yang; Quan Zhou; Bingxiang Zhao; Tianhua Zhou; Jianping Wu; Shanshan Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

How can the deposit return scheme promote the high-value recycling of food contact PET? - Wanying Lin; Xingmin Chen; Jinfen Huo; Yuan Chen; Han Yu; Yan Lin (Environment, Development and Sustainability, 2025)

Molecular mechanisms and therapeutic application of pyrogallic acid in treating multidrug-resistant Klebsiella pneumoniae infections in American bullfrogs (Aquarana catesbeiana) - Han Lin; Furong Li; Yufang Huang; Yongping Ye; Ziyan Chen; Chun Liu; Ruiai Chen (Aquaculture, 2025)

Effects of compound probiotics on intestinal and liver transcriptome, immunity and disease resistance of zig-zag eel (Mastacembelus armatus) - Yuwei Feng; Yiman Chen; Zhiting Zuo; Xianshan Lin; Qiaoyi Chen; Along Gao; Zhide Yu; Chong Han; Hu Shu (Aquaculture, 2025)

Exploration of low-dose ozone-activated periodate (O₃/IO₄⁻) for rapid degradation of the β-Blocker pindolol: efficiency and radical mechanism - Mengya Zhang; Tao Lin; Han Chen (Water Research, 2025)

Corrigendum to “Along-strike variations in intermediate-depth seismicity in the southernmost Mariana subduction zone: Impact from the subduction of an oceanic plateau” [Tectonophysics, Volume 913, 27 October 2025, 230875, https://doi.org/10.1016/j.tecto.2025.230875] - Han Chen; Gaohua Zhu; Hongfeng Yang; Jiangyang Zhang; Shaopin Lu; Chuanxu Chen; Jian Lin; Yiming Luo (Tectonophysics, 2025)

Along-strike variations in intermediate-depth seismicity in the southernmost Mariana subduction zone: Impact from the subduction of an oceanic plateau - Han Chen; Gaohua Zhu; Hongfeng Yang; Jiangyang Zhang; Shaopin Lu; Chuanxu Chen; Jian Lin; Yiming Luo (Tectonophysics, 2025)

Preparation of sludge derived fuels for co-incineration in waste incinerators: Industrial tests and life cycle assessment - Yanfei Lin; Hanqiao Liu; Guoxia Wei; Tong Li; Qianlong Han; Zilu Liu; Xinrui Su; Yifan Chen (Sustainable Production and Consumption, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Chemical constituents isolated from leaves of seashore plant Aglaia rimosa - Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung; Wei-Yu Lin; Zhen-Hong Han; You-Ying Chen; Chun-Lin Chen (Phytochemistry Letters, 2025)

PDHA1-mediated H3K18 lactylation is involved in arsenic-induced nonalcoholic fatty liver disease by activating the CD36–NLRP3 inflammasome axis - Han Li; Zhenyang Li; Lin Chen; Xiaoshan Peng; Dapeng Wang; Qian Sun; Yuting Chen; Aihua Zhang; Qizhan Liu; Huanwen Tang (Journal of Hazardous Materials, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Microstructure-property relationships in Cu/N-TiO₂ photocatalytic concrete for marine applications: Role of preparation strategies - Guoliang Lin; Mengchen Huang; Sen Chen; Kun Li; Kun Han; Minyi Liu; Yuxiang Li; Wenhua Chen (Journal of Environmental Chemical Engineering, 2025)

Investigation on the use of waste biomass as a carbonaceous reducing agent in industrial silicon smelting: Thermogravimetric analysis, cooperative behavior and reaction characteristic - Chenguang Han; Zhengjie Chen; Wenhui Ma; Lin Wang; Xiaowei Gan (Journal of Environmental Chemical Engineering, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Oxidative stress-mediated neurotoxicity of para-xylene and neuroprotection by gluconolactone in Xenopus laevis - Lu Han; Wenyi Huang; Lingyun Meng; Xinyi Duan; Yufei Wu; Qihui Lin; Xiaohua Wu; Qi Chen; Wanhua Shen (Environmental Pollution, 2025)

Shrinkage effect of innovative group studs configuration on steel-UHPC composite deck in a girder - Sheraz Abbas; Han Xiao; Chen Xu; Wei Wang; Zhipin Lin (Engineering Structures, 2025)

Single-electrode multiplex sensing via metal ion displacement method - Yiming Zhang; Zhi Chen; Songrui Wei; Huiling Lin; Yujun Zhang; Yingxia Liu; Jing Wang; Qi Gao; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

Tartaric acid-functionalized MOF-808 with tailored ultramicroporous for efficient separation of C2H2 from C2H2/C2H4/CO2 mixture - Chen-Ning Li; Liu Lin; Daqiang Yuan; Zheng-Bo Han (Chemical Engineering Journal, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Target mitochondrial pyroptosis with sequential delivery of nanoliposomes to alleviate secondary injury following traumatic brain injury - Yuwei Lin; Jiaqi Jin; Qingyi Han; Diancheng Hang; Zijun Chen; Suihan Ye; Qing Guo; Xuyang Huang; Jinna Li; Hengzhu Zhang; Xuefeng Zhang; Yufu Zhu (Chemical Engineering Journal, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Levonorgestrel-induced anal fin masculinization in mosquitofish: Do TGF-β/BMP signaling and osteogenic remodeling underpin endocrine disruption in aquatic ecosystem? - Weiqian Liang; Tongfu Lu; Dingxian Chen; Weijian Chen; Kaifeng Wang; Jie Lai; Shengyue Lin; Lin Gui; Jian Gong; Chong Han; Qiang Li (Aquatic Toxicology, 2025)

Fine root trait dynamics and their relationships with productivity across grasslands under extreme drought - Yuan Shi; Taofeek O. Muraina; Saheed O. Jimoh; Niwu Te; Lin Song; Jiaqi Chen; Hongqiang Wang; Qiang Yu; Xiaoan Zuo; Xingguo Han; Wentao Luo; Scott L. Collins (Oecologia, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Design of a Wearable Finger PPG-Based Blood Glucose Monitor - Mutian Wang; Xuelei Liu; Wenyi Han; Xinyu Lin; Xin Chen; Shun Zhao; Zhiqiang Zhuang; Leian Zhang; Peiqiang Su (Annals of Biomedical Engineering, 2025)

Adaptive Evolution for Freshwater Adaptation in Coilia nasus by Directional Selection on Osmoregulation Genes - Shuang Han; Jie Wang; Taixing Lin; Jingping Zhang; Adelino V. M. Canario; Qigen Liu; Liangbiao Chen (Molecular Ecology, 2025)
The molecular mechanisms underlying the adaptation to freshwater habitats in fish of marine origin remain unclear. Grenadier anchovies, such as Coilia nasus , originate from marine environments and include both anadromous and freshwater‐resident conspecifics, making them ideal for studying adaptive evolution from marine to freshwater habitats. We conducted a comparative population genomic and transcriptome analysis of two distinct C. nasus lineages, one anadromous and the other freshwater‐resident, collected from mainstream and estuarine regions of the Yangtze River, China. By genome‐wide genotyping of the anadromous and the freshwater‐resident populations, we observed significant divergence in osmoregulation, energy metabolism, and immune response pathways associated with ecological adaptation and energy expenditure for migration. Some ion transport genes such as CAMK1 , ATP1α3 , KCNJ1 and SLC30A2 were identified that may contribute to freshwater adaptation. Notably, numerous mineralocorticoid signalling genes (e.g., NR3C2 , SGK1 , ATP1α3 , KCNJ1 ) exhibit dynamic change between the anadromous and freshwater populations, suggesting an important role for the hormone cortisol in regulating salinity acclimation in euryhaline fish. Among these genes, the ion channel ATP1α3 experienced adaptive amino acid substitutions (Val317Ile and Thr329Ser), which appear to be evolutionary hotspots across migratory species based on ortholog comparisons. These variants may facilitate sodium/potassium transport and highlight salinity tolerance as a key driver of divergence in anadromous fish transitioning to freshwater. These results enhance our understanding of the genetic basis underlying freshwater adaptation for an anadromous fish across osmotic boundaries.

Microbial-Modified Organosilica-Based Dual-Mode Fluorescent Probe for Zn²⁺ and pH Sensing with Potential Application in Gut Immunity Modulation - Qing-Qing Han; Fang Chen; Zhao-Lin Zhang; Dong-Ya Chen (Journal of Fluorescence, 2025)

Rapid oxidation of gatifloxacin by ozone/sulfite process: Generation of reactive species and radical-mediated mechanisms - Junding Yin; Tao Lin; Han Chen (Water Research, 2025)

A novel multifunctional suction-controlled apparatus for investigating tensile strength of unsaturated soils - Xiang-Shen Fu; Han-Lin Wang; Ren-Peng Chen; Cheng-Shuang Yin; Yue-Hui Sun; Xiao-Hu Zhang; Daniel Dias (Transportation Geotechnics, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

A grid search-based optimal trajectory planning approach for automatic berthing of underactuated unmanned surface vehicles - Shidi Wu; Shifeng Ding; Lin Geng; Zihan Chen; Sen Han; Li Zhou (Ocean Engineering, 2025)

Identification of heavy metal transport-related genes and microRNAs in response to cadmium toxicity and micronutrient deficiency in barley roots - Liuhui Kuang; Jian Chen; Jie Ding; Tao Yan; Fei Gao; Lin Li; Zhigang Han; Dezhi Wu (Journal of Hazardous Materials, 2025)

POM-promoted synergistic catalysis of NO and chlorobenzene over amorphous MnCeOx catalysts: Activation of lattice oxygen, role of acid site, catalytic mechanism - Shengyong Lu; Xuanhao Guo; Xinlei Xu; Zhengdong Han; Min Chen; Beilong Lin; Yaqi Peng; Guanjie Wang (Journal of Hazardous Materials, 2025)

Particle size distribution (PSD) of mine waste dump via unmanned aerial vehicle (UAV) image recognition and sieving - Han Ke; Zi Han Lin; Xiao Fei Wei; Bing Zhou; Tian Shou Hu; Shuai Zhang; Jie Hu; Chen Sheng Zhang (Engineering Geology, 2025)

Downward soil arching below excavation base: Theory and application - Kai Wu; Fan-yan Meng; Ren-peng Chen; Han-Lin Wang (Computers and Geotechnics, 2025)

Efficient perfluorooctanoic acid degradation using by a vacuum ultraviolet-activated dithionite reduction system: Reactive species, process optimization, degradation pathways, and toxicity changes - Jinmin Su; Tao Lin; Yuchen Wang; Han Chen; Xinran Ge (Chemical Engineering Journal, 2025)

Multifunctional Cu-engineered NH2-MIL-125Ti@ZnIn2S4 heterojunction with dual-channel H2O2 activation for ultrafast water-mediated Cr(VI) photoreduction - Guangyuan Chen; Wei Han; Chenyang Lin; Yubao Li; Shijian Zhou; Yan Kong (Chemical Engineering Journal, 2025)

Complete nitrogen removal via novel nitrite-absent anodic anammox process with granular sludge in titanium anode microbial electrolysis cells - Liang Zhu; Jingwei Ma; Zhanhang Wang; Ying Han; Long Chen; Hui Sun; Qiulai He; Lin Deng; Zhou Shi; Shuizhou Ke (Chemical Engineering Journal, 2025)

Quality valuation and open fermentation process of polyhydroxyalkanoates production for the waste carbons biorefinery using Paracoccus sp. TOH as chassis - Leizhen Zhao; Lin Chen; Yuanxi Zhang; Jiexuan Han; Gaojie Sun; Jianhang Qu (Biomass and Bioenergy, 2025)

Creating easily accessible adsorption sites in natural wood-derived hierarchical porous carbon via a controlled delignification strategy for organic pollutant removal - Minjiao Chen; Meihua Li; Peng Jiang; Wenjie She; Han Lin; Jiahua Zhu (Biomass and Bioenergy, 2025)

An efficient network with state space model under evidential training for fetal echocardiography standard view recognition - Changzhao Chen; Yiman Liu; Tongtong Liang; Shibin Lin; Xiaoxiang Han; Xiaohong Liu; Jing Yang; Yuqi Zhang; Xueping Yan (Medical & Biological Engineering & Computing, 2025)

Berberine attenuates the expression of NLRP3 and downstream inflammasome effectors in diabetic retinopathy - Na Li; Ji-Lin Chen; Yi-Jian Sun; Jia-Fan Sun; Ting-Hua Wang; Amy Yi Hsan Saik; Alan Han-Kiat Ong (Journal of Natural Medicines, 2025)

Effects of lichen symbiotic bacteria-derived indole-3-acetic acid on the stress responses of an algal–fungal symbiont - Yan-Yu Lin; Han-Chen Ho; Jui-Yu Chou (Brazilian Journal of Microbiology, 2025)

Distinct responses of fungal and bacterial denitrification genes to seasonal changes, nitrogen deposition and precipitation reduction in subtropical forest soils - Qirun Chen; Fengyi Han; Maokui Lyu; Zhiwei Zeng; Yanjiang Cai; Yuheng Cheng; Zi-Yang He; Milin Deng; Jinsheng Xie; Yongxin Lin (Applied Soil Ecology, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Quantifying assembly processes of dissolved organic matter pools in eutrophication using high-resolution mass spectrometry and ecological models - Guan-Lin Chen; Chen Qian; Meng Du; Min-Jie Tong; Jie-Jie Chen; Han-Qing Yu (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Microbiological mechanisms of lignin- and humus-derived small molecule addition promoting straw conversion into soil organic matter in a sodic soil - Jingwang LI; Lin CHEN; Fengxia YUE; Congzhi ZHANG; Donghao MA; Guixiang ZHOU; Jiangli WANG; Changdong HAN; Biao FENG; Jiabao ZHANG (Pedosphere, 2025)

Heavy metal pollution enhances herbivore resistance of male poplars over females through modifying volatile-mediated tritrophic interactions - Tiantian Lin; Xiaotao Han; Guoqing Zhu; Wanci He; Lianghua Chen; Jing Li; Yan Wang; Tao Li (Journal of Hazardous Materials, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Antibacterial and flame-retardant TEMPO-oxidized cellulose nanofibrils/chitosan-based sponge for efficient PM2.5 capture - Yifan Chen; Shite Lin; Weisheng Han; Youwen Chen; Qijun Zhang; La Hu; Wenbiao Zhang; Jingda Huang (Carbohydrate Polymers, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Seasonal dynamics of ammonia-oxidizing archaea and bacteria in subalpine forests of western Sichuan - Li Zhang; Su Chen; Zebin Jiao; Sining Liu; Wenlan Huang; Lulu Huang; Liyun Yu; Lixia Wang; Bo Tan; Hongwei Xu; Lin Xu; Chengming You; et al. (Plant and Soil, 2025)

Organic amendments with low C/N ratios enhanced the deposition of crop root exudates into stable soil organic carbon in a sodic soil - Jingwang Li; Lin Chen; Congzhi Zhang; Changdong Han; Biao Feng; Donghao Ma; Guixiang Zhou; Jiabao Zhang (Plant and Soil, 2025)

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Efficient antibiotic tetracycline degradation and toxicity abatement via the perovskite-type CaFexNi1-xO3 assisted heterogeneous electro-Fenton system - Yuling Liang; Aochen Feng; Naif Abdullah Al-Dhabi; Jing Zhang; Wenle Xing; Tao Chen; Yuxuan Han; Guangming Zeng; Lin Tang; Wangwang Tang (Water Research, 2025)

Air classification efficiency evaluation of landfilled municipal solid waste using experiments and a probabilistic method - Lin Feng Yu; Yu Qi Jin; Miao Xin Yuan; Fei Zhang; Jie Hu; Ji Wu Lan; Yu Fan Wei; Yun Min Chen; Han Ke (Waste Management, 2025)

Design of heavy chain antibody-drug conjugates targeting c-Met to eradicate lung adenocarcinoma giant tumors with a single-dose - Wenjing Ning; Han Liu; Hongye Zeng; Xiaojing Qin; Lin Xu; Shiting Yang; Zhiren Zeng; Na Yuan; Zhenzhen Zhu; Xiaoqing Chen; Tao Xu; Fentian Chen; et al. (Science Bulletin, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Ecological impacts of treated effluent on multitrophic biodiversity and their interactions - Wei Xiong; Ting Chen; Xun Du; Lin Hou; Yiyong Chen; Jing-Long Han; Aibin Zhan (Environmental Research, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

A biomimetic liposome platform targeting non-small cell lung cancer to modulate the inflammatory and metabolic microenvironment for enhanced therapy - Xinyu Jiang; Pengfei Mao; Minghui Wang; Dingchao Shen; Linyi Zhang; Yingyi Zhao; Xindan Liang; Zihao Huang; Yunzhi Wang; Yinhao Lin; Zihao Tao; Yuqi Han; et al. (Chemical Engineering Journal, 2025)

Cycleift: A deep transfer learning model based on informer with cycle fine-tuning for water quality prediction - Yang Yu; Shixin Zhao; Lintong Han; Lin Peng; Yanmei Xu; Qiujin Tian; Sen Chen; Zuogang Yang; Qiude Li; Zuquan Hu (Stochastic Environmental Research and Risk Assessment, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Correlation study of 5-HT in brain with cognitive function and anxious-like behavior in APP/PS1 transgene mice - Li Yuan; Linshan An; Rui Xie; Jiahong Cai; Dong Li; Xiaorong Chen; Wenjing Guo; Yinran Lin; Chunjing Zhu; Yongli Chang; Kunbo Wang; Weina Han; et al. (Sleep and Biological Rhythms, 2025)

Drying–rewetting cycles determine maize growth by shifting microbial community assembly and coexistence patterns - Ling Ma; Guixiang Zhou; Lin Chen; Zhongjun Jia; Hongtao Zou; Congzhi Zhang; Donghao Ma; Changdong Han; Jiabao Zhang (Plant and Soil, 2025)

Exploring exhaled volatile organic compounds as potential biomarkers in anti-MDA5 antibody-positive interstitial lung disease - Yuxuan Wang; Xuewen Wang; Luqin Yang; Ke Wang; Fengqin Zhang; Huihui Yue; Junqi Wang; Minhua Peng; Pengnan Fan; Xiangcheng Qiu; Han Zhang; Wei Lin; et al. (Molecular and Cellular Biochemistry, 2025)

The failure modes and evolution process of loess landslide dams via flume tests - Zekun Li; Penghui Ma; Ning Han; Qixian Jiao; Lisen Chen; Lin Ran; Zhijie Jia; Luqing Zhao; Jingjing Nan; Jianbing Peng (Landslides, 2025)

The impact of changing ambient population composition on crime during COVID-19 lockdowns - Xin Gu; Lin Liu; Su Yeon Han; Minxuan Lan; Hanlin Zhou; Debao Chen; Zihan Su (Applied Geography, 2025)

Heavy metal contamination in fish and human health risks from lakes of a mega inter-basin water diversion - Wenxia Fan; Wentong Xia; Lian-Shin Lin; Han Liu; Xiao Qu; Wei Xin; Lizhou Tang; Yushun Chen (Chemosphere, 2025)

Revealing considerable emissions reduction potential in flight operations: A real-time emission perspective - Simeng Ma; Shizhuo Lin; Bo Han; Chen Zhang; Zhiqiang Wei; Lingxiang Xue; Jingbo Zhao; Kun Wang; Jian Yu; Philip K. Hopke (Transportation Research Part D: Transport and Environment, 2025)

Bisphenol S promotes clear cell renal cell carcinoma progression by modulating the WNT5A-dependent EMT pathway - Hua Zhang; Fei Lin; Bo-Han Lin; Xiong-Lin Sun; Qing-Shui Zheng; Rui Gao; Yong Wei; Shao-Hao Chen; Xue-Yi Xue (Toxicology, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Advanced oxidation process with hydrogen peroxide and sulfite for superfast degradation of micro-contaminants in drinking water - Han Chen; Tao Lin; Yuchen Wang; Feiyu Lu; Yiling Shi; Junding Yin (Journal of Hazardous Materials, 2025)

Passivation mechanism driven selective leaching for recycling spent LiFePO4 lithium-ion batteries - Yurong Han; Menglong Yan; Yinzhuang Fang; Yifeng Han; Yi Chen; Liangyou Lin; Jingwen Qian; Tao Mei; Xianbao Wang (Journal of Environmental Chemical Engineering, 2025)

New insights into the impact of microplastics on nitrogen transformation in urban rivers based on field experiments - Cheng Yang; Yuanyuan Feng; Jinjiang Duan; Nayin Li; Qingping Zou; Peng Lin; Mengli Chen; Jiang Li; Han Zhang (Journal of Environmental Chemical Engineering, 2025)

Honey-processed Astragalus polysaccharides exhibit enhanced Qi-tonifying effects via structural modifications and microbiome-metabolome regulation - Zhaohui Lin; Lili Lu; Wenlong Guo; Shuyu Han; Yufei Tian; Hongyuan Chen; Wen Rui (Food Bioscience, 2025)

Optimization of in-situ synthesis of methane in microbial electrochemical systems: influence of substrate concentration, polymerization degree, and applied voltage - Cuixia Liu; Wen Liu; Shengao Meng; Dongyu Han; Zhihao Pan; Junhua Chen; Chunmian Lin (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

The heterogeneous response in leaf traits among seasons and plant types of an evergreen broadleaf forest in western China to nitrogen addition was regulated by fertilization intensity - Wenzheng Chang; Qiu Song; Tianxing Liang; Jie Chen; Lixia Wang; Han Li; Li Zhang; Chengming You; Hongwei Xu; Lin Xu; Bo Tan; Zhenfeng Xu; et al. (Plant and Soil, 2025)

Overview and Prospect of Data Assimilation in Numerical Weather Prediction - Lili Lei; Fuzhong Weng; Wansuo Duan; Yaodeng Chen; Lin Zhang; Ruichun Wang; Jun Yang; Xiaohao Qin; Wei Han; Jun Li; Jinzhong Min; Zhifang Xu; et al. (Journal of Meteorological Research, 2025)

A 3-Year Environmental Surveillance Reveals Multiple Enteroviruses Including Types A76, A89, A90 and C113 in Eastern China - Xiaojuan Lin; Mingyi Xu; Yonglin Han; Feng Ji; Suting Wang; Meng Chen; Mengmeng Wang; Aiqiang Xu; Zexin Tao (Food and Environmental Virology, 2025)

Observer-based robust preview control for tracking low Earth orbit targets of a 2.5-meter optical telescope with wind disturbance - Jueqi Lin; Weirui Chen; Zheng Wang; Xiaojun Zhou; Yu Han (Advances in Space Research, 2025)

Exploring biosynthetic potential of the endophytic Penicillium turbatum BLH34 using whole-genome sequence analysis and molecular networking - Xuejun Wang; Jun Chen; Han Lin; Changli Min; Li Zhang; Zhimou Gao (Natural Product Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Co-combustion reaction of corn stalk hydrochar and anthracite: Kinetics, mechanism and CO2 emission reduction - Wang Liang; Yihao Cui; Di Zhu; Yihan Chen; Yonghui Han; Lin Yue; Chunhe Jiang; Runsheng Xu; Xiaojun Ning; Jianliang Zhang; Chuan Wang; Guangwei Wang (Fuel, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

CRISPR CLAMP: Attomolar level of multiple miRNAs - Yiming Zhang; Zhi Chen; Songrui Wei; Jing Wang; Yujun Zhang; Huiling Lin; Hai Fu; Yingxia Liu; Qi Gao; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

When crop straw meets CO2-intensive process industries in China: The potential of CO2 mitigation and techno-economic analysis - Minjiao Chen; Peng Jiang; Meihua Li; Guanhan Zhao; Han Lin; Liwen Mu; Lee Chung Lau; Jiahua Zhu (Biomass and Bioenergy, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Mechanical response of broken surrounding rock by in-situ expansion of highway tunnel - Hongyun Yang; Jiang Gao; Yongchao Ding; Xiang Chen; Zhi Lin; Han Wu; Yongke Wei; Longwang Xu; Zhanfeng Yang (Bulletin of Engineering Geology and the Environment, 2025)

MiR-518b Promotes the Tumorigenesis of Hepatocellular Carcinoma by Targeting EGR1 to Regulate PI3K/AKT/mTOR Signaling Pathway - Xinyuan Wang; Juan Li; Jiao Nong; Xin Deng; Yiping Chen; Bing Han; Lin Zeng; Xiabing Huang (Cell Biochemistry and Biophysics, 2025)

A new collapse mechanism of RC frame structures under earthquakes: Shaking table tests and numerical analysis - Zhe Xu; Zi-Han Chen; Feng Lin (Soil Dynamics and Earthquake Engineering, 2025)

Spatially explicit land use of manufacturing sectors and its biodiversity impacts in China - Yutao Wang; Zhixiu Han; Yiru Song; Chen Sun; Lin Sun; Huajun Yu (Resources, Conservation and Recycling, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Long-term conservation tillage changes the diversity, assembly and network stability of soil diazotrophic community - Ling MA; Guixiang ZHOU; Jiabao ZHANG; Zhongjun JIA; Hongtao ZOU; Lin CHEN; Congzhi ZHANG; Donghao MA; Changdong HAN (Pedosphere, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Organic amendments enhance rhizosphere carbon stabilization in macroaggregates of saline-sodic soils by regulating keystone microbial clusters - Changdong Han; Lin Chen; Zhongjun Jia; Hongtao Zou; Ling Ma; Congzhi Zhang; Guixiang Zhou; Donghao Ma; Jiabao Zhang (Journal of Environmental Management, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

WTAP-mediated m6A modification of Hmgb2 contributes to spermatogenic damage induced by PM2.5 exposure - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Chaofeng Shi; Tong Wang; Lei Sun; Lin Ao; Fei Han; Qing Chen; Jia Cao; Jinyi Liu (Environmental Pollution, 2025)

Development and validation of deformation-dependent theoretical model for soil arching effect under unloading - Ren-Peng Chen; Xiang-Shen Fu; Qi-Wei Liu; Xiao-Hu Zhang; Han-Lin Wang (Computers and Geotechnics, 2025)

A reversible solar photothermal Li-CO2 battery enabled by engineering 3D plasmonic Cr-N-Ru catalysts assembled on carbon-free Si NP cathode - Shimin Chen; Junnan Han; Zhihuan Li; Zijie Lin; Min Wang; Hucheng Song; Xiaodong Pi; Dongke Li; Linwei Yu; Jun Xu; Kunji Chen (Chemical Engineering Journal, 2025)

Groundwater Level Prediction by Wavelet Deep Learning with Smart Pumping Data - Tsai-Ning Weng; Ray-Shyan Wu; Tzu-Han Weng; Yi-Ho Chen; Tsai-Chun Lai; Jui-Yun Hsieh; Chu-Chun Hsu; Yuan-Chien Lin (Water Resources Management, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Establishing electro-functionalized gravity-driven ceramic membrane filtration (EGDCM) for decentralized treatment of algae-laden brackish water: Comparison of in-situ electro-oxidation and ex-situ electro-coagulation - Dachao Lin; Xinxu Shen; Caiwei Tan; Han Zhang; Rui Chen; Xing Du; Heng Liang (Water Research, 2025)

Enhanced virulence of Acinetobacter johnsonii at low temperatures induces acute immune response and systemic infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Jingyang Sun; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Veterinary Microbiology, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Enhancing hexavalent chromium stable reduction via sodium alginate encapsulation of newly isolated fungal and bacterial consortia - Obey Kudakwashe Zveushe; Jackson Nkoh Nkoh; Víctor Resco de Dios; Tendai Terence Manjoro; Fidèle Suanon; Hengxing Zhang; Wenfang Chen; Lin Lin; Lei Zhou; Wei Zhang; Frank Sesu; Jin Li; et al. (Journal of Hazardous Materials, 2025)

Removal of ofloxacin and inhibition of antibiotic resistance gene spread during the aerobic biofilm treatment of rural domestic sewage through the micro–nano aeration technology - Bingbing Feng; Juan Chen; Chao Wang; Peifang Wang; Guoxiang You; Junkai Lin; Han Gao (Journal of Hazardous Materials, 2025)

Mechanical properties and microstructure of fly ash and slag-based geopolymer prepared by silica fume-based activator - Minguo Lin; Geng Chen; Yonghui Chen; Dandan Han; Ruobin Su; Jing Wu (Journal of Cleaner Production, 2025)

Simulated nitrogen deposition enhances resistance of female poplars over males to Pestalotiopsis microspora infection through the recruitment of antagonistic microbes in phyllosphere - Guoqing Zhu; Shuya Yang; Wanci He; Xiaotao Han; Lianghua Chen; Gang Chen; Tiantian Lin (Journal of Environmental Management, 2025)

Analysis of geothermal resources in the northeast margin of the Pamir plateau - Feng Chen; Jingyu Lin; Genyi He; Shuai Wang; Xuelian Huang; Boyuan Zhao; Sijia Wang; Yongjie Han; Shihua Qi (Geothermics, 2025)

Atmospheric black carbon (BC) in Hangzhou, China: Temporal variation, source apportionment, and case study of the 19th Asian Games - Jian Lin; Deming Han; Feng Chen; Xiaorong Zhang; Yang Yang; Lin Yang; Hua Guo; Zechen Yu; Liuyan Cao; Jianbo Shi; Guibin Jiang (Environmental Pollution, 2025)

Shrinkage and bending performance of trapezoidal wet joints in steel-UHPC composite decks - Han Xiao; Wei Wang; Chen Xu; Biao Ma; Zhiping Lin; Qingtian Su (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Improving the catalytic activity and sintering resistance of Ni-BaCe0.7Zr0.1Y0.1Yb0.1O3−δ cermet anode for ammonia-fueled protonic ceramic fuel cells via Cobalt addition - Bangze Wu; Xiaole Yu; Zenan Zhao; Bingyu He; Zhanheng Jin; Zhexiang Yu; Qing Ni; Shoucheng He; Han Chen; Yifeng Zheng; Sheng Cui; Lin Ge (Chemical Engineering Journal, 2025)

A bioengineered antibody conjugate reshape dendritic cell viability for immune-tolerance modulation - Xiaoqing Chen; Yalin Wang; Tao Xu; Han Liu; Xinya Ye; Peng Wang; Xiaojing Qin; Shiting Yang; Wenjing Ning; Hongye Zeng; Lin Xu; Mujin Fang; et al. (Chemical Engineering Journal, 2025)

Synthesis and antitumor activity of ultra-low molecular weight hyaluronic acid-decorated camptothecin conjugates - Changsheng Chen; Henan Zhang; Jingjun Han; Lin Yang; Shuang Li; Qingwen Jia; Junqiang Fang; Peixue Ling; Shuaishuai Wang (Carbohydrate Polymers, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Conservation tillage regulates the influence of drought on multitrophic network complexity and improves soil multifunctionality - Ling Ma; Guixiang Zhou; Lin Chen; Zhongjun Jia; Hongtao Zou; Congzhi Zhang; Donghao Ma; Changdong Han; Jiabao Zhang (Applied Soil Ecology, 2025)

Research on LSTM-PPO Obstacle Avoidance Algorithm and Training Environment for Unmanned Surface Vehicles - Wangbin Luo; Xiang Wang; Fang Han; Zhiguo Zhou; Junyu Cai; Lin Zeng; Hong Chen; Jiawei Chen; Xuehua Zhou (Journal of Marine Science and Engineering, 2025)
The current unmanned surface vehicle (USV) intelligent obstacle avoidance algorithm based on deep reinforcement learning usually adopts the mass point model to train in an ideal environment. However, in actual navigation, due to the influence of the ship model and the water surface environment, the training set is triggered. The reward function does not match the actual situation, resulting in a poor obstacle avoidance effect. In response to the above problems, this paper proposes a long and short memory network-proximal strategy optimization (LSTM-PPO) intelligent obstacle avoidance algorithm for non-particle models in non-ideal environments, and designs a corresponding deep reinforcement learning training environment. We integrate the motion characteristics of the unmanned boat and the influencing factors of the surface environment, based on the curiosity-driven set reward function, to improve its autonomous obstacle avoidance ability, combined with the LSTM network to identify and save obstacle information to improve the adaptability to the unknown environment; virtual simulation is performed in Unity. The engine builds a USV physical model and a refined water deep reinforcement learning training environment including a variety of obstacle models. The experimental results demonstrate that the LSTM-PPO algorithm exhibits an effective and rational obstacle avoidance effect, with a success rate of 86.7%, an average path length of 198.52 m, and a convergence time of 1.5 h. A comparison with the performance of three other deep reinforcement learning algorithms reveals that the LSTM-PPO algorithm exhibits a 21.5% reduction in average convergence time, an 18.5% reduction in average path length, and an approximately 20% enhancement in the success rate of obstacle avoidance in complex environments. These results indicate that the LSTM-PPO algorithm can effectively enhance the search efficiency and optimize the path planning in obstacle avoidance for unmanned boats, rendering it more rational.

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Selective complex leaching of Cu, Zn, and Cd from recycled copper smelting fly ash using NH3-NH4Cl system and kinetic analysis - Fan Lin; Tianya Lei; Jiancheng Shu; Mengjun Chen; Jibamu Duo; Xiangfei Zeng; Yunhui Han; Shaoqin Chen; Jiaming Chen; Weiping Huang; Jun Luo (Process Safety and Environmental Protection, 2025)

Unraveling carbon mineralization patterns and mechanisms in conservation agriculture: A global synthesis and multi-point experiment - Cong He; Jin-Sai Chen; Shou-Wei Han; Wen-Sheng Liu; Wen-Xuan Liu; Olatunde Pelumi Oladele; Yash Pal Dang; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Journal of Cleaner Production, 2025)

Degradation of anthracene and phenanthrene by strain Streptomyces sp. M-1 and its application in the treatment of PAHs-contaminated water - Zaimei Zhang; Hui Li; Han Han; Lijian Qin; Wei Lu; Lin Yue; Zongzhen Guo; Shengsong Gao; Shuang Chen; Huie Liu; Dong Wang; Jiqian Wang (Journal of Environmental Management, 2025)

Non-additive effects of leaf-litter flammability on eight subtropical tree species: Implications for forest species composition and fire susceptibility - Pujie Wei; Li Tang; Zixuan Xiong; Byron B. Lamont; Lin Chen; Weixing Xue; Zeyao Zhao; Wenxiong Lu; Jisi Han; Wanwan He; Wei Yang; Zhaogui Yan (Journal of Environmental Management, 2025)

Efficient photoelectrocatalytic degradation of tetracycline coupled with hydrogen production by N-doped carbon layer-wrapped TiO2 nanorods - Yan Li; Lili Yu; Jiayang Xie; Zilong Han; Haotong Chen; Zhiyuan Zhang; Zehao Lin; Li Li (Journal of Environmental Chemical Engineering, 2025)

Engineered silicon-titania heterojunction elicits catalytic cancer cell death - Deliang Xu; Tingting Xu; Min Ge; Shibo Cao; Zhaoda Yu; Zhixin Chen; Ya-Xuan Zhu; Zhuang Liu; Ming Zong; Han Lin; Jianlin Shi (Chemical Engineering Journal, 2025)

DTD1 modulates synaptic efficacy by maintaining D-serine and D-aspartate homeostasis - Xiao Liu; Chaojuan Yang; Zhuoran Lin; Jianing Li; Bin Yin; Xuepei Lei; Wei Han; Boqin Qiang; Pengcheng Shu; Chen Zhang; Xiaozhong Peng (Science China Life Sciences, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

A simple and efficient TALEN system for genome editing in plants - Qing Liu; Lizhou Lin; Shengjian He; Jianghui Yu; Caili Xie; Chaoyue Gai; Yongqiang Han; Chunmei Liu; Feihan Huang; Daoqian Chen; Yuanyuan Song; Guannan Qin; et al. (Plant Molecular Biology, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Grassland bud and shoot demographic responses to single and recurrent droughts vary across an aridity gradient - Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Yuan Shi; Lin Song; Jiaqi Chen; Hongqiang Wang; Jianqiang Qian; Qiang Yu; Zhengwen Wang; Xiaotao Lü; Xingguo Han; et al. (Ecology, 2025)
Clonal demographic traits play important roles in regulating community dynamics. Yet, it remains unclear how the responses of these clonal traits to drought might depend on previous drought exposure, and how drought responses vary among grasslands. We conducted a repeated drought experiment across four grasslands along an aridity gradient in northern China. We assessed the effects of single (precipitation reduction in 2021–2022) versus recurrent (precipitation reduction in 2015–2018 and 2021–2022) drought on bud density, shoot density, and the ratio of bud to shoot density. Drought reduced bud density at all grasslands and shoot density at most grasslands. Drought reduced the ratio of bud‐to‐shoot density only in the most arid grasslands. Recurrent drought had larger negative effects than a single drought on bud density and composition of bud and shoot at only one of four grasslands, and on shoot density at two of four grasslands. Our results suggest that previous drought exposure can alter the response of plant clonal demographic traits to subsequent drought in some but not all grasslands, and that responses can vary with mean climate.

Integrated transcriptomic and proteomic analysis unravels the response mechanisms of Saccharina japonica to heat stress - Zhongyuan Lin; Xuelian Liu; Jinbin Lin; Feng Lin; Yijuan Han; Huibin Xu; Hongmei Lin; Weiqi Tang; Yu Qin; Yanbing Zhu; Hui Ni; Jianjun Lu; et al. (Aquaculture, 2025)

Experimental investigation on the soil arching effect induced by deep-buried shield tunneling - Ren-Peng Chen; Xu Song; Fan-Yan Meng; Han-Lin Wang; Yang Liu; Lei Wen (Tunnelling and Underground Space Technology, 2025)

A bottom-up nationwide analysis of sectoral land use reveals spatial heterogeneity across the United States - Zhixiu Han; Wei Xie; Yiru Song; Lin Sun; Huajun Yu; Bin Chen; Yang Li; Yutao Wang (Resources, Conservation and Recycling, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Recent advances in natural gums as additives to help the construction and application of edible biopolymer gels: the example of hydrogels and oleogels - Wenbo Miao; Han Jiang; Xiaojing Li; Shangyuan Sang; Liming Jiang; Qianzhu Lin; Zhiheng Zhang; Long Chen; Jie Long; Aiquan Jiao; Jinpeng Wang; Zhengyu Jin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

Unveiling a novel mechanism: Reduction of graphene oxide by Lysinibacillus sp. through secretion of l-ascorbic acid - Yuanyuan Zhou; Ziyi Lin; Yonghe Han; Li Gan; Ying Cheng; Zuliang Chen (Chemosphere, 2024)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Influence of endophytic fungi treatments on aluminum contents in Vernicia montana seedlings and soils under different concentrations of aluminum stress - Qiaoyun Wu; Yaorui Zhang; Han Lin; Can Chen; Anqiang Xie; Hailan Fan (Rhizosphere, 2024)

A novel collaborative collision avoidance decision method for multi-ship encounters in complex waterways - Han Dong; Rong Zhen; Qiyong Gu; Zhong Lin; Jiuhu Chen; Kai Yan; Bing Chen (Ocean Engineering, 2024)

Long-term fallowing produces specific fungal taxa associated with soil carbon storage - Fang LI; Lin CHEN; Yue LI; Yanlai HAN; Yi WANG; Peipei LI; Shuiqing ZHANG; Jiabao ZHANG (Pedosphere, 2024)

Integration of multiple observations for validation of mechanisms of earthquake-triggered groundwater level Anomalies: 2016 Taiwan Meinong earthquake - Shih-Jung Wang; Yan-Yao Lin; Ying-Han Chen; Chia-Lin Chung; Wen-Chi Lai; Chien-Chung Ke (Journal of Hydrology, 2024)

Modulating charge transfer and constructing synergistic bimetallic active sites for CO-SCR reactions in inverse spinel - Qin Li; Xiaorong Han; Lin Tao; Qiuju Qin; Xuechi Du; Yuzhu Liang; Bin Li; Zhengjun Chen; Liya Zhou; Lihui Dong (Journal of Environmental Chemical Engineering, 2024)

Integrating a high-energy activation method for the sustainable treatment of iron smelting slag, phosphogypsum, and arsenic-contaminated water - Donghui Chen; Jie Tan; Hong Li; Yanmin Lin; Fangming Nan; Qingwen Han; Wei Zhan (Journal of Environmental Chemical Engineering, 2024)

Interaction of Kerguelen and Amsterdam-St. Paul dual hotspots with Southeast Indian Ridge - Yiming Luo; Jian Lin; Zhiyuan Zhou; Xubo Zhang; Fan Zhang; Jinchang Zhang; Han Chen (Earth and Planetary Science Letters, 2024)

Tracing the stepwise warming trend in the tropical Indian Ocean through a 40-year record of oxygen isotope composition in Maldives corals - Ke Lin; Tao Han; Kyle Morgan; Paul S. Kench; Yue-Gau Chen; Xianfeng Wang (Earth and Planetary Science Letters, 2024)

Peroxyacetic acid activated sulfite process: Generation of reactive species and degradation of β-lactam antibiotics - Yuchen Wang; Tao Lin; Han Chen (Chemical Engineering Journal, 2024)

Cation exchange strategy of ellagic acid-based microporous metal-organic framework for efficient CO2/N2 and CO2/CH4 separation - Chen-Ning Li; Zhi-Peng Tao; Lin Liu; Daqiang Yuan; Zheng-Bo Han (Chemical Engineering Journal, 2024)

Covalent metal–organic porous polymer on ZIF-67 realize anti-UV and highly stressed flame retardant epoxy composites - Jin Cao; Shangxian Chen; Zhengde Han; Ye-Tang Pan; Yichao Lin; Wei Wang; Rongjie Yang (Chemical Engineering Journal, 2024)

The source, transport, deposition and direct radiative effect of mineral dust over western China: A modeling study of July 2022 with focus on the Tibetan Plateau - Lin Liang; Zhiwei Han; Weiwei Chen; Jiawei Li; Mingjie Liang; Shujing Shen (Atmospheric Research, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

MST1R Gene Variants Predispose Individuals to Tetralogy of Fallot - Zhiyu Feng; Xianghui Huang; Yuan Gao; Han Gao; Weilan Na; Chaozhong Tan; Shaojie Min; Yuquan Lu; Quannan Zhuang; Siyi Lin; Xiaojing Ma; Weicheng Chen; et al. (Phenomics, 2024)
Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart malformation. While a few susceptibility genes for TOF have been identified, research on the genetic basis of TOF is limited. The Macrophage stimulating 1 receptor ( MST1R ) gene encodes the macrophage-stimulating protein receptor with tyrosine phosphatase activity that is involved in immune defense. In this study, we performed whole-exome sequencing (WES) on 10 TOF families and 50 sporadic TOF patients and identified a recessive homozygous missense mutation in MST1R , c.T2009G: p.V670G, in two offspring with TOF in a single family. Targeted sequencing of the MST1R gene showed enrichment for rare variants in 417 TOF patients compared with East Asians in Genome Aggregation Database Version 2 (gnomADv2_EAS). MST1R -deficient human induced pluripotent stem cells (hiPSCs) maintained normal pluripotency but differentiated into non-functional cardiomyocytes (CMs). Taken together, our findings indicate that MST1R may play a critical role in cardiac differentiation and genetic variations in MST1R may be associated with the pathogenesis of TOF.

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

The Temperature-Dependent Monotonic Mechanical Characteristics of Marine Sand–Geomembrane Interfaces - Zhiming Chao; Hongyi Zhao; Hui Liu; Peng Cui; Danda Shi; Hai Lin; Yang Lu; Bing Han; Shuang Chen (Journal of Marine Science and Engineering, 2024)
The utilization of geomembrane reinforcement technology is pervasive in marine sand foundation reinforcement projects. However, the elevated temperatures and intricate stress conditions prevalent in marine environments exert a notable influence on the mechanical characteristics of geomembrane interfaces comprising marine sand, which impedes the efficacy of geomembrane reinforcement in marine sand foundations. Nevertheless, there is a lack of research investigating the temperature-dependent interfacial mechanical performance of geomembranes and marine sand under diverse stress states. In this study, a series of monotonic shear tests were carried out on the interface between geomembranes and marine sand within a temperature range of 5 °C to 80 °C. These experiments were carried out using a self-developed large-scale temperature-controlled interfacial dynamic and static shear device. The experimental results demonstrate that temperature has a pronounced effect on the monotonic mechanical characteristics of the geomembrane–marine sand interface, which displays clear temperature dependence. The findings of this study may help in the design and optimization of offshore projects where a marine sand–polymer layer interface exists.

Comprehensive evaluation of the nephrotoxicity of carbon quantum dots: Effects of the surface charge - Pei-Luen Jiang; Yan-Yu Hong; Lingyan Yang; Han-Jia Lin; Chih-Ching Huang; Yan-Hua Chen; Chia-Hua Lin; Yi-Chun Chen (Chemosphere, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Dietary silicate minerals relieving cadmium or lead poisoning in juvenile sea cucumber, Apostichopus japonicus - Yi Chen; Shuchang Cui; Lin Wu; Yuzhe Han; Xiaoran Zhao; Tongjun Ren (Marine Environmental Research, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

Urban green vitalization and its impact on green exposure equity: A case study of Shanghai city, China - Hongkai Geng; Tao Lin; Ji Han; Yicheng Zheng; Junmao Zhang; Zixu Jia; Yuan Chen; Meixia Lin; Long Yu; Yukui Zhang (Journal of Environmental Management, 2024)

High-contrast electrochromic coatings and devices for health assurance, visual comfort and energy-saving in buildings - Chung-Wen Kuo; Han-Yu Chen; Chen-Hao Yeh; Yuan-Chung Lin; Jeng-Kuei Chang; Pei-Ying Lee; Tzi-Yi Wu (Energy and Buildings, 2024)

Oceanic response to tropical cyclone in the northern South China Sea observed by underwater gliders during 2018 and 2020 - Yanfeng Zhang; Han Zhang; Xiaodong Tang; Shaoqiong Yang; Yanhui Wang; Xiayan Lin; Di Tian; Dake Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Efficient nitrogen removal and stable operation of a dynamic membrane bioreactor (DMBR) for landfill leachate treatment - Jie Han; Wei Xu; Junjie Zhu; Xiaomei Su; Hailu Fu; Xiao Xiao; Feng Dong; Chongjun Chen; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2024)

Eu2+-activated hexagonal aluminate solid solution phosphors with high quantum efficiency and anti-thermal quenching for pc-LEDs - Yue Han; Mengfang Chen; Xiaochen Hu; Shuzhen Liao; Jiali Tang; Jiayuan Lin; Shixun Lian; Jilin Zhang (Chemical Engineering Journal, 2024)

Exploration and application of treating OSCC by a precisely concentrated synergistic agent in combination with thermally responsive release of effective therapeutic dosages of cisplatin - Shilin Guo; Tao Liu; Xinyuan Peng; Xinyu Zhang; Yangguang Li; Linzhong Yang; Wenguang Xu; Zheng Wei; Diya Xie; Lin Chen; Zichen Cao; Xiteng Yin; et al. (Chemical Engineering Journal, 2024)

Formation, migration, and removal mechanisms of PCDD/Fs throughout the temperature range (850°C–150°C) in a full-scale MSW incinerator: The invention of novel high-temperature PCDD/F sampling device - Pengju Wang; Feng Xie; Feng Yan; Xianfeng Jiao; Xuehua Shen; Heijin Chen; Han Lin; Hao Wu; Zuotai Zhang (Chemical Engineering Journal, 2024)

Anionic and cationic co-doping to enhance the oxygen transport property of Bi0.5Sr0.5FeO3-δ as a high-performance air electrode for reversible solid oxide cells - Hui Ye; Yixuan Feng; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng (Chemical Engineering Journal, 2024)

Enhancement of stress resistance of electroactive biofilms against hypersaline shock via exogenous electron mediator addition - Tao Li; Chen-ying Li; Han-lin Liang; Xiao-xue Li; Xiao-li Yang; Hua Li; Hai-liang Song (Chemical Engineering Journal, 2024)

Natural shading is helpful but not sufficient for mitigating warming in green sea turtle nests in the tropical South China Sea - Tsung-Han Liu; Ming-Shiou Jeng; Chan-Yuan David Lee; Chih-Wei Tu; Po-Hsiung Lin; Chaolun Allen Chen; Chia-Ying Ko (Biological Conservation, 2024)

Comparative study on environmental and economic assessment of straw heating across administrative areas scale of rural China - Tong Li; Guoxia Wei; Hanqiao Liu; Hailong Zhao; Yuwen Zhu; Yanfei Lin; Qianlong Han; Yifan Chen; Yanzhang Wang (The International Journal of Life Cycle Assessment, 2024)

Field performance of 15 rain gardens in different cities in Taiwan - Chi-Feng Chen; Yi-Wei Chen; Cheng-Han Lin; Jen-Yang Lin (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Bio-based tin phytate interface assembled bismuth oxychloride for enhanced flame retardancy and smoke suppression in polyvinyl chloride coatings - Feiyang Cheng; Xiangfeng Zhu; Bokun Lin; Chen Shi; Jian Han (Journal of Cleaner Production, 2024)

Determination of 3-nitropropionic acid in sugarcane using dispersive solid-phase extraction and gas chromatography–atmospheric pressure chemical ionization–tandem mass spectrometry - Zuolong Yu; Yu Lin; Xiujin Zhou; Yao Chen; Zhijin Yang; Chao Han; Yan Shen (Food Chemistry, 2024)

Supplementation with a phenolic-rich fraction from Ilex kudingcha improves inflammatory stress, gastrocnemius weights, and foreleg muscle grip strength in murine squamous cell carcinoma (SCC7)-bearing mice - Han-Chen Chao; Wan-Li Yang; Li-Wha Wu; Jin-Yuarn Lin (Food Bioscience, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Novel catalytic membrane based on γ-FeOOH@PVDF/peroxymonosulfate for efficient ammonia recovery: Self-cleaning mechanism and emerging organic contaminant degradation performance - Wucheng Ma; Chenfei Liu; Liang Zhu; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Shi Wang; Lin Chen; Yiping Li (Chemical Engineering Journal, 2024)

Developing fine-tuned MOF membranes for highly efficient separation and adsorption of chemical pollutant in water - Jiatong Han; Donghui Xu; Yanyan Huang; Yuwei Hua; Xin Ding; Zhihao Lin; Jie Zhou; Huan Lin; Ge Chen; Jing Wang; Xiaomin Xu; Jia Liu; et al. (Chemical Engineering Journal, 2024)

Joint regulation of the soil organic carbon accumulation by mineral protection and microbial properties following conservation practices - Changdong Han; Lin Chen; Zhongjun Jia; Hongtao Zou; Ling Ma; Biao Feng; Jingwang Li; Guixiang Zhou; Congzhi Zhang; Donghao Ma; Jiabao Zhang (CATENA, 2024)

Corrigendum to “An efficient approach for identifying important biomarkers for biomedical diagnosis” [Biosystems 237 (2024) 105163] - Jing-Wen Huang; Yan-Hong Chen; Frederick Kin Hing Phoa; Yan-Han Lin; Shau-Ping Lin (BioSystems, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

The role of rhamnolipids in the growth and defense responses of passion fruit plants - Ting Yang; Jihu Li; Yongkai Mao; Han Wu; Mingjiang Lin; Lijuan Chen (Physiology and Molecular Biology of Plants, 2024)

Allelopathy research on the continuous cropping problem of poplar (populus) - Tao Song; Jia-Xu Chen; Lin-Miao Shan; Yu-Chen Qian; Mo-Xian Chen; Jian-Gang Han; Fu-Yuan Zhu (Phytochemistry Reviews, 2024)

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

Identification of Floating Green Tide in High-Turbidity Water from Sentinel-2 MSI Images Employing NDVI and CIE Hue Angle Thresholds - Lin Wang; Qinghui Meng; Xiang Wang; Yanlong Chen; Xinxin Wang; Jie Han; Bingqiang Wang (Journal of Marine Science and Engineering, 2024)
Remote sensing technology is widely used to obtain information on floating green tides, and thresholding methods based on indices such as the normalized difference vegetation index (NDVI) and the floating algae index (FAI) play an important role in such studies. However, as the methods are influenced by many factors, the threshold values vary greatly; in particular, the error of data extraction clearly increases in situations of high-turbidity water (HTW) (NDVI > 0). In this study, high spatial resolution, multispectral images from the Sentinel-2 MSI mission were used as the data source. It was found that the International Commission on Illumination (CIE) hue angle calculated using remotely sensed equivalent multispectral reflectance data and the RGB method is extremely effective in distinguishing floating green tides from areas of HTW. Statistical analysis of Sentinel-2 MSI images showed that the threshold value of the hue angle that can effectively eliminate the effect of HTW is 218.94°. A test demonstration of the method for identifying the floating green tide in HTW in a Sentinel-2 MSI image was carried out using the identified threshold values of NDVI > 0 and CIE hue angle 0), resulting in better consistency of the identification of the floating green tide and its distribution in the true color image. The method enables rapid and accurate extraction of information on floating green tide in HTW, and offers a new solution for the monitoring and tracking of green tides in coastal areas.

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

Investigation on the induced electrical wakes generated by underwater vehicles - Qing Chen; Yimin Xuan; Qunqing Lin; Yuge Han; Kai Wei (Ocean Engineering, 2024)

Fabrication and characterization of polydopamine-mediated zein-based nanoparticle for delivery of bioactive molecules - Zhiheng Zhang; Han Jiang; Guo Chen; Wenbo Miao; Qianzhu Lin; Shangyuan Sang; David Julian McClements; Aiquan Jiao; Zhengyu Jin; Jinpeng Wang; Chao Qiu (Food Chemistry, 2024)

Cryopreservation-enhanced differentiation capacity of embryogenic cultures of Castanea mollissima - Shuangxian Liu; Liang Lin; Biao Han; Junchao Ma; Hugh W. Pritchard; Xiaojian Hu; Min Deng; Hongying Chen (Cryobiology, 2024)

A systematic investigation of PVDF-HFP in perovskite solar cells for improved space mission reliability - Seoungjun Ahn; Wei-Hao Chiu; Wei-Chen Chu; Pei-Yu Chen; Ting-Han Lin; Kun-Mu Lee (Chemical Engineering Journal, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Co-Al hydrotalcite assembled nanofibers to enhance corrosion inhibition and effective Cl− adsorption for long-term corrosion protection - Lin Cao; Jinming Piao; Wei Wang; Weijie Fan; Dongxiao Han; Yantong Pei; Ye Chen; Yue Zhang (Chemical Engineering Journal, 2024)

Evaluation of the anti-atherosclerotic effect for Allium macrostemon Bge. Polysaccharides and structural characterization of its a newly active fructan - Pei Lin; Qiqi Wang; Qi Wang; Jiayun Chen; Liangliang He; Zifei Qin; Shaoping Li; Jingyan Han; Xinsheng Yao; Yang Yu; Zhihong Yao (Carbohydrate Polymers, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Anisotropy measurements and characterization of the Qingshankou shale - Qing-feng Li; Xue-hong Yan; Wei-lin Yan; Li Ren; Peng Wang; Jian-qiang Han; Xue Xia; Hao Chen (Applied Geophysics, 2024)

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Multiscale coupling analysis and modeling of airflow and heat transfer for warehouse-packaging-kiwifruit under forced-air cooling - Qian Chen; Jianping Qian; Han Yang; Jiali Li; Xintao Lin; Baogang Wang (Biosystems Engineering, 2024)

Core microbial taxonomies that maintain high organic carbon content in upland soil - Fang Li; Lin Chen; Zhongjun Jia; Jiabao Zhang; Zhanhui Zhao; Yanlai Han; Yi Wang (Science of The Total Environment, 2024)

Evaluating the effect of Multi-Scale droughts on autumn phenology of global land biomes with satellite observation - Ronglei Zhou; Yangyang Liu; Xueqing Wang; Xu Chen; Gaohui Duan; Peidong Han; Ziqi Lin; Haijing Shi; Zhongming Wen (Journal of Hydrology, 2024)

Selective catalytic oxidation of DMF over Cu-Ce/H-MOR by modulating the surface active sites - Hua-Hui Xu; Yi-Wei Xian; Xi Zhao; Lin-Ya Xu; Cai-Hao Wen; Han Zhao; Cen Tang; Wen-Zhi Jia; Meng-Fei Luo; Jian Chen (Journal of Hazardous Materials, 2024)

A novel EGCG-Histidine complex improves gelling and physicochemical properties of porcine myofibrillar proteins: Insight into underlying mechanisms - Xiao Guo; Renzheng Wang; Bofu Han; Wei Shao; Lin Chen; Xianchao Feng (Food Chemistry, 2024)

Comprehensive comparison of aroma profiles and chiral free and glycosidically bound volatiles in Fujian and Yunnan white teas - Han Yan; Wei-Xuan Li; Ying-Lin Zhu; Zhi-Yuan Lin; Dan Chen; Yue Zhang; Hai-Peng Lv; Wei-Dong Dai; De-Jiang Ni; Zhi Lin; Yin Zhu (Food Chemistry, 2024)

A novel explainable kinetic model for two-stage fermentation profile - Xiao-Yan Huang; Chen-Guang Liu; Yen-Han Lin (Chemical Engineering Journal, 2024)

Online monitoring lignocellulosic particles by focus beam reflectance measurement for efficient bioprocessing - Ji-Wen Yao; Xiao-Yan Huang; Yen-Han Lin; Chen-Guang Liu; Feng-Wu Bai (Bioresource Technology, 2024)

The role of galectins in the regulation of autophagy and inflammasome in host immunity - Tzu-Han Lo; I-Chun Weng; Hung-Lin Chen; Fu-Tong Liu (Seminars in Immunopathology, 2024)

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

A leaf age‐dependent light use efficiency model for remote sensing the gross primary productivity seasonality over pantropical evergreen broadleaved forests - Jie Tian; Xueqin Yang; Wenping Yuan; Shangrong Lin; Liusheng Han; Yi Zheng; Xiaosheng Xia; Liyang Liu; Mei Wang; Wei Zheng; Lei Fan; Kai Yan; et al. (Global Change Biology, 2024)
Tropical and subtropical evergreen broadleaved forests (TEFs) contribute more than one‐third of terrestrial gross primary productivity (GPP). However, the continental‐scale leaf phenology‐photosynthesis nexus over TEFs is still poorly understood to date. This knowledge gap hinders most light use efficiency (LUE) models from accurately simulating the GPP seasonality in TEFs. Leaf age is the crucial plant trait to link the dynamics of leaf phenology with GPP seasonality. Thus, here we incorporated the seasonal leaf area index of different leaf age cohorts into a widely used LUE model (i.e., EC‐LUE) and proposed a novel leaf age‐dependent LUE model (denoted as LA‐LUE model). At the site level, the LA‐LUE model (average R 2 = .59, average root‐mean‐square error [RMSE] = 1.23 gC m −2 day −1 ) performs better than the EC‐LUE model in simulating the GPP seasonality across the nine TEFs sites (average R 2 = .18; average RMSE = 1.87 gC m −2 day −1 ). At the continental scale, the monthly GPP estimates from the LA‐LUE model are consistent with FLUXCOM GPP data ( R 2 = .80; average RMSE = 1.74 gC m −2 day −1 ), and satellite‐based GPP data retrieved from the global Orbiting Carbon Observatory‐2 (OCO‐2) based solar‐induced chlorophyll fluorescence (SIF) product (GOSIF) ( R 2 = .64; average RMSE = 1.90 gC m −2 day −1 ) and the reconstructed TROPOspheric Monitoring Instrument SIF dataset using machine learning algorithms (RTSIF) ( R 2 = .78; average RMSE = 1.88 gC m −2 day −1 ). Typically, the estimated monthly GPP not only successfully represents the unimodal GPP seasonality near the Tropics of Cancer and Capricorn, but also captures well the bimodal GPP seasonality near the Equator. Overall, this study for the first time integrates the leaf age information into the satellite‐based LUE model and provides a feasible implementation for mapping the continental‐scale GPP seasonality over the entire TEFs.

Deformation characteristics and stability analysis of lean clay under cyclic loading - Han-Lin Wang; Yue-Hui Sun; Ren-Peng Chen; Chun-Yin Peng; Askar Khasanov (Transportation Geotechnics, 2024)

Upward soil arching effect under unloading: mechanism, theory and engineering application - Ren-Peng Chen; Han-Lin Wang; Xiang-Shen Fu; Fanyan Meng; Qi-Wei Liu; Xing-Tao Lin (Transportation Geotechnics, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Optimized DLP 3D-printed high-resolution nano zirconia-hydroxyapatite scaffold with craniomaxillofacial soft tissue invasion resistance and pro-osteogenic properties via dectin-1/syk inflammatory axis - Xiaomeng Gao; Jieting Yang; Xuejing Gan; Yixiong Lin; Jieyun Xu; Zhengjie Shan; Zongpu Han; Shijie Chen; Baoxin Huang; Bingfeng Fan; Zetao Chen (Chemical Engineering Journal, 2024)

Soil organic carbon storage, microbial abundance and pore structure characteristics of macroaggregates across a soil-landscape sequence in a subtropical hilly watershed - Zheng Zhao; Xiao Feng; Chun Liu; Yue Han; Guogang Long; Shuotong Chen; Qingmei Lin; Jingwen Gong; Yi Shen; Ziyi Mao; Thammavongsa Sounilan; Xuhui Zhang; et al. (CATENA, 2024)

Cyclodextrin-based ternary supramolecular deep eutectic solvents for efficient extraction and analysis of trace quinolones and sulfonamides in wastewater by adjusting pH - Jingyu Zhang; Shang Li; Liping Yao; Yulin Han; Kexian Chen; Mingrong Qian; Zuguang Li; Hui Lin (Analytica Chimica Acta, 2024)

Different microbial functional traits drive bulk and rhizosphere soil phosphorus mobilization in an alpine meadow after nitrogen input - Bing Han; Yicheng He; Ji Chen; Yufei Wang; Lina Shi; Zhenrong Lin; Lu Yu; Xiaoting Wei; Wantong Zhang; Yiyi Geng; Xinqing Shao; Shangang Jia (Science of The Total Environment, 2024)

Dynamic analysis of lift-off operation of offshore wind turbine jacket foundation from the transportation barge - Mingsheng Chen; Guibo Yuan; Bin Li; Chun Bao Li; Mingjun Ouyang; Lin Li; Wei Shi; Zhaolong Han; Wei Zhang; Ziwen Chen (Ocean Engineering, 2024)

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

Salinity influence on adsorption of lipid molecules in clay minerals: Results from experiments and calculations - Xiao Gao; Zuozhen Han; Gang Zhou; Lin Li; Xiaowei Lyu; Yanyang Zhao; Wenjie Chen; Zhenhua Qi; Fang Liu; Qingqiang Meng; Michael Steiner; Chao Han (Journal of Environmental Chemical Engineering, 2024)

BmNPV p35 regulates apoptosis in Bombyx mori via a novel target of interaction with the BmVDAC2-BmRACK1 complex - Lin-Bao Zhu; Han-Dan Zhu; Zhi-Hao Huang; Hui-Hua Cao; Sadaf Ayaz; Jia-Yue Yang; Xi-Ya Chen; Ying Zhang; Shi-Huo Liu; Jia-Ping Xu (Insect Biochemistry and Molecular Biology, 2024)

Does soil nutrient heterogeneity affect the competition and adaptation of Vernicia montana? - Yunlong Pan; Yue Fan; Can Chen; Han Lin (Forest Ecology and Management, 2024)

Extending the freshness of tilapia surimi with pulsed electric field modified pea protein isolate-EGCG complex - Zhong Han; Ze-Ling Chen; Xin-Dong Xu; Songyi Lin; Yan Wang; Lang-Hong Wang; De-Bao Niu; Xin-An Zeng; Meng-Wai Woo; Ruo-Yong Wang (Food Hydrocolloids, 2024)

Effects of adding Bacillus subtilis natto NTU-18 in paste feed on growth, intestinal morphology, gastrointestinal microbiota diversity, immunity, and disease resistance of Anguilla japonica glass eels - Yen-Ting Lin; Yu-Chen Hung; Li-Han Chen; Kung-Ta Lee; Yu-San Han (Fish & Shellfish Immunology, 2024)

Phosphine oxide balanced charge transfer hybridization in multi-resonance emitters: towards ∼40% external quantum efficiency and preserved color purity - Su Chen; Yidan Wang; Jincheng Lin; Rundong Tian; Shuang Li; Yi Man; Shuo Chen; Jing Zhang; Chunbo Duan; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Arbuscular mycorrhizal fungal diversity associated with an endangered species, Chamaecyparis formosensis, in the nature habitat - Tzu-Chao Lin; Wan-Rou Lin; Lei-Chen Lin; Pi-Han Wang (Tropical Ecology, 2024)

Metabolomic profiling of maternal plasma identifies inverse associations of acetate and urea with anti-SARS-CoV-2 antibody titers following COVID-19 vaccination during pregnancy - An-Shine Chao; Chiao-Yun Lin; Meng-Han Chiang; Kuan-Ying Lu; Cheng-Kun Tsai; Kuan-Ju Chen; Chih-Wei Chien; Ting-Shu Wu; Yao-Lung Chang; Angel Chao; Gigin Lin; Chih-Yung Chiu (Journal of Molecular Medicine, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Change in rate of healthcare encounters for respiratory infection from air pollution exposure after improved vehicle emissions standards in New York State - Daniel P. Croft; Mark J. Utell; Han Liu; Shao Lin; Philip K. Hopke; Sally W. Thurston; Yunle Chen; David Q. Rich (Air Quality, Atmosphere & Health, 2024)
The introduction of Tier 3 light-duty vehicles with reduced emissions began in New York State (NYS) in 2017, with required compliance by 2025. We hypothesized that improved air quality during the early implementation of Tier 3 (2017–2019) would result in reduced rates of hospitalizations and emergency department (ED) visits for respiratory infection associated with increased PM 2.5 compared to 2014–2016 (pre-Tier 3). Using data on adult patients hospitalized or having an ED visit for influenza, upper respiratory infection, culture-negative pneumonia, or respiratory bacterial infection, living within 15 miles of six air quality monitoring sites in NY, and a case-crossover design and conditional logistic regression, we estimated the rates of respiratory infection hospitalizations and ED visits associated with increased ambient PM 2.5 concentrations in the previous 0–6 days and each week thereafter up to 1 month. Interquartile range (IQR) increases in PM 2.5 in the previous 6 days were associated with 4.6% (95% CI: − 0.5, 10.1) and 11.9% (95% CI = 6.1, 18.0) increased rates of influenza hospitalizations in 2014–2016 and 2017–2019, respectively. This pattern of larger relative rates in 2017–2019 observed at all lag times was only present in males hospitalized for influenza but not other infections or in females. The rates of respiratory infection visits associated with increased PM 2.5 were generally not reduced in this early Tier 3 implementation period compared to 2014–2016. Limited fleet penetration of Tier 3 vehicles and differences in particle deposition, infection type, and sex by period may all have contributed to this lack of improvement.

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Identification of SNPs and candidate genes associate with growth performance in all-female mandarin fish (Siniperca chuatsi) by a genome-wide association study - Dingrui Liu; Jin Zhang; Zhenjiang Zou; Chen Long; Jiaqi Lin; Junyan Zeng; Jingpeng Hou; Linqiang Han; Yanlin Jiang; Shuisheng Li; Yong Zhang (Aquaculture, 2024)

Unlocking the secrets of Qingzhuan tea: A comprehensive overview of processing, flavor characteristics, and health benefits - Panpan Liu; Lin Feng; Jia Chen; Shengpeng Wang; Xueping Wang; Yanna Han; Mengjun Ma; Zhonghua Liu; Pengcheng Zheng (Trends in Food Science & Technology, 2024)

Ilex kudingcha’s phenolic-rich fraction inhibits murine squamous cell carcinoma (SCC7) through restoring adaptive immunity and Th1-polarized immune balance in vitro and in vivo - Han-Chen Chao; Li-Wha Wu; Jin-Yuarn Lin (South African Journal of Botany, 2024)

Bioenzyme–nanoenzyme–chromogen all-in-one test strip for convenient and sensitive detection of malathion in water environment - Hanwen Zhang; Jiabin Jin; Xini Wang; Wei Han; Lei Qin; Lin Chen; Xiaoyan Mao; Zhenjiang Liu; Xingwei Xiang (Science of The Total Environment, 2024)

Long-term PM1 exposure and hypertension hospitalization: A causal inference study on a large community-based cohort in South China - Yuqin Zhang; Shirui Chen; Jing Wei; Jie Jiang; Xiao Lin; Ying Wang; Chun Hao; Wenjing Wu; Zhupei Yuan; Jie Sun; Han Wang; Zhicheng Du; et al. (Science Bulletin, 2024)

Dynamic response and performance assessment of subsea sandwich pipelines with different interlayer subjected to underwater explosion - Hong Lin; Hao Xu; Lei Yang; Pingping Han; Shuo Zhang; Longcheng Wei; Guoming Chen (Process Safety and Environmental Protection, 2024)

Investigation of dry environment construction Equipment's medium displacement system for submarine pipelines - Kaichuang Wang; Jiawang Chen; Jian Huang; Peiwen Lin; Jin Guo; Hai Zhu; Yuping Fang; Xuehua Chen; Guomin Cao; Wenbao Jia; Xu Gao; Han Ge (Ocean Engineering, 2024)

Changes in preferential flow caused by root effects in black locust plantations of different stand ages in the semi-arid region of the Loess Plateau - Lu Cai; Fei Wang; Yuanyuan Lin; Qi Long; Yulong Zhao; Jianqiao Han; Wenyan Ge; Hao Chen (Journal of Hydrology, 2024)

Advanced oxidation process/coagulation coupled with membrane distillation (AOP/Coag-MD) for efficient ammonia recovery: Elucidating biofouling control performance and mechanism - Wucheng Ma; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Lin Chen; Liang Zhu (Journal of Hazardous Materials, 2024)

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Super absorbent resilience antibacterial aerogel with curcumin for fresh pork preservation - Fangqu Wang; Zipeng Xu; Lin Chen; Ziyan Qiao; Yayun Hu; Xiaojing Fan; Yaping Liu; Zhuangli Kang; Feng Huang; Minyi Han; Huijuan Yang; Xianchao Feng (Food Control, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

An antibacterial membrane based on Janus bacterial cellulose with nano-sized copper oxide through polydopamine conjugation for infectious wound healing - Bing Han; Fan Liu; Shuhang Hu; Xinyu Chen; Chenming Lin; In-Seop Lee; Cen Chen (Carbohydrate Polymers, 2024)

Genome-wide characterization of SmZHD gene family and the role of SmZHD12 in regulating anthocyanin biosynthesis in eggplant (Solanum melongena L.) - Qian Chen; XinQin Liu; Han Zhang; JinDi Wang; Lin Du; ZiWei Zhao; ShaoHang Li; YongJun He (Plant Cell Reports, 2024)

Fast and efficient As(III) removal from water by bifunctional nZVI@NBC - Jiuwan Wang; Mengfan Chen; Yulian Han; Congting Sun; Ying Zhang; Shuyan Zang; Lin Qi (Environmental Geochemistry and Health, 2024)

Impact of changes in biofilm composition response following chlorine and chloramine disinfection on nitrogenous disinfection byproduct formation and toxicity risk in drinking water distribution systems - Songyuan Zheng; Tao Lin; Han Chen; Xue Zhang; Fuchun Jiang (Water Research, 2024)

Decreased snow depth inhibits litter decomposition via changes in litter microbial biomass and enzyme activity - Ting Du; Li Zhang; Yulian Chen; Yu Zhang; Hemeng Zhu; Zhenfeng Xu; Bo Tan; Chengming You; Yang Liu; Lixia Wang; Sining Liu; Hongwei Xu; et al. (Science of The Total Environment, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

Whole-genome sequencing of Escherichia coli from retail meat in China reveals the dissemination of clinically important antimicrobial resistance genes - Qin Wang; Ying-Yue Han; Tie-Jun Zhang; Xuan Chen; Heng Lin; Hong-Ning Wang; Chang-Wei Lei (International Journal of Food Microbiology, 2024)

Ofloxacin weakened treatment performance of rural domestic sewage in an aerobic biofilm system by affecting biofilm resistance, bacterial community, and functional genes - Bingbing Feng; Juan Chen; Chao Wang; Guoxiang You; Junkai Lin; Han Gao; Shanrui Han; Junchao Ma (Environmental Research, 2024)

Ascertaining sensitive exposure biomarkers of various metal(loid)s to embryo implantation - Mengyuan Ren; Tianxiang Wu; Shuo Yang; Ning Gao; Changxin Lan; Han Zhang; Weinan Lin; Shu Su; Lailai Yan; Lili Zhuang; Qun Lu; Jia Xu; et al. (Environmental Pollution, 2024)

Multifunctional enhanced energy density of flexible wide-temperature supercapacitors based on MXene/PANI conductive hydrogel - Lin Han; Yueqin Li; Chen Chen; Lingke Liu; Zichun Lu (Chemical Engineering Journal, 2024)

Chemical composition, sources, and processes of winter haze in Chengdu, China: Insights from integrating the bulk chemical and single particle approaches - Junke Zhang; Wei Sun; Yunfei Su; Xiaoxue Peng; Chunying Chen; Xinyi Fu; Yuhan Long; Gehui Wang; Zhihan Rao; Lin Han; Xiaojuan Huang (Atmospheric Environment, 2024)

Alternation of social behaviors for zebrafish (Danio rerio) in response to acute cold stress - Sian-Tai Liu; Chun-Yung Chang; Kuang-Yung Lee; Sok-Keng Tong; Han-Liang Huang; Hsi Chen; Jiun-Lin Horng; Ming-Yi Chou (Fish Physiology and Biochemistry, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Nutritional and physiological responses of female and male largemouth bass (Micropterus salmoides) to different dietary starch levels - Han Huang; Xianping Tian; Haijie Chen; Ruisheng Liao; Yuanfa He; Yongjun Chen; Zhijian Wang; Shimei Lin (Aquaculture, 2024)

Settlement transfer mechanism of CFG piles for strengthening high-speed railway subgrades induced by twin shield tunnelling undercrossing - Beiyu Wu; Xing-Tao Lin; Dong Su; Kaihang Han; Xiangsheng Chen (Tunnelling and Underground Space Technology, 2024)

PM2.5 air quality and health gains in the quest for carbon peaking: A case study of Fujian Province, China - Yahui Bian; Xiaobo Huang; Shuifa Lin; Hui Han; Jinsheng Chen; Jianyi Lin; Xinxin Ye (Science of The Total Environment, 2024)

Long-term conservation tillage enhances microbial carbon use efficiency by altering multitrophic interactions in soil - Ling Ma; Guixiang Zhou; Jiabao Zhang; Zhongjun Jia; Hongtao Zou; Lin Chen; Congzhi Zhang; Donghao Ma; Changdong Han; Yan Duan (Science of The Total Environment, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

New modifications of PBAT by a small amount of oxalic acid: Fast crystallization and enhanced degradation in all natural environments - Qingyang Luan; Han Hu; Xingyu Ouyang; Xiaoyu Jiang; Chen Lin; Hanxu Zhu; Ting Shi; Yi-Lei Zhao; Jinggang Wang; Jin Zhu (Journal of Hazardous Materials, 2024)

UV-induced photodegradation of emerging para-phenylenediamine quinones in aqueous environment: Kinetics, products identification and toxicity assessments - Wei Wang; Guodong Cao; Jing Zhang; Han Qiao; Huankai Li; Biwei Yang; Yanyan Chen; Lin Zhu; Yuecheng Sang; Lei Du; Zongwei Cai (Journal of Hazardous Materials, 2024)

Mitigating heavy metal volatilization during thermal treatment of MSWI fly ash by using iron(III) sulfate as a chlorine depleting agent - Siyu Han; Kailun Chen; Fanzhi Meng; Yuchen Gao; Jinglin Li; Li Lin; Weikai Qin; Jianguo Jiang (Journal of Hazardous Materials, 2024)

Aboveground plants determine the exchange of pathogens within air-phyllosphere-soil continuum in urban greenspaces - Changyi Lu; Zufei Xiao; Hu Li; Ruixia Han; Anqi Sun; Qian Xiang; Zhe Zhu; Gang Li; Xiaoru Yang; Yong-Guan Zhu; Qing-Lin Chen (Journal of Hazardous Materials, 2024)

Well plate-based LF-NMR/colorimetric dual-mode homogeneous immunosensor for Vibrio parahaemolyticus detection - Dongyu Zhang; Le Chen; Han Lin; Tingting Hao; Yangbo Wu; Jianjun Xie; Xizhi Shi; Xiaohua Jiang; Zhiyong Guo (Food Chemistry, 2024)

A comprehensive evaluation of milk protein molecular weight distribution based on exclusion chromatography dataset - Yu Liu; Xiao-Yan Li; Ling Li; Yu-Qi Yin; Han-Lin Zhang; Kun-Long Wang; Jie Zhou; Yun Chen; Ying-Hua Zhang (Food Chemistry, 2024)

An efficient approach for identifying important biomarkers for biomedical diagnosis - Jing-Wen Huang; Yan-Hong Chen; Frederick Kin Hing Phoa; Yan-Han Lin; Shau-Ping Lin (BioSystems, 2024)

Triphenyl phosphate exposure impairs colorectal health by altering host immunity and colorectal microbiota - Changchun Ye; Zilu Chen; Wenhao Lin; Zepeng Dong; Jie Han; Jingyi Zhang; Xueqian Ma; Junhui Yu; Xuejun Sun; Ying Li; Jianbao Zheng (Chemosphere, 2024)

Acute septicemia and diagnostic evaluation of Aeromonas veronii infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Guilian Zeng; Yebing Yu; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2024)

Prediction of thermal conductivities of insulation materials under water immersion and freeze–thaw conditions for tunnels in cold regions - Fenglei Han; Zonghan Liu; Jiazheng Li; Wenbing Yu; Qixiang Yan; Yuanfu Zhou; Shuzhen Zhang; Lin Chen (Tunnelling and Underground Space Technology, 2024)

Biochemical, histological and transcriptomic analyses for the immunological organs provide insights into heat stress-induced disease susceptibility in Largemouth Bass - Zhicheng Xv; Shaoxiong Chen; Guili Song; Han Hu; Shimei Lin; Yong Long (Science of The Total Environment, 2024)

Impacts of seasonal variation on volatile fatty acids production of food waste anaerobic fermentation - Weikai Qin; Siyu Han; Fanzhi Meng; Kailun Chen; Yuchen Gao; Jinglin Li; Li Lin; Endian Hu; Jianguo Jiang (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

The ability of energy commodities to hedge the dynamic risk of epidemic black swans - I-Chun Tsai; Han-Bo Chen; Che-Chun Lin (Resources Policy, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Mathematical modeling of pickling of bamboo shoot strips and their sulfur dioxide removal during cooking - Chien-Lin Chen; Jheng-Han Tsai; Yeun-Chung Lee; Jen-Yi Huang (Journal of Food Engineering, 2024)

Magnetic biochar enhanced copper immobilization in agricultural lands: Insights from adsorption precipitation and redox - Wucheng Ma; Rui Han; Wei Zhang; Hao Zhang; Lin Chen; Liang Zhu (Journal of Environmental Management, 2024)

Influence of inertinite on coal physicochemical thermal transformation properties and liquefaction behaviors - Wenchao Qian; Chunyang Yan; Xiaoyin Mu; Jiahao Chen; Lulu Cui; Hualin Lin; Sheng Han; Zongqing Bai (Fuel, 2024)

ZrO2-MoO3/modified lotus stem biochar catalysts for catalytic aquathermolysis of heavy oil at low-temperature - Yiya Wang; Riyi Lin; Liqiang Zhang; Xinlu Han; Jinyu Li; Chenxing Huang; Qiwei Dong; Pengyu Chen; Huanan Li; Xinwei Wang (Fuel, 2024)

Fermented Syzygium samarangense leaves mitigate oxidative stress-triggered hepatotoxicity through Nrf2 activation and epigenetic regulation - Ssu-Han Huang; Zi-Han Lin; Tien-Yuan Wu; Guor-Jien Wei; Yen-Chen Tung; Zheng-Yuan Su (Food Bioscience, 2024)

Maternal serum neonicotinoids during early-mid pregnancy and congenital heart diseases in offspring: An exploratory study - Yanji Qu; Adela Jing Li; Xiaoqing Liu; Shao Lin; Michael S. Bloom; Ximeng Wang; Xiaohong Li; Hui Wang; Fengzhen Han; Xiangmin Gao; Yong Wu; Kaiqin Huang; et al. (Environmental Pollution, 2024)

A digital platform for One-Pot signal enhanced foodborne pathogen detection based on mesophilic argonaute-driven polydisperse microdroplet reactors and machine learning - Junping Wen; Minjie Han; Niu Feng; Guoxun Chen; Feng Jiang; Jianhan Lin; Yiping Chen (Chemical Engineering Journal, 2024)

Diisobutylamine mediated CO2 mineralization and CaCO3 production from municipal solid waste incineration fly ash as raw ingredient and regeneration reagent - Kailun Chen; Siyu Han; Fanzhi Meng; Li Lin; Jinglin Li; Yuchen Gao; Weikai Qin; Endian Hu; Jianguo Jiang (Chemical Engineering Journal, 2024)

Chemical constituents from the stem of Ficus pumila - Wen-Lin Xiao; Wen-Hao Chen; Wei Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2024)

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

Emergence of OXA-48-producing hypervirulent Klebsiella pneumoniae strains in Taiwan - Yi-Tsung Lin; Chien Chuang; Sheng-Hua Chou; Chih-Han Juan; Tsuey-Ching Yang; Barry N. Kreiswirth; Liang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Long-term fertilization affects microbial necromass accumulation by regulating nutrient and enzymatic stoichiometry in a calcareous Fluvisol - Changdong Han; Lin Chen; Xiuli Xin; Guixiang Zhou; Congzhi Zhang; Donghao Ma; Yue Li; Ling Ma; Jiabao Zhang (Applied Soil Ecology, 2024)

Investigating the diurnal effects of on-street population and streetscape physical environment on street theft crime: A machine learning and negative binomial regression approach using street view images - Han Yue; Lin Liu; Chong Xu; Guangwen Song; Jianguo Chen; Li He; Lian Duan (Applied Geography, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Spatial patterns of light response parameters and their regulation on gross primary productivity in China - Yong Lin; Zhi Chen; Guirui Yu; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Wenxing Luo (Agricultural and Forest Meteorology, 2024)

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

Linkage analysis for water-energy-economic system efficiency in China - Zhong Fang; Yung-ho Chiu; Yiqin Chen; Tai-Yu Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2024)

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

Fabrication and performance of novel multifunctional sodium alginate/polyvinylpyrrolidone hydrogels - Deli Lu; Chen Liu; Fengtian Zhu; Ying Liu; Yushi Lin; Qidong Yang; Sheng Han (Chemosphere, 2024)

Hydrological connectivity controls on the dynamics of particulate organic matter in a semi-enclosed mariculture bay - Aiqin Han; Jin-Yu Terence Yang; Mengli Chen; Zhenzhen Zheng; Xijie Yin; Hui Lin; Min Nina Xu; Shuh-Ji Kao (Aquaculture, 2024)

Effect of human chorionic gonadotrophin (HCG) and luteinizing hormone releasing hormone A3 (LHRH-A3) on reproduction and development of brood pouch in Hippocampus erectus - Xuange Liu; Gongpei Wang; Jiahui Chen; Sheng Bi; Chenlei Huang; Han Lai; Huadong Yi; Haiyang Li; Qiuxian Chen; Li Lin; Zhilun Zhang; Xuchong Wei; et al. (Aquaculture, 2024)

Singlet oxygen-mediated fluconazole degradation during the activation of chlorine dioxide with sulfite - Feiyu Lu; Tao Lin; Han Chen (Water Research, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Acid controlled washing of municipal solid waste incineration fly ash: Extraction of calcium inhibiting heavy metals and reaction kinetics - Kailun Chen; Siyu Han; Fanzhi Meng; Li Lin; Jinglin Li; Yuchen Gao; Weikai Qin; Jianguo Jiang (Science of The Total Environment, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Water stress significantly affects the diurnal variation of solar-induced chlorophyll fluorescence (SIF): A case study for winter wheat - Jingyu Lin; Litao Zhou; Jianjun Wu; Xinyi Han; Bingyu Zhao; Meng Chen; Leizhen Liu (Science of The Total Environment, 2024)

Mxenes for membrane separation: from fabrication strategies to advanced applications - Zhengyi Huang; Die Ling Zhao; Liguo Shen; Hongjun Lin; Cheng Chen; Yanchao Xu; Bisheng Li; Jiaheng Teng; Lei Han; Tai-Shung Chung (Science Bulletin, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Effects of comb-like poly-α-olefins on the cold flow properties of diesel fuel - Honggang Wang; Xiaokang Zhang; Xiuwei Lei; Li Chen; Songyue Wang; Hualin Lin; Sheng Han (Fuel, 2024)

Engineering of zeolitic imidazolate frameworks based on magnetic three-dimensional graphene as effective and reusable adsorbent to enhance the adsorption and removal of caffeine from tea samples - Yuwei Hua; Guangyang Liu; Zhihao Lin; Zhou Jie; Chenxi Zhao; Jiatong Han; Ge Chen; Linyun Li; Xiaodong Huang; Zhongxiao Liu; Jun Lv; Donghui Xu (Food Chemistry, 2024)

Fast ion/electron transport enabled by MXene confined bimetallic sulfides with heterostructure toward highly effective lithium/sodium storage - Yun-Lei Hou; Jing-Zhou Chen; Bo-Han Zhang; Hua-Ying Wang; Wan-Xin Wen; Dong-Lin Zhao (Chemical Engineering Journal, 2024)

Effects of Aegilops longissima chromosome 1Sl on wheat bread-making quality in two types of translocation lines - Yuliang Qiu; Zhiyang Han; Ningtao Liu; Mei Yu; Shuangxi Zhang; Haiqiang Chen; Huali Tang; Zhiyong Zhao; Ke Wang; Zhishan Lin; Fangpu Han; Xingguo Ye (Theoretical and Applied Genetics, 2024)

Obtainment and Inoculation of Acinetobacter pittii Strain JJ-2, and Combined Action with Plants for Formaldehyde and CO2 Removal: A Research Study - Jiaochan Zhong; Silan Chen; Shujie Lin; Yinjuan Jia; Han Li; Ting Zhan; Jian Li (Current Microbiology, 2024)

Cascade effects of climate and vegetation influencing the spatial variation of evapotranspiration in China - Lexin Ma; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Quanhong Lin; Zhaogang Liu; Lang Han; Xiaojun Dou; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Clinical characteristics and outcomes of patients with COVID-19 and tuberculosis coinfection - Jun Lv; Mengyu Liang; Lin Wang; Minmin Zhang; Renjie Liu; Han Liang; Chen Wang; Liuqun Jia; Qinglei Zeng; Pengfei Zhu (Infectious Diseases, 2023)

Study on ecological compensation quotas in different confined areas of coastal zone - A case study of mangrove reserve in shankou, guangxi, China - Xin Nie; Lin He; Zhoupeng Chen; Mengshi Yang; Yuanyuan Li; Xiaowei He; Han Wang; Wei Gao (Ocean & Coastal Management, 2023)

Discriminating the impacts of vegetation greening and climate change on the changes in evapotranspiration and transpiration fraction over the Yellow River Basin - Yangyang Liu; Ziqi Lin; Zijun Wang; Xu Chen; Peidong Han; Bo Wang; Zhenqian Wang; Zhongming Wen; Haijing Shi; Zhixin Zhang; Wei Zhang (Science of The Total Environment, 2023)

Emission characteristics of naphthalene from ship exhausts under global sulfur cap - Chin-Ko Yeh; Fu-Ming Tzu; Po-Yang Chen; Hsueh-Chen Shen; Chung-Shin Yuan; Chitsan Lin; Han-Pin Pu; Huu Hao Ngo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Observed oceanic response to Tropical Cyclone Amphan (2020) from a subsurface mooring in the Bay of Bengal - Yingyu Peng; Di Tian; Feng Zhou; Han Zhang; Xiao Ma; Dingyong Zeng; Qicheng Meng; Beifeng Zhou; Ruijie Ye; Yeqing Chen; Feilong Lin; Zhentao Hu; et al. (Progress in Oceanography, 2023)

Regulatory dynamics of the higher-plant PSI–LHCI supercomplex during state transitions - Jianghao Wu; Shuaijiabin Chen; Chao Wang; Weijun Lin; Chao Huang; Chengxu Fan; Dexian Han; Dandan Lu; Xiumei Xu; SenFang Sui; Lixin Zhang (Molecular Plant, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

pH-controlled sulfuric acid washing enhancing heavy metal stabilization in lightweight aggregate production from municipal solid waste incineration fly ash - Siyu Han; Kailun Chen; Fanzhi Meng; Yuchen Gao; Jinglin Li; Li Lin; Weikai Qin; Jianguo Jiang (Journal of Cleaner Production, 2023)

Discovery and verification of bitter components in Panax notoginseng based on the integrated strategy of pharmacophore model, system separation and bitter tracing technology - Jing Yang; Min Qiu; Tai Lu; Shangdong Yang; Ji Yu; Junzhi Lin; Hongyan Ma; Zhiping Guo; Zhencai Chen; Xue Han; Dingkun Zhang (Food Chemistry, 2023)

The behavior of whey protein isolate-curcumin complex at the oil-water interface - Huanqing Lei; Jiawei Lin; Zeling Chen; Zenan Shi; Debao Niu; Xinan Zeng; Lin Zhou; Zhong Han (Food Hydrocolloids, 2023)

Molecular cloning, expression, and functional analysis of a putative lectin from the pearl oyster (Pinctada fucata, Gould 1850) - Peng Liu; Wenyue Li; Yue Peng; Siyin Han; Zhongxiu Liang; Yanhui Cen; Xinrong Li; Peiyan Wang; Huiying Lv; Qingying Zhang; Honglin Chen; Jiang Lin (Fish & Shellfish Immunology, 2023)

Janus photothermal adsorbent for solar-powered simultaneous uranium extraction and co-production of freshwater and sea salt from seawater - Mengtao Fu; Li Han; Chen Huang; Lin Ma; Yunyou Yao; Kang Chen; Peng Sun; Haiyang Shao; Minghong Wu; Bowu Zhang; Hongjuan Ma (Chemical Engineering Journal, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Face-to-face conducting mechanism enabled by Si-C bonds for binder free Si@CNTs electrode - Zhi Yong Zhang; Zhe Fei Sun; Yan Liu; Bing Sheng Liu; Lin Shan Luo; Peng Fei Su; Chao Fei Lan; Shi Sheng Guo; Zi Qi Zhang; Xiang Han; Wei Huang; Zi Ping Wu; et al. (Chemical Engineering Journal, 2023)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Altered functional brain networks in coronary heart disease: independent component analysis and graph theoretical analysis - Simin Lin; Puyeh Wu; Shaoyin Duan; Qianni Du; Shujia Guo; Zhishang Chen; Naiming Wu; Xiaoyan Chen; Ting Xie; Yi Han; Hengyu Zhao (Brain Structure and Function, 2023)

Unraveling heterogeneity of dissolved organic matter in highly connected natural water bodies at molecular level - Guan-Lin Chen; Chen Qian; Bo Gong; Meng Du; Rui-Zhe Sun; Jie-Jie Chen; Han-Qing Yu (Water Research, 2023)

A resilience assessment framework for existing underground structures under adjacent construction disturbance - Kaihang Han; Dongmei Zhang; Xiangsheng Chen; Dong Su; Jiann-Wen Woody Ju; Xing-Tao Lin; Hongzhi Cui (Tunnelling and Underground Space Technology, 2023)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

Flunitrazepam induces neurotoxicity in zebrafish through microbiota-gut-brain axis - Wenting Lin; Kan Li; Yingjun Qin; Xing Han; Xiaohui Chen; Yuan Ren (Science of The Total Environment, 2023)

Synergistic effect between electric field and Ce-doped catalysts to promote hydrogen production from ammonia decomposition - Xiaochao Wang; Zijian Zhang; Guangzhao Zhou; Yiran Zhang; Xuteng Zhao; Dong Han; Ting Chen; Zhen Huang; He Lin (Fuel, 2023)

The metabolism of membrane lipid participates in the occurrence of chilling injury in cold-stored banana fruit - Qian Li; Han Lin; He-tong Lin; Meng-shi Lin; Hui Wang; Wei Wei; Jian-ye Chen; Wang-jin Lu; Xing-feng Shao; Zhong-qi Fan (Food Research International, 2023)

High-efficiency foam fractionation of anthocyanin from perilla leaves using surfactant-free active Al2O3 nanoparticle as collector and frother: Performance and mechanism - Lin Chen; Nan Hu; Chunquan Zhao; Xiaodan Sun; Rong Han; Yanyan Lv; Zhijun Zhang (Food Chemistry, 2023)

Oxidation of Sb(III) by Shewanella species with the assistance of extracellular organic matter - Kai-Li Wang; Di Min; Guan-Lin Chen; Dong-Feng Liu; Han-Qing Yu (Environmental Research, 2023)

Peroxymonosulfate enhanced Fe(III) coagulation coupled with membrane distillation for ammonia recovery: Membrane fouling control process and mechanism - Wucheng Ma; Rui Han; Liang Zhu; Wei Zhang; Hao Zhang; Longjie Jiang; Lin Chen (Desalination, 2023)

Unlocking the potential of elemental sulfur autotrophic denitrification through inorganic nutrient optimization - Yi-Lu Sun; Xue-Ning Zhang; Han-Lin Wang; Chen-Yang Shao; Wei-Qin Zhuang; Hao-Yi Cheng; Ji-Xian Yang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Oxygen-producing composite dressing activated by photothermal and piezoelectric effects for accelerated healing of infected wounds - Yen-Han Lai; Snigdha Roy Barman; Anindita Ganguly; Arnab Pal; Jui-Han Yu; Syun-Hong Chou; E-Wen Huang; Zong-Hong Lin; San-Yuan Chen (Chemical Engineering Journal, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

Enhanced dual-mode electrochemical zinc ion sensing by electric field-driven bi-directional mass transport - Yuzhen Huang; Kai Zhang; Xiaoshuang Chen; Xiaohui Yan; Jiaoyan Qiu; Yu Zhang; Lin Han (Chemical Engineering Journal, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Disrupted in Schizophrenia 1 Reverse Ectopic Migration of Neural Precursors in Mouse Hilus After Pilocarpine-Induced Status Epilepticus - Lu Chen; Jing Xu; Lin Zhu; Puying Xu; Lvhua Chang; Yanbing Han; Qian Wu (Molecular Neurobiology, 2023)

Association between Asbestos Exposure and the Incidence of Kidney Cancer: a Weight-of-Evidence Evaluation and Meta-analysis - Fu-Shiuan Whitney Lee; Yu-Han Chen; Ngoc Dang Tran; Cheng-Kuan Lin; Le An Pham (Current Environmental Health Reports, 2023)

Towards effective recovery of humate as green fertilizer from landfill leachate concentrate by electro-neutral nanofiltration membrane - Wenyuan Ye; Mingqiu Hong; Xuan Huang; Tianci Chen; Ailiang Gu; Xiaocheng Lin; Xuewei Li; Xiangrong Chen; Dong Han Seo; Shuaifei Zhao; Xueming Chen; Bart Van der Bruggen; et al. (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Flash-ignition of carbon black synthesized from acetylene diffusion flames and its application as ignition agents - Chih-Yung Wu; Yi-Chu Chen; Tse-Hao Wang; Po-Han Lin; Yi-Kuan Kuo (Fuel, 2023)

Ultrafast strategy to self-assemble polyamidoxime PVA nanofibers with solar-induced synergy for enhancing uranium extraction from seawater - Chen Huang; Mengtao Fu; Lin Ma; Chengkai Mao; Yunyou Yao; Xiao Xu; Lu Xu; Jiaguang Han; Xiaogang Xue; Gang Xu; Minghong Wu; Haiyang Shao; et al. (Chemical Engineering Journal, 2023)

Study on the effectiveness of ionic liquid-based biphasic amine solvent in removing H2S, NH3 and CO2 from biogas and its influential characteristics - Fanzhi Meng; Tongyao Ju; Siyu Han; Li Lin; Jinglin Li; Kailun Chen; Jianguo Jiang (Chemical Engineering Journal, 2023)

Titanium oxide nanotubes intercalated two-dimensional MXene composite membrane with exceptional antifouling and self-cleaning properties for oil/water separation - Qianqian Zeng; Die Ling Zhao; Liguo Shen; Hongjun Lin; Ning Kong; Lei Han; Cheng Chen; Jiaheng Teng; Chuyang Tang; Tai-Shung Chung (Chemical Engineering Journal, 2023)

SERS-based rapid susceptibility testing of commonly administered antibiotics on clinically important bacteria species directly from blood culture of bacteremia patients - Yin-Yi Han; Jann-Tay Wang; Wei-Chih Cheng; Ko-Lun Chen; Yi Chi; Lee-Jene Teng; Juen-Kai Wang; Yuh-Lin Wang (World Journal of Microbiology and Biotechnology, 2023)
Bloodstream infections are a growing public health concern due to emerging pathogens and increasing antimicrobial resistance. Rapid antibiotic susceptibility testing (AST) is urgently needed for timely and optimized choice of antibiotics, but current methods require days to obtain results. Here, we present a general AST protocol based on surface-enhanced Raman scattering (SERS-AST) for bacteremia caused by eight clinically relevant Gram-positive and Gram-negative pathogens treated with seven commonly administered antibiotics. Our results show that the SERS-AST protocol achieves a high level of agreement (96% for Gram-positive and 97% for Gram-negative bacteria) with the widely deployed VITEK 2 diagnostic system. The protocol requires only five hours to complete per blood-culture sample, making it a rapid and effective alternative to conventional methods. Our findings provide a solid foundation for the SERS-AST protocol as a promising approach to optimize the choice of antibiotics for specific bacteremia patients. This novel protocol has the potential to improve patient outcomes and reduce the spread of antibiotic resistance.

Fixation of CO2 by soil fungi: contribution to organic carbon pool and destination of fixed carbon products - Fang Li; Zhong-Jun Jia; Lin Chen; Yan-Lai Han; Yuan-Feng Cai; Brajesh K. Singh; Jia-Bao Zhang (Biology and Fertility of Soils, 2023)

USP14 Regulates ATF2/PIK3CD Axis to Promote Microvascular Endothelial Cell Proliferation, Migration, and Angiogenesis in Diabetic Retinopathy - Fu-Tao He; Xiao-Lin Fu; Mo-Han Li; Chun-Yan Fu; Jian-Zhi Chen (Biochemical Genetics, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Delivery of sPD1 gene by anti-CD133 antibody conjugated microbubbles combined with ultrasound for the treatment of cervical cancer in mice - Yun Liu; Zhiwei Zheng; Jiaxuan Han; Chen Lin; Chaoqi Liu; Yao Ma; Yun Zhao (Toxicology and Applied Pharmacology, 2023)

Mitochondrial RNA m3C methyltransferase METTL8 relies on an isoform-specific N-terminal extension and modifies multiple heterogenous tRNAs - Meng-Han Huang; Jin-Tao Wang; Jian-Hui Zhang; Xue-Ling Mao; Gui-Xin Peng; Xiuying Lin; Daizhu Lv; Chen Yuan; Huan Lin; En-Duo Wang; Xiao-Long Zhou (Science Bulletin, 2023)

Effects of filter cartridge wetted before filtration and during filtration on the performance of cartridge dust collector - Shihang Li; Liyuan Liu; Xiaoyu Tan; Hao Liu; Changgeng Gui; Xingyue Chen; Muze Han; Yihan Lin; Jiang Shao; Liang Yuan; Fubao Zhou (Process Safety and Environmental Protection, 2023)

PbrWRKY70 increases pear (Pyrus bretschneideri Rehd) black spot disease tolerance by negatively regulating ethylene synthesis via PbrERF1B-2 - Caihua Xing; Qiming Chen; Qinghai Qiao; Shenao Gu; Xiangyu Cheng; Huizhen Dong; Likun Lin; Feng Zhang; Chenyang Han; Zan Zhang; Hao Yin; Kaijie Qi; et al. (Plant Science, 2023)

Investigation of the fall armyworm (Spodoptera frugiperda) gut microbiome and entomopathogenic fungus-induced pathobiome - Yao-Chia Liu; Tzu-Han Chen; Yu-Feng Huang; Chang-Lin Chen; Yu-Shin Nai (Journal of Invertebrate Pathology, 2023)

Melt polycondensation of poly (butylene oxalate-co-succinate) with great potential in curbing marine plastic pollution - Qingyang Luan; Han Hu; Xiaoyu Jiang; Chen Lin; Xiaoqin Zhang; Qianfeng Wang; Yunxiao Dong; Jinggang Wang; Jin Zhu (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

In situ generated of hybrid interface in poly(1,3-dioxolane) quasi solid electrolyte and extended sulfone cosolvent for lithium-metal batteries - Bo-Han Zhang; Wan-Xin Wen; Hua-Ying Wang; Yun-Lei Hou; Jing-Zhou Chen; Dong-Lin Zhao (Chemical Engineering Journal, 2023)

Plasma-activated silicon–glass high-strength multistep bonding for low-temperature vacuum packaging - Mingzhi Yu; Libo Zhao; Yongliang Wang; Yong Xia; Yintao Ma; Yanbin Wang; Xiangguang Han; Yao Chen; Shun Lu; Guoxi Luo; Nan Zhu; Ping Yang; et al. (Chemical Engineering Journal, 2023)

Marine fungus-derived alkaloid inhibits the growth and metastasis of gastric cancer via targeting mTORC1 signaling pathway - Shuai Ma; Yiwei Hu; Jianjiao Chen; Xiaojuan Wang; Chenxi Zhang; Qianqian Liu; Guodi Cai; Hong Wang; Jianwei Zheng; Qianqian Wang; Lin Zhong; Bin Yang; et al. (Chemico-Biological Interactions, 2023)

Exploring a variable-resolution approach for simulating the regional climate in Southwest China using VR-CESM - Xiaoyu Jiang; Chenglai Wu; Bing Chen; Weiyi Wang; Xiaohong Liu; Zhaohui Lin; Zhenyu Han (Atmospheric Research, 2023)

A novel diagnostic signature of circulating tsRNAs and miRNAs in esophageal squamous cell carcinoma detected with a microfluidic platform - Di Huang; Yujin Chu; Jiaoyan Qiu; Xiaoshuang Chen; Junhua Zhao; Yu Zhang; Shunjia Li; Yufeng Cheng; Han Shi; Lin Han; Jianbo Wang (Analytica Chimica Acta, 2023)

Research on carbon footprint measurement and emissions reduction optimization of the beer supply chain in China - Jing Chen; Han Bao; Lin-Ke Pei (Environmental Science and Pollution Research, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Capsular polysaccharide mediates Streptococcus agalactiae to resist Nile tilapia macrophage phagocytosis - Yanjian Yang; Meng Chen; Zhelin Wu; Defeng Zhang; Huiyan Lin; Xiayi Wei; Biao Han; Zheng Guo; Jianmin Ye (Aquaculture, 2023)

Characterization of young biofilm morphology, disinfection byproduct formation potential and toxicity of renewed water supply pipelines by phosphorus release from corroded pipes - Songyuan Zheng; Tao Lin; Han Chen; Xue Zhang; Fuchun Jiang (Science of The Total Environment, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

MaizeNetome: A multi-omics network database for functional genomics in maize - Jia-Wu Feng; Linqian Han; Hao Liu; Wen-Zhao Xie; Hanmingzi Liu; Lin Li; Ling-Ling Chen (Molecular Plant, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

Comprehensive analyses of membrane lipids and phenolics metabolisms reveal the developments of chilling injury and browning in Chinese olives during cold storage - Xiaoyong Kuang; Yazhen Chen; Hetong Lin; Han Lin; Guo Chen; Yifen Lin; Yihui Chen; Hui Wang; Zhongqi Fan (Food Chemistry, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

The association between chemical constituents of ambient fine particulate matter and obesity in adults: A large population-based cohort study - Shaokun Yang; Feng Hong; Sicheng Li; Xinyu Han; Jiawei Li; Xing Wang; Lin Chen; Xuehui Zhang; Xi Tan; Jingru Xu; Zhuoma Duoji; Zhuoga Ciren; et al. (Environmental Research, 2023)

Exploration of the mechanism of 2-CP degradation by Acinetobacter sp. stimulated by Lactobacillus plantarum fermentation waste: A bio-waste reuse - Han Lin; Guotao Chen; Zhen Zhang; Yuan Ren (Environmental Research, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Controlled deposition via a bifunctional layer enables dendrite-free zinc metal batteries - Han Wang; Quanyu Li; Shaozhen Huang; Liangjun Zhou; Lin Mei; Zhibin Wu; Baihua Qu; Weifeng Wei; Xiaobo Ji; Yuejiao Chen; Libao Chen (Chemical Engineering Journal, 2023)

Strategies for controlling gas evolution reactions to boost the divergent paired electrochemical upgrading of furfural in acidic environment - Xinxin Li; Linchuan Cong; Yupeng Wu; Nan Lin; Fangbing Liu; Deyuan Xin; Fuyu Han; Jin Yang; Weitong Chen; Haibo Lin (Chemical Engineering Journal, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Excitation- & concentration-dependent color-tunable ultra-long phosphorescence of isophthalonitriles doped polymers - Xiaoxin Zheng; Jinke Jiang; Qinglian Lin; Cuicui Li; Jiashuai Chen; Shuwen Wang; Quanxiang Han; Xin Ye; Yang Liu; Xutang Tao (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

A novel solar-activated chlorine dioxide process for atrazine degradation in drinking water - Han Chen; Tao Lin; Peifang Wang; Yuchen Wang; Wei Wei; Shuguang Zhu (Water Research, 2023)

Effect of non-simultaneous movement of adjacent twin-trapdoor on soil arching effect through discrete-element method simulation - Ren-Peng Chen; Xiang-Shen Fu; Qi-Wei Liu; Han-Lin Wang; Fanyan Meng (Transportation Geotechnics, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Comprehensive study of recycling municipal solid waste incineration fly ash in lightweight aggregate with bloating agent: Effects of water washing and bloating mechanism - Siyu Han; Tongyao Ju; Fanzhi Meng; Li Lin; Jinglin Li; Kailun Chen; Jianguo Jiang (Science of The Total Environment, 2023)

Effect of Arbuscular mycorrhizal fungi (AMF) inoculation on endophytic bacteria of lettuce - Zhixiang Han; Zihua Zhang; Yingyue Li; Boyan Wang; Qingchen Xiao; Zishan Li; Xiaowan Geng; Keqing Lin; Tao Huang; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Evaluation of alternative processes of methanol production from CO2: Design, optimization, control, techno-economic, and environmental analysis - Hsuan-Han Chiou; Chi-Jui Lee; Bo-Sheng Wen; Jian-Xun Lin; Cheng-Liang Chen; Bor-Yih Yu (Fuel, 2023)

Enantiomeric separation and precise quantification of chiral volatiles in Wuyi rock teas using an efficient enantioselective GC × GC-TOFMS approach - Yue Zhang; Yu-Hui Zhang; Han Yan; Chen-Yang Shao; Wei-Xuan Li; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Research International, 2023)

Mixed exposure effect of seminal metals on semen quality, mediation of total antioxidant capacity, and moderation of GSTM1/GSTT1 gene deletion in Chinese reproductive-aged men - Jingchao Ren; Huidong Jin; Chen Zhang; Song Liu; Yufen Han; Jinyan Xi; Jinhu Cao; Fenglong Lin; Pingyang Zhang; Fengquan Zhang; Guang-hui Zhang; Huijun Yang; et al. (Environmental Research, 2023)

A fractional-order two-surface plasticity model for over-consolidated clays and its application to deep gallery excavation - Wei Cheng; Ren-Peng Chen; Zhen-Yu Yin; Han-Lin Wang; Fan-Yan Meng (Computers and Geotechnics, 2023)

Degradation of atrazine by a UV-activated organic chloramines process: kinetics, degradation pathways, disinfection by-product formation, and toxicity changes - Yuchen Wang; Tao Lin; Han Chen (Chemical Engineering Journal, 2023)

Investigating the nonlinear and non-stationary relationship between PM2.5 and air pollutants by wavelet signal analysis in central Taiwan - Shan-Non Feng; Yi-Ho Chen; Tzu-Han Weng; Yuan-Chien Lin (Environmental Geochemistry and Health, 2023)

Editorial: Macroecology of coastal zones under global changes - Meilin Wu; Hui Zhao; Qiuying Han; Lin Hui; Vetrimurugan Elumalai; Luzhen Chen; Keerthi Sri Senarathna Atapaththu (Frontiers in Marine Science, 2023)

Magnetotelluric constraints on the tectonic evolution beneath the Luotian dome in the North Dabie complex zone, Central China - Bo Yang; Yufeng Chen; Bo Han; Wule Lin; Xiangyun Hu; Jian Lin (Tectonophysics, 2023)

New evidence of the Hoyle-like structure in 16O - Jiahao Chen; Yanlin Ye; Kai Ma; Jiaxing Han; Dongxi Wang; Chengjian Lin; Huiming Jia; Lei Yang; Gen Li; Lisheng Yang; Ziyao Hu; Zhiwei Tan; et al. (Science Bulletin, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Investigation of additive-assisted microbial-induced calcium carbonate precipitation in 3D printed cross fractures - Liang Guo; Min Zhang; Mingwei Liao; Baoquan Wang; Xiaoyu He; Yiqi Peng; Xingzhu Lin; Ni He; Zhuhong Xiong; Han Chen; Yehui Shi; Tong Li (Geomechanics for Energy and the Environment, 2023)

Hydrochromic wood biocomposites for humidity and moisture detection - Yujie Chen; Chaozheng Liu; Zhaolun Liang; Lei Ye; Lin Liu; Zhipeng Liu; Xinhao Feng; Lloyd Donaldson; Tripti Singh; Xianxu Zhan; Jingquan Han; Qiliang Fu; et al. (Chemical Engineering Journal, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

RNA-Sequencing Reveals Gene Expression and Pathway Signatures in Umbilical Cord Blood Affected by Birth Delivery Mode - Yongjie Liu; Kun Sun; Yuexin Gan; Han Liu; Juehua Yu; Wei Xu; Lin Zhang; Dan Chen (Phenomics, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Sialylation of cell surface glycoconjugates modulates cytosolic galectin-mediated responses upon organelle damage - I-Chun Weng; Hung-Lin Chen; Wei-Han Lin; Fu-Tong Liu (Glycoconjugate Journal, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Correction: PTEN-induced kinase 1 enhances the reparative effects of bone marrow mesenchymal stromal cells on mice with renal ischaemia/reperfusion-induced acute kidney injury - Chenyu Lin; Wen Chen; Yong Han; Yujie Sun; Xiaoqiong Zhao; Yuan Yue; Binyu Li; Wenmei Fan; Tao Zhang; Li Xiao (Human Cell, 2023)

PM2.5 caused ferroptosis in spermatocyte via overloading iron and disrupting redox homeostasis - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Ying Tang; Chang Liu; Yimeng Wang; Jianping Chen; Xiao Jiang; Huan Yang; Lei Sun; Qing Chen; et al. (Science of The Total Environment, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Exploring the fungal communities and their correlation with the physicochemical properties of Zaopocu, a distinctive fermented food on Hainan island - Lin Huang; Yalin Han; Keyan Zhong; Xinjun Chen (Biologia, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

A weighted contextual active fire detection algorithm based on Himawari-8 data - Han Zhang; Lin Sun; Chunkai Zheng; Shuai Ge; Jinpeng Chen; Jiayin Li (International Journal of Remote Sensing, 2023)

Regulatory role of vitamin A in lipid metabolism and health of Eriocheir sinensis fed different vegetable oil sources - Qincheng Huang; Xiaodan Wang; Zhideng Lin; Jiadai Liu; Han Wang; Cong Zhang; Zhenyu Du; Jianguang Qin; Liqiao Chen (Aquaculture, 2023)

Nexus of ecosystem service-human health-natural resources: The nature-based solutions for urban PM2.5 pollution - Han-Shi Chen; Ying-Chen Lin; Pei-Te Chiueh (Sustainable Cities and Society, 2023)

Involvement of microRNA164 in responses to heat stress in Arabidopsis - Wei-An Tsai; Po-Han Sung; Yun-Wei Kuo; Ming-Cheng Chen; Shih-Tong Jeng; Jeng-Shane Lin (Plant Science, 2023)

Novel monoethanolamine absorption using ionic liquids as phase splitter for CO2 capture in biogas upgrading: High CH4 purity and low energy consumption - Fanzhi Meng; Tongyao Ju; Siyu Han; Li Lin; Jinglin Li; Kailun Chen; Jianguo Jiang (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

Two Novel Species of Mesophoma gen. nov. from China - Ai-Ling Yang; Lin Chen; Lu Cheng; Jin-Peng Li; Zhao-Ying Zeng; Han-Bo Zhang (Current Microbiology, 2023)

Cluster-bomb type magnetic biosensor for ultrasensitive detection of Vibrio parahaemolyticus based on low field nuclear magnetic resonance - Dongyu Zhang; Han Lin; Le Chen; Yangbo Wu; Jianjun Xie; Xizhi Shi; Zhiyong Guo (Analytica Chimica Acta, 2023)

m6A writer WTAP targets NRF2 to accelerate bladder cancer malignancy via m6A-dependent ferroptosis regulation - Ke Wang; Gang Wang; Gang Li; Wei Zhang; Yarong Wang; Xiaofeng Lin; Chengxian Han; Hanxuan Chen; Liang Shi; Abudoula Reheman; Jingkai Li; Zhaomin Li; et al. (Apoptosis, 2023)

A case of A133V genetic Creutzfeldt–Jakob disease presenting with bilateral thalamic lesions and atypical clinical features - Shi-Lin Yang; Shu-Fen Chen; Chong-Bo Zhao; Xiang Han (Acta Neurologica Belgica, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

The changes of chemical molecular components in soil organic matter are associated with fungus Mortierella capitata K. - Fang Li; Lin Chen; Zhan-Hui Zhao; Yue Li; Hai-You Yu; Yi Wang; Jia-Bao Zhang; Yan-Lai Han (Soil and Tillage Research, 2023)

Reversal of soil moisture constraint on vegetation growth in North China - Ruohua Du; Jianjun Wu; Feng Tian; Jianhua Yang; Xinyi Han; Meng Chen; Bingyu Zhao; Jingyu Lin (Science of The Total Environment, 2023)

Using HRMS fingerprinting to explore micropollutant contamination in soil and vegetables caused by swine wastewater irrigation - Wen-Ling Chen; Sih-Yi Yu; Shu-Yen Liu; Sheng-Chi Lin; Tsung-Han Lee (Science of The Total Environment, 2023)

Potential negative effects of illumination on gravity-driven membrane system in treating sulfamethoxazole-containing water - Rui Chen; Han Zhang; Dachao Lin; Jinlong Wang; Yuanqing Guo; Xiaobin Tang; Weijia Gong; Heng Liang (Resources, Conservation and Recycling, 2023)

Impact of biological activated carbon filtration and backwashing on the behaviour of PFASs in drinking water treatment plants - Tingting Zhong; Tao Lin; Xue Zhang; Fuchun Jiang; Han Chen (Journal of Hazardous Materials, 2023)

Characterization of procyanidin extracts from hawthorn (Crataegus pinnatifida) in human colorectal adenocarcinoma cell line Caco-2, simulated Digestion, and fermentation identified unique and novel prebiotic properties - Xue Han; Qian Zhou; Zhe Gao; Guanying Bianca Xu; Hong Chen; Bimal Chitrakar; Yasai Sun; Wen Zhao; Xuan Lin; Kaixuan Zhou; Zhisheng Zhang (Food Research International, 2023)

Carnosic acid attenuated cytochrome c release through the mitochondrial structural protein Mic60 by PINK1 in SH-SY5Y cells - Chia-Yuan Lin; Yi-Chen Huang; Chi-Rei Wu; Han-Ting Wu; Ru-Huei Fu; Chia-Wen Tsai (Food and Chemical Toxicology, 2023)

Swallowtail butterflies and hawkmoths contribute equally to the pollination of Habenaria dentata (Orchidaceae) - Shao-Lin Tan; Xing-Hui Chen; Hai-Hong Liao; Lang Huang; Han-Wen Xiao; Huo-Lin Luo; Dong-Jin Xiong; Bo-Yun Yang; Zong-Xin Ren (Flora, 2023)

Corrigendum to “Discovery and characterization of the flavonoids in Cortex Mori Radicis as naturally occurring inhibitors against intestinal nitroreductases” [Chem. Biol. Interact. 368 (2022) 110222] - Xi Chen; Yue Han; Lu Chen; Qian-Lin Tian; Yu-Ling Yin; Qi Zhou; Shi-Zhu Zang; Jie Hou (Chemico-Biological Interactions, 2023)

Soil microbial community is resilient to thinning disturbance - Wan-Rou Lin; Wen-Cheng Chen; Pi-Han Wang (Tropical Ecology, 2023)

Engelheptanoxides behave as liver X receptor α agonists - Yu-Hsuan Liang; Yu-Han Luo; Ih-Sheng Chen; Hsiang-Ru Lin (Medicinal Chemistry Research, 2023)

Alteration of the Gut Microbiota in Missed Abortion - Yi Chen; Xianqian Chen; Pingyu Chen; Xiuxia Chen; Lin Pan; Lihong Han; Tang Zhu (Indian Journal of Microbiology, 2023)
There is a symbiotic relationship between gut microbiota and human beings. Imbalance of the gut microbiota will cause pathological damages to humans. Although many risk factors are associated with missed abortion (MA), the pathological mechanism of it is still unclear. Here, we analyzed gut flora of the patients with MA by S16 high-throughput sequencing. The possible pathogenic mechanisms of the MA were explored. Fecal samples from 14 healthy controls and 16 MA patients were collected to do 16S rRNA gene high-throughput sequencing analysis. The abundance of the Bacteroidetes , Proteobacteria , Actinobacteria , Escherichia , Streptococcus_ Salivarius , and Lactobacillus was significantly reduced in the MA group, while, the abundance of the Klebsiella was significantly increased in the MA patients. The Ruminococcaceae and [Eubacterium]_coprostanoligenes_group were found only in the specimens of the MA patients. The Fabrotax function prediction analysis showed that four photosynthesis function bacteria ( cyanobateria , oxygenic_photoautotrophy , photoautotrophy , and phototrophy ) only existed in the MA group. In the analysis of the BugBase microbiome function prediction, the Escherichia of the MA group is significantly reduced compared to that of the healthy controls in the items of that Contains_Mobile_Elements , Facultatively_Anaerobic , Forms_Biofilms , Potentially_Pathogenic.png , Gram_Nagative , and Stress_Tolerant_relabundance . These alterations may affect the stability of the host's immune, neural, metabolic and other systems by interfering with the balance of the gut microbiota or by the metabolites of those bacteria, causing the MA. This study explored the possible pathogenic factors of the gut microbiota of the MA. The results provide evidence to figure out the pathogenesis of the MA.

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

Evaluation of toxicity of polystyrene microplastics under realistic exposure levels in human vascular endothelial EA.hy926 cells - Yi-Chun Chen; Ku-Fan Chen; Kun-Yi Andrew Lin; Han-Pang Su; Dong-Ni Wu; Chia-Hua Lin (Chemosphere, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Preferred prey reduce species realized niche shift and improve range expansion prediction - Lixia Han; Zhixin Zhang; Weishan Tu; Qing Zhang; Yanhua Hong; Shengnan Chen; Zhiqiang Lin; Shimin Gu; Yuanbao Du; Zhengjun Wu; Xuan Liu (Science of The Total Environment, 2023)

Effects of Fe(II)-activated persulfate/sodium percarbonate (PS/SPC) pretreatment on ultrafiltration membrane fouling control and mechanisms - Jiachen Mo; Tao Lin; Xue Zhang; Fuchun Jiang; Han Chen (Desalination, 2023)

A stretchable and conductive design based on multi-responsive hydrogel for self-sensing actuators - Changhao Qian; Yueqin Li; Chen Chen; Lin Han; Qingshan Han; Lingke Liu; Zichun Lu (Chemical Engineering Journal, 2023)

Editorial: Oceanographic processes linking nearshore, continental shelf, and shelf break - Feng-Hsun Chang; Yun-Chi Lin; Kuo-Ping Chiang; Ya-Han Nien; Chih-hao Hsieh; Wei-Jen Chen; Chin-Chang Hung; Toru Kobari; Hiroaki Saito; William Savidge (Frontiers in Marine Science, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Effects of synthetic astaxanthin and Haematococcus pluvialis on growth, antioxidant capacity, immune response, and hepato-morphology of Oncorhynchus mykiss under cage culture with flowing freshwater - Wei Zhao; Han-Lin Wei; Meng-Die Chen; Rong Yao; Zi-Qiao Wang; Jin Niu (Aquaculture, 2023)

Landslide-impacted soils recover faster biologically than chemically or physically, though recovery also varies with forest type in subtropical China - Jian Li; Lan Xiao; Jonathan D. Bakker; Qinghu Luo; Hang Yu; Jianzhao Wu; Songyang Li; Loretta Pedersen; Can Chen; Tao Hong; Han Lin; Daojie Wang; et al. (Soil and Tillage Research, 2023)

Seasonal variation and ecological risk assessment of Pharmaceuticals and Personal Care Products (PPCPs) in a typical semi-enclosed bay — The Bohai Bay in northern China - Kun Lin; Rui Wang; Tongzhu Han; Liju Tan; Xue Yang; Mengmeng Wan; Yanshan Chen; Ting Zhao; Shan Jiang; Jiangtao Wang (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Comparative pulmonary toxicity assessment of tungsten trioxide and tungsten trioxide hydrate nanoparticles - Hsin Her Yu; Yi-Chun Chen; Han-Pang Su; Liliang Chen; Hung-Hsiang Chen; Kun-Yi Andrew Lin; Chia-Hua Lin (Science of The Total Environment, 2023)

Variation of microplastics and biofilm community characteristics along the long-distance raw water pipeline - Hui Tao; Lingqin Zhou; Yiting Qi; Yiyang Chen; Zongshuo han; Tao Lin (Process Safety and Environmental Protection, 2023)

Multidimensional analysis of the essential elements in pregnant women's whole blood and characterization of maternal status by elemental pattern - Min Zhan; Wenbin Chen; Zhichao Wang; Xuhui She; Qiaoxuan Zhang; Heng Dong; Jun Yan; Zhuoyang Li; Liqiao Han; Haibiao Lin; Xianzhang Huang; Beibei Zhao (Journal of Trace Elements in Medicine and Biology, 2023)

Higher blood selenium level is associated with lower risk of hyperhomocysteinemia in the elderly - Ting Wang; Liqin Su; Xi Chen; Sisi Wang; Xu Han; Yibin Cheng; Shaobin Lin; Liang Ding; Jingyi Liu; Chen Chen; Frederick W. Unverzagt; Ann M. Hake; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Bifunctional additive phenolic acids grafted ethylene-vinyl acetate copolymers for improving the cold flow properties and oxidative stability of waste cooking oil biodiesel-diesel blends - Bin Sun; Xiaokang Zhang; Yuzhuang Zhao; Fengfei Chen; Feihe Ren; Hualin Lin; Yuan Xue; Sheng Han (Fuel, 2023)

Statistical optimization of hydrogen production from bio-methanol steam reforming over Ni-Cu/Al2O3 catalysts - Yi-Kai Chih; Wei-Hsin Chen; Siming You; Chun-Han Hsu; Hong-Ping Lin; Salman Raza Naqvi; Veeramuthu Ashokkumar (Fuel, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

Patent mining on soil pollution remediation technology from the perspective of technological trajectory - Zefeng Qi; Yixin Han; Sandylove Afrane; Xi Liu; Mingqi Zhang; John Crittenden; Jian Lin Chen; Guozhu Mao (Environmental Pollution, 2023)

Biodegradation of high di-(2-Ethylhexyl) phthalate (DEHP) concentration by food waste composting and its toxicity assessment using seed germination test - Huu-Tuan Tran; Chitsan Lin; Su Shiung Lam; Thi Hieu Le; Hong-Giang Hoang; Xuan-Thanh Bui; Eldon R. Rene; Po Han Chen (Environmental Pollution, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

N-type small molecule electron transport materials with D-A-D conjugated core for non-fullerene organic solar cells - Dan Zhou; Yubing Li; Hehui Zhang; Haolan Zheng; Xingxing Shen; Wen You; Lin Hu; Liangjing Han; Yongfen Tong; Lie Chen (Chemical Engineering Journal, 2023)

Combination of highly photovoltaic and highly transparent materials enables record performance semitransparent organic solar cells - Lin Zhao; Xuexiang Huang; Yukai Wang; Sang Young Jeong; Bin Huang; Jiawei Deng; Jiabin Liu; Yujun Cheng; Han Young Woo; Feiyan Wu; Limin Chen; Lie Chen (Chemical Engineering Journal, 2023)

Novel solar/sulfite advanced oxidation process for carbamazepine degradation: Radical chemistry, transformation pathways, influence on disinfection byproducts and toxic changes - Han Chen; Tao Lin; Peifang Wang; Xue Zhang; Fuchun Jiang; Yuchen Wang (Chemical Engineering Journal, 2023)

Control measure implications of COVID-19 infection in healthcare facilities reconsidered from human physiological and engineering aspects - Ying-Fei Yang; Yi-Jun Lin; Shu-Han You; Tien-Hsuan Lu; Chi-Yun Chen; Wei-Min Wang; Chung-Min Liao (Environmental Science and Pollution Research, 2022)

The biological transformation of ammonium and urea in a eutrophic estuarine system in Southern China - Jin-Ming Tang; Min Nina Xu; Yuxuan Lin; Huangxin Chen; Haoquan Jin; Li-Li Han; Wenbin Zou; Shuh-Ji Kao (Frontiers in Marine Science, 2022)
Estuaries channel large amounts of anthropogenic nitrogen (N) from continents to the offshore where productivity is widely limited by N and phosphorus. Ammonium and urea, two reduced forms of anthropogenic N commonly observed, are the preferred substrates for various microorganisms (e.g., uptake by phytoplankton or bacteria and oxidation by nitrifier). Yet, it remains underexplored how they transform and their concentrations vary during transport in the estuary which may influence the offshore microbial community. We applied 15 N isotope tracer incubation techniques to determine the two main bio-consumption processes, i.e., uptake and oxidation, of ammonium and urea, in the dark for the Jiulong River Estuary, a eutrophic estuary in southeastern China. Results showed that light penetration depth ranged from 0.8-3.3 m leaving 76% of estuary water bodies to stay in dark situations throughout a day. Ammonia oxidation, which favors dark conditions, dominates the estuarine regenerated-N cycle, showing the rank: ammonia oxidation > ammonium uptake >> urea uptake ≈ urea oxidation. By compiling the reported case studies, we found the relatively low ratio of urea oxidation to ammonia oxidation was accompanied by a relatively high ammonium concentration. Microorganisms’ high preference for ammonium over urea may lead to an inhibitory-like phenomenon. An analogous effect was evident by the increased urea uptake at downstream when ammonium was down to a few µM. The obstructed urea utilization resulted in 10 times longer lifetime for urea relative to ammonium (surface: 19 ± 9 days; bottom 12 ± 7 days). Such an inhibitory-like effect allows urea to be preserved in the estuary and allows urea to be transported farther offshore to stimulate microorganisms capable of utilizing urea, which may have significant impacts on offshore ecology.

Feasibility Study of a Novel Open Ocean Aquaculture Ship Integrating with a Wind Turbine and an Internal Turret Mooring System - Hanyu Liu; Mingsheng Chen; Zhaolong Han; Hao Zhou; Lin Li (Journal of Marine Science and Engineering, 2022)
Marine aquaculture has been expanded into more remote areas due to the increasing demand for high value-added fish products, bringing more challenges in fuel supply and mooring safety to open ocean aquaculture farms. Therefore, the idea of integrating aquaculture farms with offshore renewable energy has attracted tremendous interest. This study proposes a novel open ocean aquaculture ship integrated with a NREL 5 MW wind turbine. In addition, an internal turret mooring system is installed at the bow of the aquaculture ship, making the wind turbine always face the wind blowing direction due to the weathervaning effect. In this study, a preliminary study of the dynamics and wind power generation of the proposed open ocean aquaculture ship was conducted. The aerodynamic and elastic effects of the wind turbine and the effect of nets under the wave and current behavior on the dynamics of the single-point moored aquaculture ship were investigated. Furthermore, the effects of the dynamics of the aquaculture ship on the power generation of the wind turbine were also studied to investigate the feasibility of the idea to integrate an aquaculture ship with a wind turbine.

Two new phenylpropenoid glycosides from the roots of Illicium dunnianum - Yi-lin Wang; Han Li; Ling Song; Yun-hang Gao; Teng-fei Chen (Natural Product Research, 2022)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Optimized thyroid transcription factor-1 core promoter-driven microRNA-7 expression effectively inhibits the growth of human non-small-cell lung cancer cells - Shipeng Chen; Lian Guan; Xu Zhao; Jing Yang; Longqing Chen; Mengmeng Guo; Juanjuan Zhao; Chao Chen; Ya Zhou; Yong Han; Lin Xu (Journal of Zhejiang University-SCIENCE B, 2022)

Transcriptome and metabolome profiling of interspecific CSSLs reveals general and specific mechanisms of drought resistance in cotton - Bei Han; Fengjiao Wang; Zhilin Liu; Lin Chen; Dandan Yue; Weinan Sun; Zhongxu Lin; Xianlong Zhang; Xiaofeng Zhou; Xiyan Yang (Theoretical and Applied Genetics, 2022)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Three-dimensional characteristics of mesoscale eddies simulated by a regional model in the northwestern Pacific Ocean during 2000–2008 - Guijing Yang; Xiayan Lin; Guoqing Han; Yu Liu; Gengxin Chen; Jianhui Wang (Acta Oceanologica Sinica, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Modeling and Dynamic Analysis of a Triple-Tagline Anti-Swing System for Marine Cranes in an Offshore Environment - Maokai Sun; Shenghai Wang; Guangdong Han; Lin An; Haiquan Chen; Yuqing Sun (Journal of Marine Science and Engineering, 2022)
Payload lifting is inefficient and high-risk under rough sea conditions. Thus, it is not easy to achieve precise assembly, and the swing payload is liable to collide with other structures on deck and cause damage. In this paper, to explore the complex dynamic characteristics of a triple-tagline anti-swing system (TTAS) for marine cranes in an offshore environment, an irregular wave model was first integrated into a dynamic system model of TTAS, and the TTAS for offshore payload lifting was simplified as a constrained-pendulum system with moving base excitations. Further, the dynamic system model was established by applying the methods in robotics. Meanwhile, the dynamic characteristics were simulated and analyzed using Matlab/Simulink. The simulation results show that the in-plane angle and out-of-plane angle of the payload can be effectively suppressed, and the range of the two-dimensional trajectory of the payload is greatly reduced. The research results provide a theoretical basis for optimizing the mechanical structures of TTAS or similar equipment.

PTEN-induced kinase 1 enhances the reparative effects of bone marrow mesenchymal stromal cells on mice with renal ischaemia/reperfusion-induced acute kidney injury - Chenyu Lin; Wen Chen; Yong Han; Yujie Sun; Xiaoqiong Zhao; Yuan Yue; Binyu Li; Wenmei Fan; Tao Zhang; Li Xiao (Human Cell, 2022)
Acute kidney injury (AKI) is a common severe acute syndrome caused by multiple factors and is characterized by a rapid decline in renal function during a short period. Bone marrow mesenchymal stromal cells (BMSCs) are effective in treating AKI. However, the mechanism of their beneficial effects remains unclear. PTEN-induced kinase 1 (PINK1) may play an important role in kidney tissue repair. In this study, we explored the effect of PINK1 overexpression on enhancing BMSC-mediated repair of AKI. In this study, ischaemia/reperfusion-induced AKI (IRI-AKI) in mice and a hypoxia-reoxygenation model in cells were established, and the indices were examined by pathology and immunology experiments. After ischaemia/reperfusion, PINK1 overexpression reduced apoptosis in injured kidney tissue cell, decreased T lymphocyte infiltration, increased macrophage infiltration, and alleviated the inflammatory response. PINK1 relieved the stress response of BMSCs and renal tubular epithelial cells (RTECs), reduced apoptosis, altered the release of inflammatory factors, and reduced the proliferation of peripheral blood mononuclear cells (PBMCs). In conclusion, BMSCs and RTECs undergo stress responses in response to hypoxia, inflammation and other conditions, and overexpressing PINK1 in BMSCs could enhance their ability to resist these stress reactions. Furthermore, PINK1 overexpression can regulate the distribution of immune cells and improve the inflammatory response. The regulation of mitochondrial autophagy during IRI-AKI maintains mitochondrial homeostasis and protects renal function. The results of this study provide new strategies and experimental evidence for BMSC-mediated repair of IRI-AKI.

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Biomechanical Analysis of Mandibular Implant-Assisted Removable Partial Denture with Distal Extension - Yung-Chung Chen; Chi-Lun Lin; Chen-Han Yu; Hung-Chih Chang; Yang-Ming Lin; Jia-Wei Lin (Journal of Medical and Biological Engineering, 2022)

Assessing the effect of probiotics on tilapia lake virus‐infected tilapia: Transmission and immune response - Ying‐Fei Yang; Jidapa Yamkasem; Win Surachetpong; Yi‐Jun Lin; Shu‐Han You; Tien‐Hsuan Lu; Chi‐Yun Chen; Wei‐Min Wang; Chung‐Min Liao (Journal of Fish Diseases, 2022)
Probiotics have been used to alleviate disease transmission in aquaculture. However, there are limited studies on probiotic use in modulating tilapia lake virus (TiLV). We assessed commercially available probiotic supplements used in TiLV‐infected tilapia and performed mortality and cohabitation assays. We developed a mechanistic approach to predict dose–response interactions of probiotic effects on mortality and immune gene response. We used a susceptible–infected–mortality disease model to assess key epidemiological parameters such as transmission rate and basic reproduction number ( R 0 ) based on our viral load dynamic data. We found that the most marked benefits of probiotics are significantly associated with immune system enhancements (~30%) and reductions in disease transmission (~80%) and R 0 (~70%) in tilapia populations, resulting in a higher tolerance of farming densities (~400 fold) in aquaculture. These findings provide early insights as to how probiotic use‐related factors may influence TiLV transmission and the immune responses in TiLV‐infected tilapia. Our study facilitates understanding the mode of action of probiotics in disease containment and predicting better probiotic dosages in diet and supplements to achieve the optimal culturing conditions. Overall, our analysis assures that further study of rationally designed and targeted probiotics, or mechanistic modelling is warranted on the basis of promising early data of this approach.

Isoflurane and Sevoflurane Induce Cognitive Impairment in Neonatal Rats by Inhibiting Neural Stem Cell Development Through Microglial Activation, Neuroinflammation, and Suppression of VEGFR2 Signaling Pathway - Chunlong Zuo; Junmei Ma; Yizhao Pan; Dongxu Zheng; Chunjiang Chen; Naqi Ruan; Ying Su; Haihan Nan; Qingquan Lian; Han Lin (Neurotoxicity Research, 2022)
Inhaled anesthetics are known to induce neurotoxicity in the developing brains of rodents, although the mechanisms are not well understood. The aim of this study was to elucidate the molecular mechanisms underlying anesthetics-induced neurodevelopmental toxicity by VEGF receptor 2 (VEGFR2) through the interaction between microglia and neural stem cells (NSCs) in postnatal day 7 (P7) rats. Cognitive function of P7 rats exposed to isoflurane and sevoflurane were assessed using Morris Water Maze and T maze tests. We also evaluated the expression levels of NSC biomarkers (Nestin and Sox2), microglia biomarker (CD11b or or IBA1), pro-inflammatory cytokines (IL-6 and TNF-α), and VEGFR2 using western blotting and immunohistochemistry in the brains of control and anesthesia-treated rats. We found spatial learning and working memory was impaired 2 weeks after anesthetics exposure in rats. Isoflurane induced stronger and more prolonged neurotoxicity than sevoflurane. However, cognitive functions were recovered 6 weeks after anesthesia. Isoflurane and sevoflurane decreased the levels of Nestin, Sox2, and p-VEGFR2, activated microglia, decreased the number of NSCs and reduced neurogenesis and the proliferation of NSCs, and increased the levels of IL-6, TNF-α, and CD11b. Our results suggested that isoflurane and sevoflurane induced cognitive impairment in rats by inhibiting NSC development and neurogenesis via microglial activation, neuroinflammation, and suppression of VEGFR2 signaling pathway.

Evaluation of PET List Data-Driven Gated Motion Correction Technique Applied in Lung Tumors - Yi-Lun Chen; Bang-Hung Yang; I.-Ling Shih; Ko-Han Lin (Journal of Medical and Biological Engineering, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Sphingobacterium bovistauri sp. nov., Isolated from the Faeces of Bos Taurus - Qiong Wang; Zhi-Qin Fang; Chen-Lu Zhang; Jian-Qiang Shen; Jian-Dong Lai; Xiu-Lin Han; Tao Lu (Current Microbiology, 2022)

Selenium Deficiency Leads to Changes in Renal Fibrosis Marker Proteins and Wnt/β-Catenin Signaling Pathway Components - Tingting Lin; Jiaqi Tao; Ying Chen; Yitong Zhang; Fenglan Li; Yutong Zhang; Xueqing Han; Zihui Zhao; Guiyan Liu; Hui Li (Biological Trace Element Research, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Effects of Suspended Particles on Exopolysaccharide Secretion of Two Microalgae in Jinjiang Estuary (Fujian, China) - Jie Liu; Xiaoyu Han; Hui Xing; Yiting Nan; Jiahui Lin; Junming He; Sijia Chen; Yanfang Wei; Peiyong Guo (Journal of Marine Science and Engineering, 2022)
The effects of suspended particles (SP) of different concentrations and sizes on the secretion of exopolysaccharide (EPS) by Chlorella pyrenoidosa (C. pyrenoidosa) and Microcystis flos-aquae (M. flos-aquae) in Jinjiang Estuary, Fujian Province, China were studied in co-cultures of microalgae and SP. The results show that the SP concentration has an “inhibit–promote–inhibit” effect on the secretion of EPS by C. pyrenoidosa, whereby there is an optimal concentration of SP corresponding to the largest amount of EPS secreted by C. pyrenoidosa. Low concentrations had no significant effect on the secretion of EPS from M. flos-aquae (p > 0.05), whereas higher concentrations had an inhibitory effect. The C. pyrenoidosa EPS content was found to be significantly decreased in response to SP of small particle sizes (0–75 and 75–120 μm) and significantly increased for SP of large particle sizes (120–150 and 150–500 μm). Small particle sizes (0–75 and 75–120 μm) were found to be beneficial to the secretion of EPS from M. flos-aquae, and the promotion of EPS secretion gradually decreased with the increase in SP particle size. However, when the particle size was too large (120–150 and 150–500 μm), SP had no significant effect on EPS secretion. This study is helpful for understanding the microalgae EPS secretion response to SP and provides a scientific basis for studying the mechanism of EPS secretion by algae and the effect of SP on eutrophication of the estuary.

Trimetazidine affects pyroptosis by targeting GSDMD in myocardial ischemia/reperfusion injury - Xudong Chen; Shuang Lin; Shanshan Dai; Jibo Han; Peiren Shan; Weiqi Wang; Zhouqing Huang; Bozhi Ye; Weijian Huang (Inflammation Research, 2022)

Identification and bioinformatics analysis of differentially expressed milk exosomal microRNAs in milk exosomes of heat-stressed Holstein cows - Yue Wang; Jian Fang; Han-Fang Zeng; Ji-Feng Zhong; Hui-Xia Li; Kun-Lin Chen (Functional & Integrative Genomics, 2022)

Individual exposure to ambient PM2.5 and hospital admissions for COPD in 110 hospitals: a case-crossover study in Guangzhou, China - Jie-Qi Jin; Dong Han; Qi Tian; Zhao-Yue Chen; Yun-Shao Ye; Qiao-Xuan Lin; Chun-Quan Ou; Li Li (Environmental Science and Pollution Research, 2022)
Few studies have evaluated the short-term association between hospital admissions and individual exposure to ambient particulate matter (PM 2.5 ). Particularly, no studies focused on hospital admissions for chronic obstructive pulmonary disease (COPD) at the individual level. We assessed the short-term effects of PM 2.5 on hospitalization admissions for COPD in Guangzhou, China, during 2014–2015, based on satellite-derived estimates of ambient PM 2.5 concentrations at a 1-km resolution near the residential address as individual-level exposure for each patient. Around 40,002 patients with COPD admitted to 110 hospitals were included in this study. A time-stratified case-crossover design with conditional logistic regression models was applied to assess the effects of PM 2.5 based on a 1-km grid data of aerosol optical depth provided by the National Aeronautics and Space Administration on hospital admissions for COPD. Further, we performed stratified analyses by individual demographic characteristics and season of hospital admission. Around 10 μg/m 3 increase in individual-level PM 2.5 was associated with an increase of 1.6% (95% confidence interval [CI]: 0.6%, 2.7%) in hospitalization for COPD at a lag of 0–5 days. The impact of PM 2.5 on hospitalization for COPD was greater significantly in males and patients admitted in summer. Our study strengthened the evidence for the adverse effect of PM 2.5 based on satellite-based individual-level exposure data.

Advenella mandrilli sp. nov., a bacterium isolated from the faeces of Mandrillus sphinx - Qiong Wang; Xiu-Lin Han; Zhi-Qin Fang; Chen-Lu Zhang; Chun Li; Tao Lu (Antonie van Leeuwenhoek, 2022)

Development and validation of a 30-day death nomogram in patients with spontaneous cerebral hemorrhage: a retrospective cohort study - Qian Han; Mei Li; Dongpo Su; Aijun Fu; Lin Li; Tong Chen (Acta Neurologica Belgica, 2022)

miRNA–mRNA Integrative Analysis Reveals the Roles of miRNAs in Hypoxia-Altered Embryonic Development- and Sex Determination-Related Genes of Medaka Fish - Keng Po Lai; Nathan Yi Kan Tam; Yuelong Chen; Chi Tim Leung; Xiao Lin; Chau Fong Tsang; Yin Cheung Kwok; William Ka Fai Tse; Shuk Han Cheng; Ting Fung Chan; Richard Yuen Chong Kong (Frontiers in Marine Science, 2022)
Recent studies have shown hypoxia to be an endocrine disruptor that impairs sex differentiation and reproductive function, leading to male-biased F1 populations in fish. However, the molecular mechanisms through which hypoxia alters fish sex differentiation and therefore sex ratios remain poorly understood. In order to understand the potential role of miRNAs in mediating hypoxia-altered sex determination and differentiation in fish, we conducted small RNA sequencing and transcriptome sequencing on marine medaka ( Oryzias melastigma ) embryos that were exposed to hypoxia (2.0 ± 0.2 mg O 2 L – 1) for 40 h (encompassing a critical window of sex determination). We identified dysregulated miRNAs and mRNAs in the hypoxia-exposed embryo, and bioinformatic analysis of the integrative small RNA sequencing and transcriptome sequencing results revealed hypoxia to cause alterations of genes related to embryonic development through miRNA regulation. Importantly, we have identified miRNA-mRNA pairs that were reported to play roles in gonad development (novel miR-145-col9a3 and novel miRNA-94- arid5b), in sex hormone response (novel miRNA-210-ca2, novel miRNA-106-nr2f2, nbr-miR-29c-nr4a1, and ola-miR-92b-akr1d1), and in sex characteristic development (novel miRNA-145-mns1, nle-miR-20-sord, and ipu-miR-219b-abcc8). Our findings highlighted the possible roles of miRNA–mRNA in regulation of embryonic development and sex determination in response to hypoxic stress.

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

The brown root rot fungus Phellinus noxius affects microbial communities in different root‐associated niches of Ficus trees - Tse‐Yen Liu; Chao‐Han Chen; Yu‐Liang Yang; Isheng J. Tsai; Ying‐Ning Ho; Chia‐Lin Chung (Environmental Microbiology, 2022)
Summary Brown root rot (BRR) caused by Phellinus noxius is a destructive tree disease in tropical and subtropical areas. To understand how BRR affects the composition of the plant rhizoplane‐enriched microbiota, the microbiomes within five root‐associated compartments (i.e., bulk soil, old/young root rhizosphere soil, old/young root tissue) of Ficus trees naturally infected by P. noxius were investigated. The level of P. noxius infection was determined by quantitative PCR. Illumina sequencing of the internal transcribed spacer and 16S rRNA revealed that P. noxius infection caused a significant reduction in fungal diversity in the bulk soil, the old root rhizosphere soil, and the old root tissue. Interestingly, Cosmospora was the only fungal genus positively correlated with P. noxius . The abundance and composition of dominant bacterial taxa such as Actinomadura , Bacillus , Rhodoplanes , and Streptomyces differed between BRR‐diseased and healthy samples. Furthermore, 838 isolates belonging to 26 fungal and 35 bacterial genera were isolated and tested for interactions with P. noxius . Antagonistic activities were observed for isolates of Bacillus , Pseudomonas , Aspergillus , Penicillium , and Trichoderma . Cellophane overlay and cellulose/lignin utilization assays suggested that Cosmospora could tolerate the secretions of P. noxius and that the degradation of lignin by P. noxius may create suitable conditions for Cosmorpora growth.

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

Effect of lgals3a on embryo development of zebrafish - Kan Chen; Yuqi Fan; Jun Gu; Zhihua Han; Yue Wang; Lin Gao; Huasu Zeng; Chengyu Mao; Changqian Wang (Transgenic Research, 2021)

Complete genome sequence of a putative novel ilarvirus isolated from Eleocharis dulcis - Lanqing Lv; Xinyang Wu; Jiajia Weng; Yuchao Lai; Kelei Han; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; et al. (Archives of Virology, 2021)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Effect of dietary supplementation with Chlorella sorokiniana meal on the growth performance, antioxidant status, and immune response of rainbow trout (Oncorhynchus mykiss) - Weijun Chen; Lin Luo; Danxiang Han; Feiping Long; Qinglei Chi; Qiang Hu (Journal of Applied Phycology, 2021)

Near-field prediction of chemical hazard diffusion based on improved differential evolution algorithm and fireworks algorithm - Chaoshuai Han; Xuezheng Zhu; Jin Gu; Qinwen Zuo; Lin Chen; Yihao Shi (Environmental Monitoring and Assessment, 2021)

Integration of small RNAs, degradome, and transcriptome sequencing provides insights into the differences between Shizhu ginseng and Yuan ginseng - Mengyuan Peng; Yanlin Chen; Wenjuan Wang; Zhihua He; Wangqiang Dai; Zhiyun Lin; Zemin Yang; Mengjuan Gong; Yongqin Yin; Bin Han; Yu Zeng; Yingfang Wang (Journal of Plant Biochemistry and Biotechnology, 2021)
Panax ginseng is one of the most popular herbs which have been used as an important traditional Chinese medicine since ancient times. Yuan ginseng and Shizhu ginseng,which belong to P. ginseng , are widely used as substitutes for wild ginseng in clinical practice. Clinical practice has proved that the clinical efficacy of Shizhu ginseng is better than Yuan ginseng. However, current research cannot completely explain this phenomenon. Considering that small RNA may be one of the pharmacodynamic substances of P. ginseng , it is challenging to investigate differential miRNAs between Shizhu ginseng and Yuan ginseng. In this study, the transcriptome, small RNAome and degradome of P. ginseng were studied by high-throughput sequencing. A total of 63,875 unigenes and 43,950,137 small RNA clean reads were obtained from the roots of P. ginseng . Among 3206 differentially expressed genes, 1190 genes were up-regulated in Yuan ginseng when compared with Shizhu ginseng. 24 known differential miRNAs and 7 novel differential miRNAs were obtained. The 304 targets of 24 differentially expressed miRNA (17 known and 7 novel) families are mainly related to energy metabolism, biotic stress and disease immunity in ginseng itself. Through the association analysis of mRNA and miRNA, our work gives a better understanding of the difference between Yuan ginseng and Shizhu ginseng. Considering the cross-kingdom regulation of plant miRNAs, our results may provide a foundation for understanding the miRNA-dependent clinical efficacy in P. ginseng .

Sphingobacterium rhinopitheci sp. Nov., isolated from the faeces of Rhinopithecus bieti in China - Xiu-Lin Han; Qiong Wang; Chen-Lu Zhang; Zhi-Qin Fang; Jian-Qiang Shen; Song Huang; Tao Lu (Archives of Microbiology, 2021)

The Significant Role of Radiosonde-measured Cloud-base Height in the Estimation of Cloud Radiative Forcing - Hui Xu; Jianping Guo; Jian Li; Lin Liu; Tianmeng Chen; Xiaoran Guo; Yanmin Lyu; Ding Wang; Yi Han; Qi Chen; Yong Zhang (Advances in Atmospheric Sciences, 2021)

Overexpression of Cell-Surface Marker SLC16A1 Shortened Survival in Human High-Grade Gliomas - Hong-Han Lin; Wen-Chiuan Tsai; Chia-Kuang Tsai; Ssu-Han Chen; Li-Chun Huang; Dueng-Yuan Hueng; Kuang-Chen Hung (Journal of Molecular Neuroscience, 2021)

Recycle of synthetic calcium fluoride and waste sulfuric acid to produce electronic grade hydrofluoric acid - Min-Fa Lin; Jhong-Lin Wu; Ken-Lin Chang; Wen-Jhy Lee; Chih-Ping Chang; Yung-Chang Lin; Po-Han Chen (Environmental Science and Pollution Research, 2021)

Nanotechnology advances in pathogen- and host-targeted antiviral delivery: multipronged therapeutic intervention for pandemic control - Kai-Chieh Yang; Jung-Chen Lin; Hsiao-Han Tsai; Chung-Yao Hsu; Vicky Shih; Che-Ming Jack Hu (Drug Delivery and Translational Research, 2021)

Porcine circovirus type 2 (PCV2) infection in Hebei Province from 2016 to 2019: a retrospective study - Lei Han; Guang-fu Yuan; Shao-jie Chen; Fei Dai; Lin-shan Hou; Jing-hui Fan; Yu-zhu Zuo (Archives of Virology, 2021)

Quantitative Fluorescence Resonance Energy Transfer Analysis on the Direct Interaction of Activation-2b with Histone H3/Switch-3B Protein in Arabidopsis Mesophyll Protoplasts - Lu Gao; Fangrui Lin; Danlu Han; Jieming Jiang; Chengwei Yang; Zhengfei Zhuang; Tongsheng Chen (Journal of Fluorescence, 2021)

Distributions of Total Mercury and Methylmercury in Dragonflies from a Large, Abandoned Mercury Mining Region in China - Gaoen Wu; Shunlin Tang; Jialiang Han; Chan Li; Lin Liu; Xiaohang Xu; Zhidong Xu; Zhuo Chen; Yajie Wang; Guangle Qiu (Archives of Environmental Contamination and Toxicology, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

GTree: an Open-source Tool for Dense Reconstruction of Brain-wide Neuronal Population - Hang Zhou; Shiwei Li; Anan Li; Qing Huang; Feng Xiong; Ning Li; Jiacheng Han; Hongtao Kang; Yijun Chen; Yun Li; Huimin Lin; Yu-Hui Zhang; et al. (Neuroinformatics, 2021)

Exendin-4 Reversed the PC12 Cell Damage Induced by circRNA CDR1as/miR-671/GSK3β Signaling Pathway - Hui Quan; Qiudan Chen; Kesheng Wang; Qinwan Wang; Meiling Lu; Yue Zhang; Sujing Qiang; Shaobo Xue; Lin Han; Huanhuan Zhu; Qiangyuan Fan; Meiyu Bao; et al. (Journal of Molecular Neuroscience, 2021)

Clinacanthus nutans Mitigates Neuronal Death and Reduces Ischemic Brain Injury: Role of NF-κB-driven IL-1β Transcription - Mei-Han Kao; Jui-Sheng Wu; Wai-Mui Cheung; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Deron R. Herr; Teng-Nan Lin (NeuroMolecular Medicine, 2021)

Enhanced antioxidant capacity and upregulated transporter genes contribute to the UV-B-induced increase in blinin in Conyza blinii - Junyi Zhan; Qin Yang; Zhiyi Lin; Tianrun Zheng; Maojia Wang; Wenjun Sun; Tongliang Bu; Zizhong Tang; Chenglei Li; Xueyi Han; Haixia Zhao; Qi Wu; et al. (Environmental Science and Pollution Research, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

The Efficacy and Safety of Transcranial Direct Current Stimulation for Cerebellar Ataxia: a Systematic Review and Meta-Analysis - Tiffany X. Chen; Chen-Ya Yang; Gloria Willson; Chih-Chun Lin; Sheng-Han Kuo (The Cerebellum, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Complete genome sequence of a new achyranthes virus A isolate from Achyranthes bidentata in China - Xinyang Wu; Yuchao Lai; Lanqing Lv; Kelei Han; Ziqiang Chen; Yuwen Lu; Jiejun Peng; Lin Lin; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2021)

Photosensitive hydrogels: from structure, mechanisms, design to bioapplications - Wenhui Ji; Qiong Wu; Xisi Han; Wei Zhang; Wei Wei; Liang Chen; Lin Li; Wei Huang (Science China Life Sciences, 2020)

Improving Image Correlation and Differentiation of 3D Endoluminal Lesions in the Air Spaces Using a Novel Target Gray Level Mapping Technique: A Preliminary Study of Its Application to Computed Tomographic Colonography and Comparison with Traditional Surface Rendering Method - Lih-Shyang Chen; Ta-Wen Hsu; Shao-Jer Chen; Shu-Han Chang; Chih-Wen Lin; Yu-Ruei Chen; Chin-Chiang Hsieh; Shu-Chen Han; Ku-Yaw Chang; Chun-Ju Hou (Journal of Medical and Biological Engineering, 2020)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Characterization of a Protease Hyper-Productive Mutant of Bacillus pumilus by Comparative Genomic and Transcriptomic Analysis - Yong-Cheng Liu; Lin-Li Han; Tian-Yu Chen; Yan-Bing Lu; Hong Feng (Current Microbiology, 2020)

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

Preparation and uranium (VI) biosorption for tri-amidoxime modified marine fungus material - Jingwen Han; Lin Hu; Leqing He; Kang Ji; Yaqing Liu; Can Chen; Xiaomei Luo; Ni Tan (Environmental Science and Pollution Research, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

Experimental study and engineering application of slurry permeability mechanism of slurry shield in circular-gravel stratum - Dongshuang Liu; Xinrong Liu; Chengqian Lin; Fei Xiong; Yafeng Han; Qingjun Meng; Zuliang Zhong; Qiang Chen; Chengxian Weng (Arabian Journal of Geosciences, 2020)

On the Sensitivity of Typhoon Wave Simulations to Tidal Elevation and Current - Shih-Chun Hsiao; Han-Lun Wu; Wei-Bo Chen; Chih-Hsin Chang; Lee-Yaw Lin (Journal of Marine Science and Engineering, 2020)
The sensitivity of storm wave simulations to storm tides and tidal currents was investigated using a high-resolution, unstructured-grid, coupled circulation-wave model (Semi-implicit Cross-scale Hydroscience Integrated System Model Wind Wave Model version III (SCHISM-WWM-III)) driven by two typhoon events (Typhoons Soudelor and Megi) impacting the northeastern coast of Taiwan. Hourly wind fields were acquired from a fifth-generation global atmospheric reanalysis (ERA5) and were used as meteorological conditions for the circulation-wave model after direct modification (MERA5). The large typhoon-induced waves derived from SCHISM-WWM-III were significantly improved with the MERA5 winds, and the peak wave height was increased by 1.0–2.0 m. A series of numerical experiments were conducted with SCHISM-WWM-II and MERA5 to explore the responses of typhoon wave simulations to tidal elevation and current. The results demonstrate that the simulated significant wave height, mean wave period and wave direction for a wave buoy in the outer region of the typhoon are more sensitive to the tidal current but less sensitive to the tidal elevation than those for a wave buoy moored in the inner region of the typhoon. This study suggests that the inclusion of the tidal current and elevation could be more important for typhoon wave modeling in sea areas with larger tidal ranges and higher tidal currents. Additionally, the suitable modification of the typhoon winds from a global atmospheric reanalysis is necessary for the accurate simulation of storm waves over the entire region of a typhoon.

Estimating purple-soil moisture content using Vis-NIR spectroscopy - Yu Gou; Jie Wei; Jin-lin Li; Chen Han; Qing-yan Tu; Chun-hong Liu (Journal of Mountain Science, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Miscanthus cultivation shapes rhizosphere microbial community structure and function as assessed by Illumina MiSeq sequencing combined with PICRUSt and FUNGUIld analyses - Yan Chen; Wei Tian; Yang Shao; Ying-Jun Li; Li-An Lin; Ying-Jun Zhang; Hui Han; Zhao-Jin Chen (Archives of Microbiology, 2020)

Description of Gemmobacter aestuarii sp. nov., isolated from estuarine surface water and reclassification of Cereibacter changlensis as Gemmobacter changlensis Chen et al. 2013 - Asif Hameed; Mariyam Shahina; Shih-Yao Lin; Wen-Ming Chen; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Archives of Microbiology, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Acute physiological responses to combined blood flow restriction and low-level laser - Yi-Ching Chen; Yu-Han Su; Yen-Ting Lin; Chien-Chun Huang; Ing-Shiou Hwang (European Journal of Applied Physiology, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

The response of warm-season precipitation extremes in China to global warming: an observational perspective from radiosonde measurements - Jianping Guo; Yan Yan; Dandan Chen; Yanmin Lv; Yi Han; Xiaoran Guo; Lin Liu; Yucong Miao; Tianmeng Chen; Ji Nie; Panmao Zhai (Climate Dynamics, 2020)

Cerebellar Volume Is Associated with Cognitive Decline in Mild Cognitive Impairment: Results from ADNI - Chi-Ying Lin; Chi-Hua Chen; Sarah E. Tom; Sheng-Han Kuo (The Cerebellum, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Optimization and Evaluation of the Thermosensitive In Situ and Adhesive Gel for Rectal Delivery of Budesonide - Lin Chen; Xue Han; Xiaohong Xu; Quan Zhang; Yingchun Zeng; Qing Su; Yujie Liu; Yanmei Sheng; Xingliang Xie (AAPS PharmSciTech, 2020)

Numerical Simulation of Large Wave Heights from Super Typhoon Nepartak (2016) in the Eastern Waters of Taiwan - Shih-Chun Hsiao; Hongey Chen; Han-Lun Wu; Wei-Bo Chen; Chih-Hsin Chang; Wen-Dar Guo; Yung-Ming Chen; Lee-Yaw Lin (Journal of Marine Science and Engineering, 2020)
Super Typhoon Nepartak (2016) was used for this case study because it is the most intense typhoon that made landfall in Taiwan in the past decade. Winds extracted from the Climate Forecast System version 2 (CFSV2) and ERA5 datasets and merged with a parametric typhoon model using two hybrid techniques served as the meteorological conditions for driving a coupled wave-circulation model. The computed significant wave heights were compared with the observations recorded at three wave buoys in the eastern waters of Taiwan. Model performance in terms of significant wave height was also investigated by employing the CFSV2 winds under varying spatial and temporal resolutions. The results of the numerical experiments reveal that the simulated storm wave heights tended to decrease significantly due to the lower spatial resolution of the hourly winds from the CFSV2 dataset; however, the variations in the storm wave height simulations were less sensitive to the temporal resolution of the wind field. Introducing the combination of the CFSV2 and the parametric typhoon winds greatly improved the storm wave simulations, and similar phenomena can be found in the exploitation of the ERA5 dataset blended into the parametric wind field. The overall performance of the hybrid winds derived from ERA5 was better than that from the CFSV2, especially in the outer region of Super Typhoon Nepartak (2016).

Effect of slope gradient on the subsurface water flow velocity of sand layer profile - Zhen Han; Xiao-yan Chen; Yu-han Huang; Bang-lin Luo; Hang Xing; Yong-chao Huang (Journal of Mountain Science, 2020)

Plasma biomarkers and plaque strain predict long-term cardiovascular events in patients with acute coronary syndrome - Mingjun Xu; Xiaobo Hu; Lin Wang; Wei Zhang; Lindi Wu; Jifu Li; Yuguo Chen; Pengfei Zhang; Haijun Su; Yaling Han; Cheng Zhang; Mei Zhang; et al. (Science China Life Sciences, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Remediation of TCE-contaminated groundwater using KMnO4 oxidation: laboratory and field-scale studies - Zong-Han Yang; Jiun-Hau Ou; Cheng-Di Dong; Chiu-Wen Chen; Wei-Han Lin; Chih-Ming Kao (Environmental Science and Pollution Research, 2019)

Cloning and overexpression of the ascorbate peroxidase gene from the yam (Dioscorea alata) enhances chilling and flood tolerance in transgenic Arabidopsis - Zhihua Chen; Hsueh-Han Lu; Shumei Hua; Kuan-Hung Lin; Ningdan Chen; Yangwen Zhang; Ziyi You; Yun-Wei Kuo; Shi-Peng Chen (Journal of Plant Research, 2019)

Plants alter their vertical root distribution rather than biomass allocation in response to changing precipitation - Bingwei Zhang; Marc W. Cadotte; Shiping Chen; Xingru Tan; Cuihai You; Tingting Ren; Minling Chen; Shanshan Wang; Weijing Li; Chengjin Chu; Lin Jiang; Yongfei Bai; et al. (Ecology, 2019)
Elucidating the variation of allocation pattern of ecosystem net primary productivity ( NPP ) and its underlying mechanisms is critically important for understanding the changes of aboveground and belowground ecosystem functions. Under optimal partitioning theory, plants should allocate more NPP to the organ that acquires the most limiting resource, and this expectation has been widely used to explain and predict NPP allocation under changing precipitation. However, confirmatory evidence for this theory has mostly come from observed spatial variation in the relationship between precipitation and NPP allocation across ecosystems, rather than directly from the influences of changing precipitation on NPP allocation within systems. We performed a 6‐yr five‐level precipitation manipulation experiment in a semiarid steppe to test whether changes in NPP allocation can be explained by the optimal partitioning theory, and how water requirement of plant community is maintained if NPP allocation is unaltered. The 30 precipitation levels (5 levels × 6 yr) were divided into dry, nominal, and wet precipitation ranges, relative to historical precipitation variation over the past six decades. We found that NPP in both aboveground ( ANPP ) and belowground ( BNPP ) increased nonlinearly as precipitation increased, while the allocation of NPP to BNPP ( f BNPP ) showed a concave quadratic relationship with precipitation. The declined f BNPP as precipitation increased in the dry range supported the optimal partitioning theory. However, in the nominal range, NPP allocation was not influenced by the changed precipitation; instead, BNPP was distributed more in the surface soil horizon (0–10 cm) as precipitation increased, and conversely more in the deeper soil layers (10–30 cm) as precipitation decreased. This response in root foraging appears to be a strategy to satisfy plant water requirements and partially explains the stable NPP allocation patterns. Overall, our results suggest that plants can adjust their vertical BNPP distribution in response to drought stress, and that only under extreme drought does the optimal partitioning theory strictly apply, highlighting the context dependency of the adaption and growth of plants under changing precipitation.

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

Spatial Distribution and Congener Profiles of Polybrominated Diphenyl Ethers in Surface Sediment from Sanmen Bay and Xiamen Bay, Southeast China - Kunyan Liu; Yong Qiu; Shanshan Zhou; Kunde Lin; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Usage patterns and comfort of gardens: a seasonal survey of internal garden microclimate in the aged care homes of Chengdu City - Hua Zong; Yin Liu; Qian Wang; Mei-lin Liu; Han Chen (International Journal of Biometeorology, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Different removal efficiency of disinfection-byproduct precursors between dichloroacetonitrile (DCAN) and dichloroacetamide (DCAcAm) by up-flow biological activated carbon (UBAC) process - Han Chen; Tao Lin; Wei Chen; Hang Xu; Hui Tao (Environmental Science and Pollution Research, 2019)

A global database of paired leaf nitrogen and phosphorus concentrations of terrestrial plants - Di Tian; Jens Kattge; Yahan Chen; Wenxuan Han; Yongkai Luo; Jinsheng He; Huifeng Hu; Zhiyao Tang; Suhui Ma; Zhengbing Yan; Quanhong Lin; Bernhard Schmid; et al. (Ecology, 2019)
Nitrogen (N) and phosphorus (P) are essential components of the basic cell structure of plants. In particular, leaf N and P concentrations and their stoichiometric relationship largely determine the photosynthesis, growth, reproduction, and ecophysiological processes of plants. As important leaf functional traits, leaf N and P concentrations and their stoichiometric relationship play vital roles in indicating plant nutrient‐use strategies and their evolution in terrestrial ecosystems. They also influence physiological and ecological processes in leaves (e.g., growth rate and energy metabolism) and productivity (e.g., net primary production and net ecosystem production) at ecosystem level. However, the lack of a comprehensive data set containing paired leaf N and P concentration records has distinctly limited research on nutrient stoichiometry and leaf functional traits. Here, we provide a global database of paired records of leaf N and P concentrations. A total of 11,354 individual records were acquired spanning 1,291 sites worldwide, including 201 families, 1,265 genera, and 3,227 species. The records span a latitudinal range of 45.28 °S to 68.35 °N and a longitudinal range of 155.5 °W to 168.0 °E. The variables provided for each individual record are (1) geographical location (longitude, latitude, and altitude); (2) matched leaf N and P concentrations and N:P ratio; (3) taxonomic information (family, genera, and species); (4) life form (angiosperm/gymnosperm, monocotyledonous/dicotyledonous and woody plants/herbaceous plants; note that woody plants were further divided into coniferous, deciduous broad‐leaved, and evergreen broad‐leaved woody species and that herbaceous plants were further divided into annual and perennial species); (5) mean annual temperature ( MAT ) and mean annual precipitation ( MAP ); and (6) soil N and P concentrations and pH value in some records. To date, this database is the world's largest database of paired leaf N and P concentrations, which contains matched information of geographical location, environmental factors, and taxa. We believe that the database will play a fundamental and crucial part of ecological stoichiometric studies. There are no copyright restrictions. When using this database, we kindly request that you cite this article, respecting all the authors’ hard work during sample collection and data compilation.

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Fatty acid composition and the evidence for mixed income–capital breeding in female Argentinean short-fin squid Illex argentinus - Dongming Lin; Fei Han; Sipeng Xuan; Xinjun Chen (Marine Biology, 2019)

Cloning, in silico characterization, subcellular localization, and expression of a heat shock cognate 70 kDa protein/gene (EjHsc70-2) from Eriobotrya japonica - Shoukai Lin; Ti Wu; Ming Li; Xiaoming Huang; Yanqing Zhang; Linxiao Han; Bisha Wu; Yu Chen; Suying Lin; Dahe Lin; Minlan Wu; Jincheng Wu (Acta Physiologiae Plantarum, 2019)

Natural CAC chemopreventive agents from Ilex rotunda Thunb. - Yueqing Han; Lin Zhang; Wei Li; Xinran Liu; Jiao Xiao; Gang Chen; Ning Li (Journal of Natural Medicines, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Effects of a Web-based Health Education Program on Quality of Life and Symptom Distress of Initially Diagnosed Advanced Non-Small Cell Lung Cancer Patients: A Randomized Controlled Trial - Chi-Chin Huang; Han-Pin Kuo; Yueh-E Lin; Shu-Ching Chen (Journal of Cancer Education, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Seismic imaging of the Formosa Ridge cold seep site offshore of southwestern Taiwan - Ho-Han Hsu; Char-Shine Liu; Sumito Morita; Shu-Lin Tu; Saulwood Lin; Hideaki Machiyama; Wataru Azuma; Chia-Yen Ku; Song-Chuen Chen (Marine Geophysical Research, 2018)

Plasminogen/thrombomodulin signaling enhances VEGF expression to promote cutaneous wound healing - Tsung-Lin Cheng; Po-Ku Chen; Wei-Kai Huang; Cheng-Hsiang Kuo; Chia-Fong Cho; Kuan-Chieh Wang; Guey-Yueh Shi; Hua-Lin Wu; Chao-Han Lai (Journal of Molecular Medicine, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Human Cutaneous Protothecosis: A Case Report and Review of Cases from Mainland China, Hong Kong, and Taiwan - Fang Wang; Peiying Feng; Yimin Lin; Xiaohong Chen; Dandan Xu; Zhuo Wang; Jiande Han (Mycopathologia, 2018)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Association between prenatal nickel exposure and preterm low birth weight: possible effect of selenium - Xiaojie Sun; Yangqian Jiang; Wei Xia; Shuna Jin; Wenyu Liu; Xin Lin; Hongxiu Liu; Xiaomei Chen; Yang Peng; Han Li; Bin Lu; Shunqing Xu; et al. (Environmental Science and Pollution Research, 2018)

Tacrine(10)-hupyridone, a dual-binding acetylcholinesterase inhibitor, potently attenuates scopolamine-induced impairments of cognition in mice - Huixin Chen; Siying Xiang; Ling Huang; Jiajia Lin; Shengquan Hu; Shing-Hung Mak; Chuang Wang; Qinwen Wang; Wei Cui; Yifan Han (Metabolic Brain Disease, 2018)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Monitoring rubber plantation distribution on Hainan Island using Landsat OLI imagery - Pengpeng Han; Jinsong Chen; Yu Han; Lin Yi; Yannan Zhang; Xiaoli Jiang (International Journal of Remote Sensing, 2018)

Transcriptome profile analysis reveals cardiotoxicity of maduramicin in primary chicken myocardial cells - Xiuge Gao; Lin Peng; Xiangchun Ruan; Xin Chen; Hui Ji; Junxiao Ma; Han Ni; Shanxiang Jiang; Dawei Guo (Archives of Toxicology, 2018)

Temporal changes in soil C‐N‐P stoichiometry over the past 60 years across subtropical China - Zaipeng Yu; Minhuang Wang; Zhiqun Huang; Teng‐Chiu Lin; Matthew A. Vadeboncoeur; Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2018)
Controlled experiments have shown that global changes decouple the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), resulting in shifting stoichiometry that lies at the core of ecosystem functioning. However, the response of soil stoichiometry to global changes in natural ecosystems with different soil depths, vegetation types, and climate gradients remains poorly understood. Based on 2,736 observations along soil profiles of 0–150 cm depth from 1955 to 2016, we evaluated the temporal changes in soil C‐N‐P stoichiometry across subtropical China, where soils are P‐impoverished, with diverse vegetation, soil, and parent material types and a wide range of climate gradients. We found a significant overall increase in soil total C concentration and a decrease in soil total P concentration, resulting in increasing soil C:P and N:P ratios during the past 60 years across all soil depths. Although average soil N concentration did not change, soil C:N increased in topsoil while decreasing in deeper soil. The temporal trends in soil C‐N‐P stoichiometry differed among vegetation, soil, parent material types, and spatial climate variations, with significantly increased C:P and N:P ratios for evergreen broadleaf forest and highly weathered Ultisols, and more pronounced temporal changes in soil C:N, N:P, and C:P ratios at low elevations. Our sensitivity analysis suggests that the temporal changes in soil stoichiometry resulted from elevated N deposition, rising atmospheric CO 2 concentration and regional warming. Our findings revealed that the responses of soil C‐N‐P and stoichiometry to long‐term global changes have occurred across the whole soil depth in subtropical China and the magnitudes of the changes in soil stoichiometry are dependent on vegetation types, soil types, and spatial climate variations.

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Spa therapy (balneotherapy) relieves mental stress, sleep disorder, and general health problems in sub-healthy people - Bei Yang; Qi-zhong Qin; Ling-li Han; Jing Lin; Yu Chen (International Journal of Biometeorology, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

The Distal Gut Bacterial Community of Some Primates and Carnivora - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Li Han; Yi Jiang; Xue-Shi Huang; Cheng-Lin Jiang (Current Microbiology, 2018)

Metaproteomics of marine viral concentrates reveals key viral populations and abundant periplasmic proteins in the oligotrophic deep chlorophyll maximum of the South China Sea - Zhang‐Xian Xie; Feng Chen; Shu‐Feng Zhang; Ming‐Hua Wang; Hao Zhang; Ling‐Fen Kong; Min‐Han Dai; Hua‐Sheng Hong; Lin Lin; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Viral concentrates (VCs), containing bioinformative DNA and proteins, have been used to study viral diversity, viral metagenomics and virus–host interactions in natural ecosystems. Besides viruses, VCs also contain many noncellular biological components including diverse functional proteins. Here, we used a shotgun proteomic approach to characterize the proteins of VCs collected from the oligotrophic deep chlorophyll maximum (DCM) of the South China Sea. Proteins of viruses infecting picophytoplankton, that is, cyanobacteria and prasinophytes, and heterotrophic bacterioplankton, such as SAR11 and SAR116, dominated the viral proteome. Almost no proteins from RNA viruses or known gene transfer agents were detected, suggesting that they were not abundant at the sampling site. Remarkably, nonviral proteins made up about two thirds of VC proteins, including overwhelmingly abundant periplasmic transporters for nutrient acquisition and proteins for diverse cellular processes, that is, translation, energy metabolism and one carbon metabolism. Interestingly, three 56 kDa selenium‐binding proteins putatively involved in peroxide reduction from gammaproteobacteria were abundant in the VCs, suggesting active removal of peroxide compounds at DCM. Our study demonstrated that metaproteomics provides a valuable avenue to explore the diversity and structure of the viral community and also the pivotal biological functions affiliated with microbes in the natural environment.

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Contaminant characteristics and environmental risk assessment of heavy metals in the paddy soils from lead (Pb)-zinc (Zn) mining areas in Guangdong Province, South China - Da-Mao Xu; Bo Yan; Tao Chen; Chang Lei; Han-Zhi Lin; Xian-Ming Xiao (Environmental Science and Pollution Research, 2017)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Qiuan Zhu; Changhui Peng; Philippe Ciais; Hong Jiang; Jinxun Liu; Philippe Bousquet; Shiqin Li; Jie Chang; Xiuqin Fang; Xiaolu Zhou; Huai Chen; Shirong Liu; et al. (Global Change Biology, 2017)
Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Regulatory element-based prediction identifies new susceptibility regulatory variants for osteoporosis - Shi Yao; Yan Guo; Shan-Shan Dong; Ruo-Han Hao; Xiao-Feng Chen; Yi-Xiao Chen; Jia-Bin Chen; Qing Tian; Hong-Wen Deng; Tie-Lin Yang (Human Genetics, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Mechanistic and therapeutic perspectives for cardiac arrhythmias: beyond ion channels - Yufei Wu; Jun Li; Liang Xu; Li Lin; Yi-Han Chen (Science China Life Sciences, 2017)

Apigenin alleviates STZ-induced diabetic cardiomyopathy - Huang-Jun Liu; Yun-Lin Fan; Hai-Han Liao; Yuan Liu; Si Chen; Zhen-Guo Ma; Ning Zhang; Zheng Yang; Wei Deng; Qi-Zhu Tang (Molecular and Cellular Biochemistry, 2017)

Follistatin-like protein 1 suppressed pro-inflammatory cytokines expression during neuroinflammation induced by lipopolysaccharide - Kai-Yuan Cheng; Yi Liu; Ying-Guang Han; Jing-Kun Li; Jia-Lin Jia; Bin Chen; Zhi-Xiao Yao; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2017)

Effects of rapid ascent on the heart rate variability of individuals with and without acute mountain sickness - Ming Ling Yih; Fang-Chi Lin; Heng-Sheng Chao; Han-Chen Tsai; Shi-Chuan Chang (European Journal of Applied Physiology, 2017)

Enterovirga rhinocerotis gen. nov., sp. nov., isolated from Rhinoceros unicornis faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Hui Lei; Yi Jiang; Li Han; Xue-Shi Huang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Joint 3D traveltime calculation based on fast marching method and wavefront construction - Hui Sun; Jian-Guo Sun; Zhang-Qing Sun; Fu-Xing Han; Zhi-Qiang Liu; Ming-Chen Liu; Zheng-Hui Gao; Xiu-Lin Shi (Applied Geophysics, 2017)

Wind and salt spray alter tree shape and dry mass density in Casuarina equisetifolia L. - Yongming Lin; Jian Li; Jonathan D. Bakker; Han Lin; Can Chen; Wei Hong; Loretta Fisher; Chengzhen Wu; Tao Hong; Haojun Deng; Guangshuai Zhang; Kun Du (Trees, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Molecular signal networks and regulating mechanisms of the unfolded protein response - Jing Gong; Xing-zhi Wang; Tao Wang; Jiao-jiao Chen; Xiao-yuan Xie; Hui Hu; Fang Yu; Hui-lin Liu; Xing-yan Jiang; Han-dong Fan (Journal of Zhejiang University-SCIENCE B, 2017)

Effect of LA on the Growth and Development of the Main Organs in Female Mice - Xiuyuan He; Feng Lin; Yongtao Li; Yuxia Chen; Jing Li; Linlin Guo; Xuelei Han; Huan Song (Biological Trace Element Research, 2017)

Hydrology Drives Vegetation Succession in a Tidal Freshwater Wetland of Subtropical Taiwan - Hsing-Juh Lin; Chun-Han Huang; Gwo-Wen Hwang; Chorng-Bin Hsu; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2016)

miR-137 and miR-491 Negatively Regulate Dopamine Transporter Expression and Function in Neural Cells - Xiaojian Jia; Feng Wang; Ying Han; Xuewen Geng; Minghua Li; Yu Shi; Lin Lu; Yun Chen (Neuroscience Bulletin, 2016)

PreSurgMapp: a MATLAB Toolbox for Presurgical Mapping of Eloquent Functional Areas Based on Task-Related and Resting-State Functional MRI - Huiyuan Huang; Zhongxiang Ding; Dewang Mao; Jianhua Yuan; Fangmei Zhu; Shuda Chen; Yan Xu; Lin Lou; Xiaoyan Feng; Le Qi; Wusi Qiu; Han Zhang; et al. (Neuroinformatics, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

Temperature dependent defence of Nicotiana tabacum against Cucumber mosaic virus and recovery occurs with the formation of dark green islands - Feifei Zhao; Yanan Li; Lijuan Chen; Lisha Zhu; Han Ren; Honghui Lin; Dehui Xi (Journal of Plant Biology, 2016)

Blood Cadmium Level Associates with Lower Testosterone and Sex Hormone-Binding Globulin in Chinese men: from SPECT-China Study, 2014 - Chi Chen; Ningjian Wang; Xiaomin Nie; Bing Han; Qin Li; Yi Chen; Hualing Zhai; Chunfang Zhu; Yingchao Chen; Fangzhen Xia; Meng Lu; Dongping Lin; et al. (Biological Trace Element Research, 2016)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

Correlation between the germline methylation status in ERβ promoter and the risk in prostate cancer: a prospective study - Lihui Wang; Pan Zhang; Xiannan Meng; Xiang Chen; Zou Xiang; Xiaoqian Lin; Ye Liu; Weidong Gan; Xiaodong Han; Dongmei Li (Familial Cancer, 2016)

Controversial opinion: evaluation of EGR1 and LAMA2 loci for high myopia in Chinese populations - Fang-yu Lin; Zhu Huang; Ning Lu; Wei Chen; Hui Fang; Wei Han (Journal of Zhejiang University-SCIENCE B, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Development of an agroinoculation system for full-length and GFP-tagged cDNA clones of cucumber green mottle mosaic virus - Hongying Zheng; Caili Xiao; Kelei Han; Jiejun Peng; Lin Lin; Yuwen Lu; Li Xie; Xiaohua Wu; Pei Xu; Guojing Li; Jianping Chen; Fei Yan (Archives of Virology, 2015)

Adenovirus-mediated osteoprotegerin ameliorates cartilage destruction by inhibiting proteoglycan loss and chondrocyte apoptosis in rats with collagen-induced arthritis - Zhi-yun Feng; Zhen-nian He; Bin Zhang; Yi-qiao Li; Jian Guo; Yuan-lin Xu; Ming-yuan Han; Zhong Chen (Cell and Tissue Research, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Haloarchaeobius amylolyticus sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Xin-Juan Sun; Xi Liang; Xiao-Jing Chen; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2015)

Research on Chinese public finance in response to domestic natural disasters - Yong-ling Zhang; Yan-nan Ma; An Chen; Yu-han Lin (Natural Hazards, 2015)

Effects of Spartina alterniflora Invasion on the Abundance and Community of Meiofauna in a Subtropical Wetland - Hsing-Juh Lin; Chorng-Bin Hsu; Szu-Han Liao; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Association analyses of FGFR2 gene polymorphisms with femoral neck bone mineral density in Chinese Han population - Shan-Shan Dong; Tie-Lin Yang; Han Yan; Zheng-Qin Rong; Jia-Bin Chen; Ruo-Han Hao; Xiao-Feng Chen; Yan Guo (Molecular Genetics and Genomics, 2015)

Production of Arachidonic and Eicosapentaenoic Acids by the Marine Oomycete Halophytophthora - Ka-Lai Pang; Han-Jia Lin; Hung-Yun Lin; Yu-Fen Huang; Yi-Min Chen (Marine Biotechnology, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Polarization of excitation light influences molecule counting in single-molecule localization microscopy - Ye Chen; Han Lin; Mandy J. Ludford-Menting; Andrew H. Clayton; Min Gu; Sarah M. Russell (Histochemistry and Cell Biology, 2015)

Removal of antineoplastic drugs cyclophosphamide, ifosfamide, and 5-fluorouracil and a vasodilator drug pentoxifylline from wastewaters by ozonation - Angela Yu-Chen Lin; Julia Han-Fang Hsueh; P. K. Andy Hong (Environmental Science and Pollution Research, 2015)

Indoor/outdoor pollution level and personal inhalation exposure of polycyclic aromatic hydrocarbons through biomass fuelled cooking - Guofeng Shen; Yanyan Zhang; Siye Wei; Yuanchen Chen; Chunli Yang; Pengchuan Lin; Han Xie; Miao Xue; Xilong Wang; Shu Tao (Air Quality, Atmosphere & Health, 2014)

Residues and dissipation of trifloxystrobin and its metabolite in tomatoes and soil - Lin Wang; Wenming Li; Puyu Li; Minghui Li; Shuo Chen; Lijun Han (Environmental Monitoring and Assessment, 2014)

Evaluation of Flow Velocity in Unilateral Middle Cerebral Artery Stenosis by Transcranial Doppler - Lin Wang; Yingqi Xing; Yang Li; Ke Han; Jiafeng Chen (Cell Biochemistry and Biophysics, 2014)

Dynamics of aeolian desertification and its driving forces in the Horqin Sandy Land, Northern China - Han-chen Duan; Tao Wang; Xian Xue; Shu-lin Liu; Jian Guo (Environmental Monitoring and Assessment, 2014)

Contamination and distribution of parent, nitrated, and oxygenated polycyclic aromatic hydrocarbons in smoked meat - Yuanchen Chen; Guofeng Shen; Shu Su; Huizhong Shen; Ye Huang; Tongchao Li; Wei Li; Yanyan Zhang; Yan Lu; Han Chen; Chunli Yang; Nan Lin; et al. (Environmental Science and Pollution Research, 2014)

Accuracy analysis of PPDF-based method to parameterize aerosol scattering effect - MingMin Zou; LiangFu Chen; JinHua Tao; Lin Su; Meng Fan; Ying Zhang; Dong Han (Science China Earth Sciences, 2014)

Re-Transurethral Resection Treatment for Non-invasive Bladder Tumor - Cong-hui Han; Zhenduo Shi; Xujun Xuan; Bo Chen; Bingzheng Dong; Lin Hao; Xiangzheng Qiu; Xiangju Zhou; Tian-lin Wu; Dong Liu (Cell Biochemistry and Biophysics, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Human hepatocellular carcinoma-infiltrating CD4+CD69+Foxp3− regulatory T cell suppresses T cell response via membrane-bound TGF-β1 - Yanmei Han; Yuan Yang; Zhubo Chen; Zhengping Jiang; Yan Gu; Yanfang Liu; Sheng Xu; Chuan Lin; Zeya Pan; Weiping Zhou; Xuetao Cao (Journal of Molecular Medicine, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Stripe rust resistance and genes in Chinese wheat cultivars and breeding lines - Qing-Dong Zeng; De-Jun Han; Qi-Lin Wang; Feng-Ping Yuan; Jian-Hui Wu; Li Zhang; Xiao-Jie Wang; Li-Li Huang; Xian-Ming Chen; Zhen-Sheng Kang (Euphytica, 2014)
Stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is one of the most important diseases on wheat in China. To assess resistance in wheat cultivars and breeding lines in China, 330 leading cultivars and 164 advanced breeding lines were evaluated with stripe rust. In the greenhouse tests, seedlings of the entries were inoculated separately with several Pst pathotypes. In the field tests, the entries were evaluated for stripe rust resistance in Yangling, Shaanxi Province artificially inoculated and in Tianshui, Gansu Province under natural infection of Pst . The oversummering/wintering and spring epidemic zones of resistance genes were postulated using molecular markers for Yr5 , Yr9 , Yr10 , Yr15 , Yr17 , Yr18 , and Yr26 , in combination with resistance spectra. Out of the 494 wheat entries, 16 (3.24 %) entries had all-stage resistance (ASR) in all race tests, 99 (20.04 %) had adult-plant resistance (APR), 28 (5.67 %) were considered to have slow-rusting (SR), and 351 (71.05 %) were susceptible to one or more races in both seedling and adult-plant stages. Advanced breeding lines had a higher percentage (37.2 %) of resistant entries (The sum of ASR, APR and SR) than leading cultivars (24.85 %). Among the epidemic regions, southern Gansu had a higher percentage of resistant entries than any other regions. Based on stripe rust reactions and molecular markers, two cultivars were found to possibly have Yr5 while no entries have Yr10 or Yr15 . Resistance genes Yr9 , Yr17 , Yr18 , and Yr26 were found in 134 (29.4 %), 45 (9.1 %), 10 (2 %), and 15 (3 %) entries, respectively.

Organic matters and lipid biomarkers in surface sediments from the northern South China Sea: Origins and transport - Weihai Xu; Wen Yan; Zhong Chen; Han Chen; Weixia Huang; Tian Lin (Journal of Earth Science, 2014)

A knockdown mutation of YELLOW-GREEN LEAF2 blocks chlorophyll biosynthesis in rice - Hong Chen; Zhijun Cheng; Xiaoding Ma; Han Wu; Yanling Liu; Kunneng Zhou; Yilin Chen; Weiwei Ma; Jingcui Bi; Xin Zhang; Xiuping Guo; Jiulin Wang; et al. (Plant Cell Reports, 2013)

Identification of appropriate reference genes for normalizing transcript expression by quantitative real-time PCR in Litsea cubeba - Liyuan Lin; Xiaojiao Han; Yicun Chen; Qingke Wu; Yangdong Wang (Molecular Genetics and Genomics, 2013)

Global and MGMT promoter hypomethylation independently associated with genomic instability of lymphocytes in subjects exposed to high-dose polycyclic aromatic hydrocarbon - Huawei Duan; Zhini He; Junxiang Ma; Bo Zhang; Zhiguo Sheng; Ping Bin; Juan Cheng; Yong Niu; Haiyan Dong; Han Lin; Yufei Dai; Benzhan Zhu; et al. (Archives of Toxicology, 2013)

The histone deacetylase inhibitor vorinostat prevents TNFα-induced necroptosis by regulating multiple signaling pathways - Di Wang; Ming Zhao; Guozhu Chen; Xiang Cheng; Xiaoxi Han; Song Lin; Xuhui Zhang; Xiaodan Yu (Apoptosis, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

A method to estimate concentrations of surface-level particulate matter using satellite-based aerosol optical thickness - JinHua Tao; MeiGen Zhang; LiangFu Chen; ZiFeng Wang; Lin Su; Cui Ge; Xiao Han; MingMin Zou (Science China Earth Sciences, 2013)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Chemistry, bioactivity and quality control of Dendrobium, a commonly used tonic herb in traditional Chinese medicine - Jun Xu; Quan-Bin Han; Song-Lin Li; Xiao-Jia Chen; Xiao-Ning Wang; Zhong-Zhen Zhao; Hu-Biao Chen (Phytochemistry Reviews, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

Retrieval of aerosol optical depth over bright targets in the urban areas of North China during winter - ShenShen Li; LiangFu Chen; JinHua Tao; Dong Han; ZhongTing Wang; Lin Su; Meng Fan; Chao Yu (Science China Earth Sciences, 2012)

High angle prestack depth migration with absorption compensation - Hui Zhou; He Lin; Shan-Bo Sheng; Han-Ming Chen; Ying Wang (Applied Geophysics, 2012)

Pharmacokinetics, Tissue Distribution, and Plasma Protein Binding Study of Platinum Originating from Dicycloplatin, a Novel Antitumor Supramolecule, in Rats and Dogs by ICP-MS - Di Zhao; Yongjie Zhang; Chunxiang Xu; Can Dong; Hui Lin; Lingli Zhang; Cuiyun Li; Shuangxia Ren; Xin Wang; Shuoye Yang; Deen Han; Xijing Chen (Biological Trace Element Research, 2012)

Amino Acid Profiles of Bivalve Mollusks from Beibu Gulf, China - De-Wei Chen; Jian Su; Xiao-Ling Liu; Dong-Mei Yan; Ying Lin; Wei-Ming Jiang; Xiao-Han Chen (Journal of Aquatic Food Product Technology, 2012)

Effect of elevated carbon dioxide on growth and nitrogen fixation of two soybean cultivars in northern China - Shu Kee Lam; Xingyu Hao; Erda Lin; Xue Han; Rob Norton; Arvin R. Mosier; Saman Seneweera; Deli Chen (Biology and Fertility of Soils, 2012)

Erbin inhibits TGF-β1-induced EMT in renal tubular epithelial cells through an ERK-dependent pathway - Qiaodan Zhou; Rui Zeng; Chuou Xu; Lili Liu; Lin Chen; Pei Kou; Guangchang Pei; Shoujun Bai; Yamin Zhang; Caixia Li; Song Rong; Min Han; et al. (Journal of Molecular Medicine, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease - Wu-Fu Chen; Chiranjib Chakraborty; Chun-Sung Sung; Chien-Wei Feng; Yen-Hsuan Jean; Yen-You Lin; Han-Chun Hung; Tzu-Yi Huang; Shi-Ying Huang; Thung-Ming Su; Ping-Jyun Sung; Jyh-Horng Sheu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Anti-tumor Function of Double-promoter Regulated Adenovirus Carrying SEA Gene, in the Treatment of Bladder Cancer - Jianpeng Hu; Xujun Xuan; Conghui Han; Lin Hao; Peiying Zhang; Meng Chen; Houguang He; Tao Fan; Binzheng Dong (Cell Biochemistry and Biophysics, 2012)

Plk1-mediated phosphorylation of UAP56 regulates the stability of UAP56 - Fuyin Xiong; Yanli Lin; Zhengbin Han; Gengshou Shi; Liyuan Tian; Xiaojie Wu; Qiangcheng Zeng; Yanrong Zhou; Jixian Deng; Hongxing Chen (Molecular Biology Reports, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

A convolution algorithm to calculate differential cross sections of the Ring effect in the Earth’s atmosphere based on rotational Raman scattering - Dong Han; LiangFu Chen; Lin Su; JinHua Tao; ShenShen Li; Chao Yu; Ying Zhang; BaoHua He (Science China Earth Sciences, 2011)

Dexamethasone attenuates development of monocrotaline-induced pulmonary arterial hypertension - Wei Wang; Yu-lin Wang; Xiao-ying Chen; Yu-tang Li; Wei Hao; You-peng Jin; Bo Han (Molecular Biology Reports, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Biomass and carbon dynamics of a tropical mountain rain forest in China - DeXiang Chen; YiDe Li; HePing Liu; Han Xu; WenFa Xiao; TuShou Luo; Zhang Zhou; MingXian Lin (Science China Life Sciences, 2010)

Cloning and characterization of a wheat β-1,3-glucanase gene induced by the stripe rust pathogen Puccinia striiformis f. sp. tritici - Bo Liu; Xiaodan Xue; Suping Cui; Xiaoyu Zhang; Qingmei Han; Lin Zhu; Xiaofei Liang; Xiaojie Wang; Lili Huang; Xianming Chen; Zhensheng Kang (Molecular Biology Reports, 2010)

Retrieval of aerosol optical properties over the Beijing area using POLDER/PARASOL satellite polarization measurements - Xuehua Fan; Hongbin Chen; Longfu Lin; Zhigang Han; Philippe Goloub (Advances in Atmospheric Sciences, 2009)

The effect of capillarisin on glycochenodeoxycholic acid-induced apoptosis and heme oxygenase-1 in rat primary hepatocytes - Tzung-Yan Lee; Fang-Yu Chen; Hen-Hong Chang; Han-Chieh Lin (Molecular and Cellular Biochemistry, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Nonlinear cooperation of p53-ING1-induced bax expression and protein S-nitrosylation in GSNO-induced thymocyte apoptosis: a quantitative approach with cross-platform validation - Shaojin Duan; Lin Wan; Wenjiang J. Fu; Hong Pan; Qi Ding; Chang Chen; Peiwei Han; Xiaoyan Zhu; Liying Du; Hongxiao Liu; Yuxia Chen; Ximing Liu; et al. (Apoptosis, 2009)

Tolerance and accumulation of lead by species of Iris L. - Yu-Lin Han; Su-Zhen Huang; Ji-Guang Gu; Shuo Qiu; Jie-Min Chen (Ecotoxicology, 2008)

A new species of Rhinogobius (Teleostei: Gobiidae) from the Feiyunjiang Basin in Zhejiang Province, China - Jin-Quan Yang; Han-Lin Wu; I-Shiung Chen (Ichthyological Research, 2008)

Improved neovascularization and wound repair by targeting human basic fibroblast growth factor (bFGF) to fibrin - Wenxue Zhao; Qianqian Han; Hang Lin; Yuan Gao; Wenjie Sun; Yannan Zhao; Bin Wang; Bing Chen; Zhifeng Xiao; Jianwu Dai (Journal of Molecular Medicine, 2008)

Cloning and expression study of a putative carotene biosynthesis related (cbr) gene from the halotolerant green alga Dunaliella salina - Chen Chen; Lin Han Bai; Dai Rong Qiao; Hui Xu; Gui Ling Dong; Kun Ruan; Fei Huang; Yi Cao (Molecular Biology Reports, 2008)

Glutamic acid 219 is critical for the thermostability of a truncated α-amylase from alkaliphilic and thermophilic Bacillus sp. strain TS-23 - Long-Liu Lin; Jai-Shin Liu; Wen-Ching Wang; Szu-Han Chen; Chih-Chen Huang; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Molecular Cloning and Expression Analysis of the Myostatin Gene in Sea Perch (Lateolabrax japonicus) - Han-Qing Ye; Song-Lin Chen; Zhen-Xia Sha; Yang Liu (Marine Biotechnology, 2007)

Pluripotency and Chimera Competence of an Embryonic Stem Cell Line from the Sea Perch (Lateolabrax japonicus) - Song-Lin Chen; Zhen-Xia Sha; Han-Qing Ye; Yang Liu; Yong-Sheng Tian; Yunhan Hong; Qi-Sheng Tang (Marine Biotechnology, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Specific Phage-Displayed Peptides Binding to Tumor Vasculature - Yu Han; Liu Hong; Kaichun Wu; Shuhui Liang; Lin Xia; Shanshan Cao; Huihong Zhai; Jun Wang; Lijie He; Feihu Bai; Zhen Chen; Taidong Qiao; et al. (International Journal of Peptide Research and Therapeutics, 2006)

Coordination between manganese and nitrogen within the ligands in the manganese complexes facilitates the reconstitution of the water-oxidizing complex in manganese-depleted photosystem II preparations - Shuqin Li; Guiying Chen; Guangye Han; Lin Ling; Deguang Huang; A. A. Khorobrykh; S. K. Zharmukhamedov; Qiutian Liu; V. V. Klimov; Tingyun Kuang (JBIC Journal of Biological Inorganic Chemistry, 2006)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

Mineralogical and geochemical study of a newly discovered mafic granulite, northwest China: Implications for tectonic evolution of the Altay Orogenic Belt - Han‐Lin Chen; Zi‐Long Li; Shu‐Feng Yang; Chuan‐Wan Dong; Wen‐Jiao Xiao; Yoshiaki Tainosho (Island Arc, 2006)
A mafic granulite body was newly discovered in the Altay Orogenic Belt, northwest China. The rocks comprise a suite of coarse‐grained and fine‐grained granulites. Orthopyroxenes (hypersthenes) in the rocks have high X Mg and low Al 2 O 3 contents, whereas clinopyroxenes have low TiO 2 and Al 2 O 3 contents. Amphiboles and biotites have a high Mg/(Mg + Fe 2+ ) ratio and low contents of F and Cl. The peak metamorphic pressure–temperature (P–T) conditions are estimated as 750–780°C and 6–7 kbar, and retrograde P–T conditions are in the range of 590–620°C and 2.3–3.7 kbar, indicating significant decompression. Metamorphic reactions and P–T estimates define a clockwise P–T path. Geochemically, the rocks are high in Mg/(Mg + Fe) and Al 2 O 3 , depleted in U, Th, K and Rb, and characterized by light rare earth element enrichment and a weak positive Eu anomaly. The Altay mafic granulite shows depleted Nb, P and Ti contents in the mid‐oceanic ridge basalt normalized spider diagram. The geochemical characteristics suggest that the protolith of the Altay mafic granulite was calc‐alkaline basalt and andesite with an island‐arc affinity. The rock has a high 143 Nd/ 144 Nd ratio with ɛNd(0) > 0, indicating derivation from a mantle‐depleted source. In the present study, a two‐stage model for the evolution of the Altay mafic granulite is proposed: an early stage in which calc‐alkaline basalt and andesite with island‐arc affinity were subducted into a deeper level of the crust and subjected to granulite‐facies metamorphism generating the mafic granulite, followed by the later stage exhumation of the system into the upper crust by the late Paleozoic thrusting.

Site-specific phosphorylation of L-form starch phosphorylase by the protein kinase activity from sweet potato roots - Guang-Huar Young; Han-Min Chen; Chi-Tsai Lin; Kuang-Ching Tseng; Jiann-Shing Wu; Rong-Huay Juang (Planta, 2006)

Effects of Growth Regulators on Direct Flowering of Isolated Ginseng Buds in vitro - Choun-Sea Lin; Chang-Tsern Chen; Han-Wen Hsiao; Wei-Chin Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Antimicrobial screening and active compound isolation from marine bacterium NJ6-3-1 associated with the sponge Hymeniacidon perleve - Li Zheng; Haimin Chen; Xiaotian Han; Wei Lin; Xiaojun Yan (World Journal of Microbiology and Biotechnology, 2005)

Nucleotide Sequences and Functions of the Epstein-Barr Virus Latent Membrane Protein 1 Genes Isolated from Salivary Gland Lymphoepithelial Carcinomas - Kai Yu Jen; Masaya Higuchi; Jun Cheng; Jiang Li; Lan Yan Wu; Ying Fang Li; Han Liang Lin; Zhilong Chen; Vladimir Gurtsevitch; Masahiro Fujii; Takashi Saku (Virus Genes, 2005)

An interspecific somatic hybrid between Actinidia chinensis and Actinidia kolomikta and its chilling tolerance - Zun-an Xiao; Lin-chen Wan; Bi-wen Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Modulation of Brain Activities by Hierarchical Processing: A High-Density ERP Study - Shihui Han; Silu Fan; Lin Chen; Yan Zhuo (Brain Topography, 1999)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)

Zinc supplementation on serum levels and hepatic conversion of thyroid hormones in obese (ob/ob) mice - Ming-Der Chen; Pi-Yao Lin; Wen-Han Lin (Biological Trace Element Research, 1998)

Zinc attenuation of GDP binding to brown adipocytes mitochondria in genetically obese (ob/ob) mice - Ming-Der Chen; Pi-Yao Lin; Piin-Sheng Chen; Vie Cheng; Wen-Han Lin (Biological Trace Element Research, 1997)

Zinc supplementation aggravates body fat accumulation in genetically obese mice and dietary-obese mice - Ming-Der Chen; Pi-Yao Lin; Vie Cheng; Wen-Han Lin (Biological Trace Element Research, 1996)

Dietary copper supplementation increases the catecholamine levels in genetically obese (ob/ob) mice - Wen-Han Lin; Ming-Der Chen; Chih-Chien Wang; Pi-Yao Lin (Biological Trace Element Research, 1995)

Selected metals status in patients with noninsulin-dependent diabetes mellitus - Ming-Der Chen; Pi-Yao Lin; Chung-Tide Tsou; Jyh-Jain Wang; Wen-Han Lin (Biological Trace Element Research, 1995)